Filter for water treatment

By integrating meteorites and minerals to emit natural vibrations and radiation, the water treatment filter alters water clusters, enhancing oxygen content and cellular effects, addressing the limitations of traditional purifiers.

JP2025011953AActive Publication Date: 2025-01-24堀 元英 +2
View PDF 47 Cites 0 Cited by

Patent Information

Application Number
JP2023114427
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-07-12
Publication Date
2025-01-24
Estimated Expiration
2043-07-12

AI Technical Summary

Technical Problem

Existing water purifiers fail to effectively address the structural changes in water clusters, which are believed to influence the biological and health effects of water, and lack scientific validation for wave-based water treatment methods.

Method used

A water treatment filter and purifier that incorporates meteorites and specific minerals, emitting natural vibrations and far-infrared radiation, along with sound waves and 1/f fluctuations, to alter the cluster structure of water.

Benefits of technology

The filter and purifier produce water with enhanced biological benefits, such as increased oxygen content and improved cellular effects, as demonstrated by experiments on unicellular organisms and human subjects.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025011953000001_ABST
    Figure 2025011953000001_ABST
Patent Text Reader

Abstract

To provide: water good for health for the purpose of promotion of cell activation without any scientific approaches involving chemicals present in nature such as ionized minerals, for example, calcium, artificial chemicals such as surfactants, antioxidants, antibiotics, and antifungal agents, or the like; a cartridge or a water purifier in such a fashion as to be able to bring tap water into contact with a meteorite, meteorite-containing ceramics (including clay firing for ceramics), or meteorite-containing fiber to apply meteorite characteristic vibration thereto, different from simple hazardous substance removal; and water having undergone the meteorite characteristic vibration.SOLUTION: A filter for water treatment includes: a container provided with a water introducing port and a water discharge port; a flowing water passageway running from the water introducing port to the water discharge port; and a meteorite of 0.0001 g or more provided in the flowing water passageway. Wave water (of a cluster size of hexamolecular structured water) obtained by applying meteorite characteristic vibration to water can be provided by a cartridge or a water purifier capable of bringing tap water into contact with the meteorite to apply the meteorite characteristic vibration thereto.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a water treatment filter, a cartridge or a water purifier that records the characteristic vibration of a meteorite by exposing water to the meteorite, and to water that has been subjected to the characteristic vibration of the meteorite. [Background technology]

[0002] There has been growing concern about the safety and health of tap water quality, and water has been sold in plastic bottles for a long time. Therefore, it is desirable for water purifiers to remove various harmful substances contained in tap water, such as bacteria (Patent Publication No. 2021-169072, Patent Publication No. 2021-159894), trihalomethanes (Patent Publication No. 2020-124714) (Patent Publication No. 2020-121288) (Patent Publication No. 2020-110801) (Patent Publication No. 2019-167258), heavy metals (Patent Publication No. 2021-176609), boron, arsenic The main focus is on removing substances such as phosphorus (Patent Publication No. 2021-171729), chloroform (Patent Publication No. 2022-017611), organic matter, impurities, harmful ions, etc. (Patent Publication No. 08-164380), trihalomethanes, chlorine, sodium hypochlorite, magnesium hydroxide, sodium hydroxide, algae, and germs (Patent Publication No. 2020-163370), and fluorosurfactants (Patent Publication No. 2022-093398). In addition, there are many patents for water purifiers that focus on water clusters, such as (JP 2022-099208), (JP 2022-102744), (JP 2011-025217), (JP 07-204635), (Jitsu Zenpei 04-131483), (Jitsu Zenpei 04-131482), (JP 2022-099208), etc.

[0003] In addition, patents have been devised for a water purifier that provides forced vibrations such as ultrasonic vibrations and electromagnetic vibrations (Utility Model Publication No. 06-048886), a water purifier that can clean electrodes using forced vibrations such as ultrasonic vibrations and electromagnetic vibrations (Utility Model Publication No. 06-048886), and a water purifier that enables regeneration of adsorbents by ultrasonic irradiation (JP Patent Publication No. 2008-136894). A water purifier has also been devised that activates water by vibrating a ceramic body that emits far-infrared rays (JP Patent Publication No. 2008-012506, Patent No. 2918535). The following water purifiers have been devised: a device that can reduce the size of water molecules without using an electrolysis system (Patent Publication No. 2022-099208); a water purifier that can be directly connected to a faucet and notify the user when it is time to replace the filtration cartridge (Patent Publication No. 2022-097852); and a magnetic treatment device that can modify the fluid by exposing it to magnetism while spontaneously inducing turbulent flow, minute vibrations, sound waves, etc. (Patent Publication No. 2010-253415). As examples of water purifiers that use magnets, there are water purifiers that incorporate magnets or magnetic circuits to provide a magnetically activated water purifier that combines the purification action of a filter with the activation action of magnetism (Patent Publication No. 2003-126865), and water purifiers in which the magnetic energy of a magnet acts on tap water, improving its penetration, dissolving power, and water purification power, thereby further enhancing its beneficial effects on the human body (Patent Publication No. 2004-261799).

[0004] It has become commonplace that drinking water such as tap water is not tasty to drink, but this is not just a matter of taste. Tap water that passes through water purification plants contains harmful substances such as trihalomethanes, residual chlorine, heavy metal ions, dioxins, sodium hypochlorite, magnesium hydroxide, sodium hydroxide, boron, arsenic, phosphorus, chloroform, various environmental hormones, fine metal particles, red rust, turbidity, bacteria, mold, algae, and the odors that result from them. These are the main substances that cause problems in tap water, and water purifiers such as activated carbon and hollow fiber membrane filters are available to remove these substances. However, even water that has passed through such water purifiers does not always have a positive effect on the body. We therefore investigated combinations of substances that could improve the properties of water itself and invented a water purifier using these combinations. However, water purifiers that are based on the idea of ​​applying vibrations (natural vibrations) have provided special vibration materials made from natural materials. 1. A water quality improvement device that uses special vibration stones made from natural materials and moderate far infrared rays (Patent Publication No. 2008-012503), 2. A boat that uses special vibration stones made from natural materials (Patent Publication No. 2008-012506), and 3. A container 1 that uses special vibration stones made from natural materials (Patent Publication No. 2008-012509) have been devised. In addition, regarding meteorites, although it is not a water purifier, there is a company that provides acupressure stimulation devices made by mixing meteorite chips into glass and molding them into a sphere in order to utilize the electromagnetic waves emitted from meteorites that have therapeutic effects (Jitou 3184863).

[0005] Others include a water purifier and its cartridge that can expose tap water to vibration-generating materials (JP Patent Publication 2004-195443), which provides a water purifier and its cartridge that can expose tap water to vibration-generating materials, particularly ivory, quartz, cinquefoil, kaolinite, wollastonite, rock crystal, lapis lazuli, pink calcite, sunstone, selenite, aquamarine, new jade, rose quartz, sodalite, banded carnelian, and amazonite. By using one or a mixture of several of these, the high-wave action associated with these materials can be applied to drinking water, and a mixture of three types of new jade, sodalite, and rose quartz has been proposed that has good results (Jitoku 3097013). Meteorites appear in the far-infrared emitting inorganic building material and manufacturing method for far-infrared emitting inorganic building material (Patent Publication No. 2005-097859). The present invention also provides a hydrosol (aromatic distilled water characterized by essential oils dissolved to their saturation limit) that is endowed with functionality such as negative ions, far infrared rays, deodorizing, antibacterial, antifungal effects, and freshness retention, as well as the expected effects of free radicals such as active oxygen, activating cells, revitalizing the cells, and providing an antioxidant effect. Hydrosols are particles, powders, or fine powders of natural minerals such as tourmaline (tourmaline), silica, obsidian, quartz, zeolite, magnetite, loess, lava, and meteorites, titanium oxide, coral, shellfish, crustacean shells, binchotan charcoal, bamboo charcoal, charcoal, seaweed charcoal, and ceramics, etc., extracted and purified with one or more of the above natural minerals, titanium oxide, coral, shellfish, shellfish shells, binchotan charcoal, bamboo charcoal, charcoal, seaweed charcoal, ceramics, etc., or mixed, stirred, and dispersed with deep seawater and an ion aqueous solution extracted and purified with natural minerals, titanium oxide, coral, shellfish, shellfish shells, binchotan charcoal, bamboo charcoal, charcoal, seaweed charcoal, ceramics, etc., to form hydrosols (stable suspensions in which solid particles are dispersed), and methods for producing the same are provided (JP Patent Publication No. 2004-018850). Unlike filtering that simply makes tap water taste better, there is a water purifier and its cartridge that can expose tap water to vibration-generating substances (ivory, quartz, cinnabar stone, kaolinite, wollastonite, rock crystal, lapis lazuli, pink calcite, selenite, aquamarine, new jade, rose quartz, sodalite, sunstone, banded carnelian, amazonite) (Patent Publication No. 2004-195443), and a high-energy water purifier and its cartridge that uses high-energy water purifier to pass tap water through vibration-generating substances (sodalite, new jade, rose quartz) (Jitou 3097013) have been released, but nothing else could be found.

[0006] Other examples of inventions relating to waves include JP 2006-314899, which describes a method for improving athletic ability using wave information water and for inducing self-healing improvement in areas with weakened abilities, and JP 07-198429, which provides a wave information converter that uses wave information of weak potential differences measured on the surface of living or non-living objects to convert various types of basic information into multiple information, such as automatically turning on and off alarm devices, fountain water supply devices, air conditioners, lighting devices, and plane synchronizers. There are many different documents and products available on types of purified water, including the above-mentioned vibrational water, magnetic water, tourmaline water, alkaline ionized water, acidic water, dissociated water (free water), water with small clusters (π water), active hydrogen water, negative ion water, deep ocean water, reduced water, electrolyzed water, oxygenated water, carbonated water, sparkling water, non-sparkling water, and raw water (mineral water, mineral water, deep well water, shallow well water, underground water, vanadium water, spring water, hot spring water, etc.). However, no documents could be found on filters, cartridges, or water purifiers that use meteorites, or on water that has passed through them.

[0007] Here, we will explain about clusters. A cluster is a group of two or more molecules or atoms that are gathered together through relatively weak interactions such as van der Waals forces and hydrogen bonds. Water is a typical substance that forms clusters through hydrogen bonds. Clusters are sometimes used to indicate the density of water molecules, but so far only two experiments have been found that accurately measured the clusters of liquid water. One was published in NATURE magazine (Vol 381 6 JUNE 1996) by K. Liu (Henan Polytechnic University) et al. in the United States. According to the study, water with a cluster size of six molecules has the highest specific heat and is the most stable, and the structure is cage-like, and it is concluded that a group of six H2O molecules is the most stable. In other words, the force is different even for the same water depending on the cluster structure. K. Liu et al. also stated that the experimental results are as shown in Figure 1. In another study, Saykally Richard J. (University of California at Berkeley, CA, USA) and others stated that hexamolecular water, that is, "a collection of six water molecules, is particularly important as the smallest representative of a multi-three-dimensional hydrogen bond structure." Richard J. and others also stated their experimental results as shown in the middle and upper right figures above (SCIENCE magazine). In addition, Masato Yasui et al. of the Department of Pharmacology, Faculty of Medicine, Keio University, have stated that water (H2O) is one of the most important molecules for living organisms, and that in fact, MRI (magnetic resonance imaging) reflects the dynamics of water molecules in the body and diagnoses cancer from differences in water structure. MRI is also used to analyze the morphology and function of the brain. However, the biological significance of water behavior in cancer cells and brain tissues remains largely unknown, and research on water structure in living organisms is lagging behind. One of the reasons for this is thought to be that water is difficult to study and there has been no observation technology. Analysis of cell membrane water diffusion as water molecule dynamics and free water and structured water inside and outside the cells as cell functions are necessary, and that water structure is considered essential for maintaining life, and further research is awaited. In other words, K. Liu et al. and Richard J et al. have stated that the structure of six water molecules in water is stable, and Masato Yasui et al. have stated that the structure of water molecules in water is necessary for maintaining life.

[0008] The group led by the late Satoru Mashimo (Professor at the Faculty of Science, Tokai University) has determined that for water to have the properties of water, at least six water molecules must exist together. Also, it was Matsushita Kazuhiro (formerly of JEOL) who claimed that the smaller the clusters, the tastier the water. Matsushita wrote a paper entitled "Looking at Foods with NMR - Differences in 'Taste' Captured at the Molecular Level" (Modern Chemistry, January 1989, 62-67). However, leaving aside the question of taste, K. Liu et al. and SAYKALLY Richard J. et al. say that five-membered ring water is not good. In other words, smaller clusters are not necessarily better water. So how do we create a cluster of six water molecules? Even if we could, it would be difficult to prove it. 17Even if there is a small change in the line width when examined with O-NMR, this is due to the influence of proton exchange as well as the rotational motion of the molecules, so there is no direct relationship to the speed of molecular motion. The indicator of molecular motion is the NMR T1 relaxation time (the time required for longitudinal magnetization, which has been shifted from the thermal equilibrium state, to return to the thermal equilibrium state), but even if the T1 relaxation time is observed, it is not possible to determine the size of the molecular group. All that can be measured is a characteristic time related to molecular motion. This is a case where we consider a "model" of a "molecular group" to explain the measurement results, and it is never related to the T1 relaxation time or 17 Changes in O-NMR linewidths are not evidence of the presence and size of molecular clusters. 17 It is not yet known whether the line width of O-NMR reflects the size of the water molecule cluster. 17 It is thought that detection by O-NMR (NMR is inexpensive, costing around 160,000 yen) is impossible. As such, it is difficult to obtain a precise molecular-scale description of the structure of water, and computer simulations using terahertz laser vibration-rotation tunneling spectroscopy have been devised to identify the structure of water, but this is not common because it requires expensive equipment costing around 16 million yen and software must be built separately. Furthermore, it may be possible to determine the exact structure by conducting a high-precision experiment using the Compton scattering method (a method of analyzing the energy difference before and after an X-ray particle (photon) collides with an electron and scatters, in order to investigate the state of electron movement in the molecule or atom under study) at the high-energy inelastic scattering beamline (BL08W) of SPring-8 (a large-scale synchrotron radiation facility located within Harima Science Garden City, 1-1-1 Hikarito, Sayo-cho, Sayo-gun, Hyogo Prefecture), but this would be an extremely large-scale undertaking. So, 17 We have devised a method for testing water that is healthy for the body that anyone can easily do without relying on O-NMR. This method is the above-mentioned trunk gravity axis test. There is Upright Kinesiology (an alternative medical diagnostic method that claims to diagnose illnesses and select treatment methods by palpating muscle strength. Invented by George Goodheart in 1964), and the Bi-Digital O-Ring Test (an alternative medical diagnostic method that uses finger strength. Invented around 1977 by Omura Yoshiaki, professor at New York Medical College and visiting professor at Showa University School of Medicine), but it is not necessarily a negative test among medical researchers and clinicians, as there are multiple hospitals, dental clinics, and acupuncture and bone setting clinics where medical professionals and medical researchers use this test as an examination method. However, it cannot be ignored that it has the drawback of not being able to be quantified. A method invented to visualize roughly the same idea as these will be described later. [Prior art documents] [Patent documents]

[0009] [Patent Document 1] Patent Publication No. 2021-169072 [Patent Document 2] Patent Publication No. 2021-159894 [Patent Document 3] JP 2020-124714 A [Patent Document 4] JP 2020-121288 A [Patent Document 5] JP 2020-110801 A [Patent Document 6] JP 2019-167258 A [Patent Document 7] Patent Publication No. 2021-176609 [Patent Document 8] Patent Publication No. 2021-171729 [Patent Document 9] JP 2022-017611 A [Patent Document 10] Japanese Patent Application Publication No. 08-164380 [Patent Document 11] JP 2020-163370 A [Patent Document 12] JP 2022-093398 A [Patent Document 13] Patent Publication No. 2022-099208 [Patent Document 14] JP 2022-102744 A [Patent Document 15] JP 2011-025217 A [Patent Document 16] Japanese Patent Application Publication No. 07-204635 [Patent Document 17] Publication No. 04-131483 [Patent Document 18] Publication No. 04-131482 [Patent Document 19] Patent Publication No. 2022-099208 [Patent Document 20] Japanese Utility Model Application Publication No. 06-048886 [Patent Document 21] Japanese Utility Model Application Publication No. 06-048886 [Patent Document 22] JP 2008-136894 A [Patent Document 23] JP 2008-012506 A [Patent Document 24] Patent No. 2918535 [Patent Document 25] Patent Publication No. 2022-099208 [Patent Document 26] Patent Publication No. 2022-097852 [Patent Document 27] JP 2010-253415 A [Patent Document 28] JP 2003-126865 A [Patent Document 29] JP 2004-261799 A [Patent Document 30] JP 2008-012503 A [Patent Document 31] JP 2008-012506 A [Patent Document 32] JP 2008-012509 A [Patent Document 33] Mito 3184863 [Patent Document 34] JP 2004-195443 A [Patent Document 35] Publication No. 3097013 [Patent Document 36] JP 2005-097859 A [Patent Document 37] JP 2004-018850 A [Patent Document 38] JP 2004-195443 A [Patent Document 39] Mito 3097013 [Patent Document 40] JP 2006-314899 A [Patent Document 41] JP 2001-104255 A [Patent Document 42] Japanese Patent Application Publication No. 07-198429 [Patent Document 43] JP 2001-321124 A [Patent Document 44] Japanese Patent Application Publication No. 06-130008 [Patent Document 45] JP 2004-016769 A [Patent Document 46] JP 2009-103298 A [Non-patent literature]

[0010] [Non-Patent Document 1] Explaining how to easily experiment with moving and levitating objects using ultrasound - YouTube<https: / / www.youtube.com / watch?v=l7BwWhFqqpU> [Non-Patent Document 2] Home Page How to move things with ultrasonic waves | Electronics Crafts (ele-lab.com)<https: / / www.ele-lab.com / usonic7.php> DISCLOSURE OF THEINVENTION [Problem to be solved by the invention]

[0011] The mysterious finding that "water records the effects of drugs and has the same effect" was published in the journal NATURE (No. 333, June 1988). The study was conducted by Jacques Benveniste (France) et al., in a paper titled "Degranulation of human basophils induced by highly diluted anti-IgE antiserum." The content of the paper is that when anti-IgE molecules that react specifically with IgE (a factor that causes allergic rhinitis and atopic dermatitis) on the surface of basophils in white blood cells meet, a phenomenon called degranulation of the basophils occurs, releasing histamine from within. Naturally, this phenomenon does not occur with ordinary distilled water, but IgE is dissolved in distilled water to make IgE water, which is then diluted 10 to the power of 60 with distilled water. This is equivalent to diluting 1mL of water on a cosmic scale, and in the end, the distilled water contains not a single molecule of IgE, so both in theory and in reality, IgE should have no effect. However, this water has the effect of the IgE that was initially dissolved in it, causing the basophils to degranulate, making this a mysterious paper. This has been proven by many institutions, but from a business perspective, this means medicines will not sell, and no one in the medical profession wants to know about it. In fact, they probably found it quite annoying. Although it gained the support of many advocates of homeopathy, it was later recalled due to its unscientific nature, most likely due to pressure from pharmaceutical companies. This paper is thought to be the first to popularize the word vibration. From now on, anything that has an effect on water in this way will be called vibration water. It is thought that vibrations, in some cases, may be related to the cluster structure of water.

[0012] In quantum mechanics, it is known that two seemingly contradictory properties, particle and wave, exist simultaneously. Quantum mechanics, along with general theory of relativity, is a theory that forms the basis of modern physics, and it mainly concerns the mechanics of microscopic physical phenomena such as molecules and atoms, or the electrons that make them up, and it has the idea of ​​the duality of particle and wave, in that some objects can be both particles and waves. This is not only seen in elementary particles, but also in composite particles such as atoms and molecules, and is thought to occur particularly in water molecules. In other words, the concept of quantum mechanics cannot be ignored when considering water. The important thing to note here is that it is a well-known fact that all matter on Earth, including electrons, atoms, and molecules, vibrates, even though it is invisible to the naked eye. It is no exaggeration to say that this world is a world of vibration. Vibration patterns are also influenced by the material, temperature, humidity, and other environmental factors, but the general vibration pattern is determined by the material. Jewelry is beautiful because it selectively reflects light, and it is believed that beautiful things have vibration patterns that they emit. There are stones called "power stones," and it is believed that this is also due to the vibration patterns that are unique to each stone. It is currently impossible to explain power stones academically, but quantum mechanics has revealed that, depending on the stone, wave information is similar to particle information, and it goes without saying that this is still a developing field, but I hope that unexpected things will be revealed in the future.

[0013] A group researching vibrations claims that there is a substance that activates the body's vitality and natural healing powers. They have applied for patent application 2001-321124, which claims that by continuously consuming a medium onto which vibration information has been transferred using a vibration measuring device, natural healing powers can be activated and a healthy body can be promoted. There are many others who say similar things, such as Masaru Emoto, director of the IHM General Research Institute, who first introduced the vibration measuring device (Magnetic Resonance Analyzer, MRA) to Japan. The vibration measuring device recommended by Emoto is a machine that measures the "vibrations" of the human body, food, etc., and is said to determine whether they are "good" or "bad." However, there is no scientific backing for this claim, and it is considered pseudoscience. This vibration measuring device is a diagnostic device developed by Ronald J. Weinstock at MRDC in California in 1989. At the time of development, it was called the Biocellar Analyzer, but at Emoto's request, it was changed to the vibration measuring device. A patent was applied for in Japan in 1994 as a computerized magnetic resonance analyzer, and patent 2647786 was granted in 1997. When measuring, if the target is an object, it is placed on top of the device, and if it is a human body, the "detection rod" is held in the hand and the "probe" held by the operator (the person measuring) is pressed against the operator's other hand, using the operator's body as an amplifier to send "vibrations" to the target. This will cause one of two types of electronic sounds to sound, and the number of times the action is repeated until the sound changes is counted, with a rating of plus or minus 21 for each measurement item. When the target is a human body, another method is used in which the operator places the probe on the subject holding the detection rod.

[0014] Five similar devices, including one named "Life Field Tester" (LFT), appeared in Japan as similar products, and when the wave measuring device introduced by Emoto Masaru was brought to the Subtle Energy Society to be examined, it was found that all of them were the same, in that the person taking the measurement was the sensor, but the measuring device itself was not equipped with a sensor, and that the code of the wave measuring device was random, and the change in electronic sound was caused by electrical resistance, and was unreliable and could be changed at the will of the operator. Hori Yasunori was also attending the society at that time. It was a type of what is commonly known as a lie detector. If the vibration meter had a built-in sensor and the code was accurate, it may not have been considered pseudoscience. I think the machine should have been questioned before it was released to the public. It is difficult to change something that has been labeled badly. Emoto had a tendency to focus on business, and it seems that he was viewed with suspicion. It is recorded that the vibration meter sold by Emoto Masaru in December 1988, 34 years ago, cost approximately 8.5 million yen. However, strangely enough, even though the vibration measuring device is unreliable, the results coincide with those of upright kinesiology and O-ring tests. In that sense, upright kinesiology and O-ring tests may also be unreliable, but they often coincide with blood test results, X-rays, CT scans, and MRIs. The current clinical situation is one that cannot be ignored, as people who cannot accept blood transfusions, blood draws, or medicine (new drugs) for religious reasons, people with extreme fear of injections, and people who become bedridden after blood draws are among those who are refused treatment if they cannot be tested, and people who post comments about it on the Internet.

[0015] In other words, regardless of whether or not vibration measuring devices can "transcribe" vibrations, it is a clear fact that vibrations specific to materials do exist. I asked a pear farmer who grows pears without pesticides, and he said that playing music (Mozwald) to pears improves the way the fruit develops and increases the sugar content. This is because there is a clear difference in sugar content of up to about 8% between a group that is exposed to music and a group that is not exposed to music, even for the same variety. It was said that water that has been subjected to the vibrations of sound transmits the vibrations to the pears and increases the sugar content. At first, the reason for this was not known, and the sound was played unevenly, but as the audible sound became quieter, the sugar content gradually decreased. This pear farmer plays Mozwald so that it can be heard evenly throughout the field from the time the pears bloom until the harvest, and they produce sweet pears. Before they go to market, fans come to buy them every year, saying that they are "sweet and delicious," so they are always sold out and there are no pears to go to market. He also explains how to easily carry out experiments to move and levitate objects using ultrasound - this is available on YouTube and on the website, Moving things with ultrasound | Electronic craft tips (ele-lab.com) (Non-Patent Document 1). Ultrasound is inaudible to the human ear but has powerful energy. The fact that sound vibrations can change the way water flows means that the structure of water clusters can be changed at the molecular level. If there is no change in the clusters, the way water flows cannot change. If sound frequency can affect the flow of water, then there is a possibility that the inherent vibrations of materials can also change the structure of water clusters, which led to the experiment. Furthermore, no literature on water purifiers was found. The present invention has been made in consideration of the above-mentioned problems, and its purpose is to provide a water treatment filter, cartridge, water purifier, and water that has been subjected to the meteorite's natural vibrations by exposing water to a meteorite and recording the meteorite's natural vibrations. [Means for solving the problem]

[0016] The present inventors have completed the present invention through extensive research. Thus, the water treatment filter of the present invention is characterized in that it comprises a container having a water inlet and a drain outlet, a water flow passageway extending from the water inlet to the drain outlet, and a meteorite disposed within the water flow passageway, the meteorite weighing 0.0001 g or more. In the water treatment filter of the present invention, it is preferable that the meteorite is pulverized to a size of 20 μm to 300 μm, kneaded into a ceramic material having an infrared emissivity of 90% or more, or mixed into a glaze, and then fired to form a ceramic. In addition, it is preferable that the meteorite is pulverized to a size of 20 μm to 300 μm and then kneaded into or adsorbed onto fibers. Moreover, it is preferable that the meteorite is pulverized to a size of 20 μm to 300 μm, and then kneaded into an adhesive such as cement. In addition to the meteorites, the water treatment filter of the present invention may further include (b) arcade, aquamarine, apatite, amazonite, alexandrite, andesine, amber, Iwo stone, ichikaku, Inca rose, wollastonite, emerald, ochre, onyx, opal, garnet, carnelian, kaolinite, amphibole, granite, volcanic glass, volcanic rock (Aomi Yakuseki) Itoigawa, volcanic rock (lava), talc, limonite, calcite, guiyangite, fish brain stone, fish / squid. Octopus otoliths, gold, silver, chrysocolla (no mineral name), crystal quartz, chrysoprase, kunzite, quercere stone, basalt, calcite, obsidian, amber, sapphire, samarskite, yttrium oxide, copper oxide, coral, sunstone, native copper (pyrite), red tallow, autumn stone, stalactite, silica, silicic cyst, zirconia (artificial), zircon (natural), super seven, sugilite, soft-shelled turtle shell, spinel, hematite, limestone ( quicklime), coal, abalone shell, xenotime, selenite, diorite, zoisite, ivory, sodalite, turquoise, tiger's eye, diamond, marble, tanzanite, chert, terahertz ore, celestial eye, topaz, tourmaline, Herkimer diamond, pearl, Maifan stone, platinum, palladium, bandit carnelian, jade, bismuth, Himekawa medicinal stone, fluorite, black star, black stone, clam shell (two pieces) It is preferable that the mineral contains 0.001 g (1 mg) of at least one raw material selected from the group consisting of 115 types of raw materials (hereinafter referred to as "group (b)"): pine shell, hematite, peridot, sodalite, horn hertz, malachite, sea pine, moonstone, Mumyoui ware, agate, meng stone, yangki stone, raspirazuri, labradorite, limonite, ruby, ruby ​​in zoisite, antelope horn, lepidolite, roselite, rhodonite, hearth eye, deer antler, and wild horse.

[0017] A water purifier according to another invention is characterized in that it contains an infrared radiator that emits infrared light in a wavelength range of 2 μm to 14 μm and has an emissivity of 90% or more when treated with the water treatment filter. A water purifier according to another invention is characterized by including the above-mentioned water treatment filter. A water treatment method according to another invention is characterized in that water is brought into contact with a meteorite having a mass of 0.1 mg or more at a flow rate of 10 mL / sec or less per unit mass (100 L / sec or less per 1 g unit mass of meteorite). At this time, it is preferable to bring (a) a meteorite having a mass of 0.1 mg or more and at least one type of raw material mineral selected from group (b) of 1 mg or more into contact with water at a flow rate of 10 mL / sec or less per unit mass (1 L / sec or less per 1 g unit mass of mineral). In addition, it is preferable that (a) a meteorite having a mass of 0.1 mg or more and at least one type of raw material mineral selected from group (b) having 1 mg or more of mineral are passed near the mineral without contacting the meteorite at a flow rate of 10 mL / sec or less per unit mass (1 L / sec or less per 1 g of mineral unit mass). A water purifier according to another invention is characterized by comprising the above-described water treatment filter and a sound wave irradiation device that applies sound waves of 20 Hz to 10,000 Hz to water passing through the filter. For the sound wave irradiation, only sound with a certain frequency can be used, or sound with sound waves of 20 Hz to 10,000 Hz (for example, music played from a CD (classical music such as Mozart or Beethoven) can also be used). A water purifier according to another invention is characterized by comprising the above-mentioned water treatment filter and a fluctuation device that applies 1 / f fluctuation to the water passing through the filter. 1 / f fluctuation is thought to be contained in sounds such as the sound of the ocean, the sound of a waterfall, the sound of a river, and swells. Therefore, the fluctuation device means a device that emits such sounds. Furthermore, water according to another invention is treated with the above-mentioned water treatment filter, and is characterized by having the effect of increasing the trunk gravitational axis (the load weight at which the hips collapse) by 5 kg or more. Another invention relates to a trunk weight testing device that is capable of measuring the pressing force between both hands in the vertical direction on the back of a subject, and is characterized in that it is equipped with a first pressing operation unit that can be pressed with either palm, a second pressing operation unit that can be pressed with the other palm and in a direction opposite to the pressing force of the first pressing operation unit, and a pressing force measuring unit that can measure the force applied to both pressing operation units. Effect of the Invention

[0018] According to the present invention, it is possible to provide water treatment filters, cartridges and water purifiers that have a record of the meteorite's natural vibrations by bringing water into contact with a meteorite, as well as water that has been subjected to the meteorite's natural vibrations. The water purifier of the present invention is a wave water purifier in which a wave generating material (meteorite + minerals) is placed in the flowing water passage. By having a wave generating material including meteorite in the flowing water passage in the container, the flowing water passing through can come into contact with the wave generating material and experience waves. Furthermore, according to the filter of the present invention, tap water or the like enters the filter through the water inlet and exits through the outlet at another outlet in the water purifier, during which time the wave action of meteorites and minerals can be exerted on the tap water. As a result, unlike simple tap water filtration, it has been successful in providing water that has a mild effect on the body, for example, water with a high oxygen content like blood, by bringing the tap water into contact with or passing near a wave generating substance including meteorites, and thus it is possible to provide such a filter. [Brief description of the drawings]

[0019] [Figure 1] FIG. 2 is a schematic diagram showing a cluster structure of water. [Diagram 2] This is a graph showing the results of 17O-NMR measurement of Yokkaichi's water supply. [Diagram 3] This is a graph showing the estimated results of 17O-NMR of well water from Yokkaichi. [Figure 4] This is a graph showing the results of 17O-NMR measurements of Yokkaichi tap water + meteorite + minerals. [Diagram 5] This is a graph showing the results of 17O-NMR measurement of Yokkaichi tap water + 0.01% ferric and trivalent iron salt. [Figure 6] This is a microscopic photograph (A) and an enlarged sketch (B) of a paramecium. [Figure 7] 1 is a graph showing the results of Example 7. [Figure 8] 1 is a graph showing the results of Example 8. [Figure 9]1 is a graph showing the results of Example 9. [Figure 10] 1 is a graph showing the results of Example 10. [Figure 11] 1 is a graph showing the results of Example 11. [Figure 12] 1 is a graph showing the results of Example 12. [Figure 13] 1 is a graph showing the results of Example 13. [Figure 14] 1 is a graph showing the results of Example 14. [Figure 15] 1 is a graph showing the results of Example 15. [Figure 16] 1 is a graph showing the results of Example 17. [Figure 17] 1 is a graph showing the results of Example 18. [Figure 18] 1 is a graph showing infrared emissivity showing the results of Example 19. (A) shows a comparison of the emissivity of a black body and ceramic, and (B) shows a graph of the infrared emissivity of ceramic. [Figure 19] 1 is a graph showing the results of Example 20. [Figure 20] 1 is a graph showing the results of Example 22. [Figure 21] FIG. 1 is a photograph showing some of the shapes of stones used in the experiment. [Figure 22] (A) Photograph of a meteorite crushed to a diameter of 300 μm, and (B) a meteorite crushed to diameters of 22 μm to 40 μm. [Figure 23] (A) Schematic diagram of the trunk gravitational axis test device, (B) photograph. [Figure 24] FIG. 1 is a photographic diagram for explaining a method for conducting a trunk gravitational axis test. [Diagram 25] This is a photograph explaining how to read the scale in the trunk gravitational axis test. [Figure 26] These are photographs showing the results of the component analysis of a stony meteorite. (A) shows the report, (B) the analysis results table by the FP method, and (C) the results of the X-ray fluorescence analysis. [Figure 27]These are photographs showing the results of the compositional analysis of an iron meteorite. (A) shows the report, (B) the analysis results table by the FP method, and (C) the results of the X-ray fluorescence analysis. [Figure 28] These are photographs showing the results of the compositional analysis of a stony-iron meteorite. (A) shows the report, (B) the analysis results table by the FP method, and (C) the results of the X-ray fluorescence analysis. [Figure 29] These are photographs showing the results of the component analysis of tektites. (A) shows the report, (B) the analysis results table using the FP method, and (C) the results of the X-ray fluorescence analysis. [Diagram 30] These are photographs showing the results of the compositional analysis of moldavite. (A) shows the report, (B) the analysis results table using the FP method, and (C) the results of the X-ray fluorescence analysis. [Diagram 31] These are photographs showing the results of the component analysis of Libyan glass. (A) shows the report, (B) the analysis results table using the FP method, and (C) the results of the X-ray fluorescence analysis. [Diagram 32] 13 is a graph showing the results of a trunk gravitational axis test according to changes in water temperature. [Diagram 33] These are photographs showing the results of investigating the changes in water due to sound frequency. From left to right in the top row, the results are shown for no sound waves (control), 23 Hz sound waves, 24 Hz sound waves, and 25 Hz sound waves, and from left to right in the bottom row, the results are shown for 10,000 Hz sound waves, 20,000 Hz sound waves, 28,000 Hz ultrasound, and 40,000 Hz ultrasound. [Diagram 34] FIG. 1 is a schematic diagram of an aquaporin. [Diagram 35] These are photographs showing the experimental conditions for Xenopus laevis: (A) a photograph showing the anesthesia injection, (B) a photograph showing the skin being peeled off, and (C) a photograph showing the extracted egg mass. [Diagram 36] Graph (1) showing the results of Example 75. [Figure 37] Graph (2) showing the results of Example 75. [Figure 38] FIG. 1 is a diagram showing the configuration of a water treatment filter and a water purifier. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0020] Next, embodiments of the present invention will be described with reference to the drawings. However, the technical scope of the present invention is not limited to these embodiments, and the present invention can be embodied in various forms without changing the gist of the invention. There are five types of meteorites used in this invention: (A) stony meteorites, which are meteorites that are mainly composed of silicate minerals. These are meteorites that may or may not have a spherulitic structure; (B) iron meteorites, which are meteorites that are mainly composed of metallic iron (Fe-Ni alloy) and may contain very small amounts of cobalt, gold, platinum, iridium, phosphorus, carbon, etc.; and (C) stony-iron meteorites, which are meteorites that are composed of almost equal amounts of Fe-Ni alloy and silicate minerals. These three types and (D) tektites, moldavite, Libyan glass, and other meteorites that were once thrown into space and fell to Earth again, as well as unclassified meteorites that have not yet been classified. Furthermore, we accept the theory that Libyan glass was formed by a meteorite impact and classify it as a type of tektite. Meteorites do not have a weak current flowing between positive and negative poles at both ends of the crystal like tourmaline crystals, nor do they have piezoelectric or pyroelectric properties or permanent electrodes. In other words, (A) is a stony meteorite, (B) is an iron meteorite that is mainly an alloy of iron and nickel, (C) is a stony-iron meteorite that is mainly a rock made of silicate minerals and iron and nickel alloys, and (D) is about 75% glass (SiO2) containing impurities such as AI, Fe, Ca, Na, K, Ba, Mg, Ti, Mn, Cu, and Sr. However, this study has proven that meteorites that have traveled through space have the power to activate water. I will explain this in turn, but I would like to state in advance that this phenomenon actually occurs, although it cannot be explained by modern science.

[0021] For convenience, the following method is called the Trunk Gravitational Axis Test. The method of the Trunk Gravitational Axis Test is as follows: (1) the subject clasps his fingers behind his back, (2) a modified grip dynamometer with a maximum value of 100 kg is prepared, (3) the operator holds the grip dynamometer at (A) and places (B) on the palm of subject 1, whose fingers are clasped behind his back. (4) The operator then slowly presses straight down. (5) The weight at which subject 1 collapses to the knees is recorded. (6) This time, the same procedure is repeated with only 5 mL of commercially available mineral water, and the weight at which subject 1 collapses to the knees is recorded. (7) This time, the subject drinks 5 mL of the water that has been used in various experiments and does the same thing. Details of the test will be described later. The results were obtained by masking the magnetic resonance analyzer (MRA), magnetic resonance analyzer, "Life Field Tester" (LFT), and other portable, compact wave measuring devices have been invented (JP Patent Publication 2004-016769), and even simpler monochrome wave measuring devices have been invented (JP Patent Publication 2009-103298), which have become popular among wave enthusiasts. However, these are heavily influenced by subjectivity, and what is interesting is that the results are almost identical despite the masking. Here, I will discuss the effects and efficacy of water. It is a well-known fact that the effectiveness of water varies depending on the stratum. In a report entitled "Mineral Balance Index for Delicious and Healthy Water" by Hashimoto, Sho (1988), Faculty of Engineering, Osaka University, published in Biology and Science, Vol. 26, No. 1 (issue 290), the Kakogawa River system and the Yumesaki River system, which originate from the hazy Tennaiyama Mountain in Oku-Tanba, have a good mineral balance and are less likely to cause strokes. It was announced that people living in these water systems are less likely to suffer from cerebral infarction. This has been thought to be largely due to mineral balance, but according to my research, there are many places throughout the country with better mineral balance. It is also now possible to produce water with a good mineral balance. So what is affecting this? This remains a question. Naturally, the main cause seems to be drinking it for a long time, but I think there may be something else as well. Furthermore, in recent years, there has been an increasing demand for tasty, healthy water, and one method is to use biogeofilters, selecting the filter mineral according to the water quality, for example by using a limestone filter for water lacking Ca, or a volcanic rock filter for water lacking SiO2, making it possible to make all water in the country tasty and healthy. Hashimoto et al. state that in addition to the major inorganic components discussed here, there may also be trace components that have an effect on water and health, and on the taste of water.

[0022] At around 6:35 a.m. on April 7, 1904 (Meiji 37), a meteorite fell in Imabuku, Tanba Sasayama City (then Imabuku, Okano Village, Taki County). It was discovered by Katsuzo Hata (deceased). It is a famous meteorite. It was passed to Tadashi Hiki (deceased), a professor at Kyoto University, and subsequent analysis revealed that it contained a high iron content of 94.85%, but only 4.44% nickel, which is usually about 7%, and therefore it was found to be a very rare meteorite that did not show the beautiful pattern unique to meteorites called Widmanstätten structure. Professor Hiki named this famous meteorite "Okano Meteorite" (diameter about 18 cm, weight 4.74 kg). It is said that meteorites used to fall in a much larger amount than they do now, even before the existence of human beings, though it was not thanks to this meteorite. It would not be surprising if meteorites were hidden deep underground. These days I've come to think that places known for their famous waters must have meteorites connected to them in some way. Incidentally, I don't know if it's because of the fog or the groundwater, but Tanba Sasayama has long been famous for its natural products, such as black beans, black edamame, matsutake mushrooms, chestnuts, Japanese yams, tea, large groups of scarlet swifts, storks, rock thrushes, and barn owls, as well as wild boars, beef, and Tanba ware. There is also a person named "Ine" in this area. They live in Kyoto and Wakayama, but their origins can be traced back to Tanba Sasayama. It is said that the root of a well is located there, so the name was given to "those who protect the well." This surname is rare nationwide, with only about 20 people. The water vein flows into the Kakogawa River system, and it is possible that it helps prevent cerebral infarctions. Therefore, when comparing the trends in the population of centenarians in Tanba Sasayama City (Hyogo Prefecture) with other cities, towns, and villages, the latest (2020) population of centenarians in Tanba Sasayama City (Hyogo Prefecture) is 47. We compared the population of people aged 100 and over in 2020 in Tanba Sasayama City (Hyogo Prefecture), Komono Town, Mie District (Mie Prefecture), and Oizumi Town, Oura District (Gunma Prefecture). First of all, the town with the closest population to Tanba Sasayama City in Japan is the neighboring town where I live, Komono Town, Mie County (Mie Prefecture), second is Oizumi Town, Oura County (Gunma Prefecture), third is Nagayo Town, Nishisonogi County (Nagasaki Prefecture), and fourth is Yomitan Village, Nakagami County (Okinawa Prefecture). There is data comparing the population of people over 100 years old mentioned above.

[0023] [Table 1]

[0024] Tanba Sasayama City has about 24 more centenarians than Komono Town, Mie District (Mie Prefecture), making it 2.043 times higher. In particular, Tanba Sasayama City and Oizumi Town, Oura District (Gunma Prefecture) are close second in population in Japan, but there is an overwhelming difference in the centenarian population, with about 27 more centenarians, making it 2.35 times higher. In third place is Nagayo Town, Nishisonogi District (Nagasaki Prefecture) with 30 people, or 1.567 times higher, and in fourth place is Yomitan Village, Nakagami District (Okinawa Prefecture) with 27 people, or 1.741 times higher. What is the difference? About 25 years ago, on August 5, 1997, in the Chubu Keizai Shimbun Medical News article "About Water," Hori Yasunori wrote, "Hexagonal Water is a Living Being," that there is a legend that "hermits eat mist and live forever." Of course, this is impossible, but would such a legend be passed down to this day without any basis? What if, when various conditions were met, water became structured, and the mist that the hermits drank or inhaled into their bodies was in fact hexagonal water? This is the theory he wrote. In Tanba Sasayama, there are many days from autumn to winter when the thick fog that is unique to the basin occurs, and the sea of ​​clouds that can be seen even from low mountains (such as Sakarigatake) is also called "Tanba fog" and has become a famous sight. It is said that the fog may be related to longevity in no small way.

[0025] 17 O-NMR next, 17 Water samples collected and prepared under the conditions in the following <Example 1> to <Example 4> were examined by O-NMR. Example 1 Tap water from Yokkaichi (7-6 Tomari-cho, Yokkaichi City, Mie Prefecture (hereinafter referred to as "collection location 1")) was collected on August 28, 2001. Example 2 Well water from Yokkaichi (water from Oiwake Torii, 1-3013-1 Oiwake 3-chome, Yokkaichi City, Mie Prefecture. Collected on August 28, 2001. <Example 3> Tap water from Yokkaichi (collection location 1, collected on August 28, 2001) into which meteorites and the above minerals were soaked. Example 4: 0.1 mg of ferric and trivalent iron salt was dissolved in 1 L of tap water from Yokkaichi City (collected at location 1 on August 28, 2001) (commonly known as pyewater). The results are shown in Figures 2 to 5. For the reasons mentioned above, the correlation between these results and clusters is not reliable. However, at present, there is no method to observe clusters other than terahertz laser vibration-rotation tunneling spectroscopy. In addition, it is said that piwater has a small water cluster size. 17 The results of O-NMR were consistent. However, Masakazu Okochi, a professor at Hosei University's Faculty of Engineering, and his colleagues say that the Cluster measurements are not related to the size of the water molecules.

[0026] Next, we investigated the changes in the population of Paramecium depending on the conditions. <Example 5> Number of divisions of Paramecium in tap water and well water An experiment was conducted on January 17, 2021 using the same types of tap water and well water as above to see whether they would affect the reproduction of the single-celled organism Paramecium. Generally, single-celled organisms do not have a concept of lifespan, but Paramecium undergoes a phenomenon whereby cells cannot divide unless they are allowed to self-reproduce and fuse after repeated isolation after division. This time and number of cells is used as a guideline for judging the quality of the water. Figure 6 shows a microscopic photograph of Paramecium (A) and an enlarged sketch (B). Paramecium was cultured in a plastic bottle. The optimum temperature for Paramecium growth is 26°C. Therefore, the room temperature was kept at 26°C. The plastic bottle was also covered to prevent the solution from evaporating and becoming contaminated. Each water sample was passed through two filters: a sterile syringe filter DISMIC AS type and a sterilizing Millex filter unit (33 mm). Although it is said that light does not affect the proliferation of paramecium, the light was set to 2250 lux. 150 paramecium were placed in each 1000mL plastic bottle containing 500mL of each culture medium (measurements were done in the same manner below using a 500mL graduated cylinder), and the numbers were counted every two days. Paramecium feed on bacteria such as bacteria and yeast, so they were fed 250mg of dried brewer's yeast and cultured with thorough stirring. Shimadzu Corporation's high-precision analytical electronic balance BM, capable of measuring 0.01mg, was used for measurements. In addition, the live or dead status of the paramecium was judged by observing them under a stereomicroscope. It was confirmed whether they were swimming or not. If they were alive, each cell would swim in a random direction, but if they were dead, they would either settle or float, so this was confirmed. From then on, the stereomicroscope used was the OLYMPUS SZX7. To determine whether a cell that was not swimming was alive or dead, a drop of water containing the cells was placed on a slide glass, a cover glass was placed on it, and the cells were observed under a microscope. If the two contractile vacuoles alternately opened and closed, the cell was considered alive, and if they remained open, the cell was considered dead. The change in the number of cells was recorded. Initially, the number of cells in 1 mL was 0.5. As an initial counting method for small numbers of individuals, 1 mL was dispensed with a micropipette and counted using a stereomicroscope. To prevent sampling error, the same procedure was repeated five times and the average was calculated. If the number of individuals increased, 2 mL of the sample was taken, saturated picric acid was added, and the specimen was fixed and counted under an OLYMPUS SZX7 stereomicroscope. At this time, a ruled glass slide was used to make the measurement easier. The measurement results were calculated based on the amount of dilution, and the number of individuals in 500 mL was calculated. The results are shown below.

[0027] Example 6: Changes in the number of Paramecium depending on conditions Below, we conducted an experiment to determine whether it had any effect on the reproduction of the single-celled organism, Paramecium. Generally, there is no concept of life span for single-celled organisms, but in the case of Paramecium, a phenomenon occurs where cells cannot divide unless they are allowed to repeatedly isolate themselves after division and undergo self-fertilization and conjugation. This time and number of cells is used as a guideline for judging the quality of water. Paramecium was cultured in a plastic bottle. The optimum temperature for Paramecium growth is 26°C. Therefore, the room temperature was kept at 26°C. The plastic bottle was also covered to prevent the solution from evaporating and becoming contaminated. Each water sample was passed through two filters: a sterile syringe filter DISMIC AS type and a sterilizing Millex filter unit (33 mm). Although it is said that light does not affect the proliferation of paramecium, the light was set to 2250 lux. 500 paramecium were placed in each 1000mL plastic bottle containing 500mL of each culture medium (measurements were performed using a 500mL graduated cylinder, and the same procedure was followed below), and the number was counted every two days. Paramecium feeds on bacteria such as bacteria and yeast, so they were fed 300mg of dried brewer's yeast and cultured with thorough stirring. Shimadzu Corporation's high-precision analytical electronic balance BM 0.01mg weighing possible was used for measurements. In the following examples, in order to ensure accuracy, all measurements were performed at the Showa University Department of Tissue Anatomy using Shimadzu Corporation's high-precision analytical electronic balance BM 0.01mg weighing possible. In addition, the live or dead status of the paramecium was judged by observing them under a stereomicroscope. It was confirmed whether they were swimming or not. If they were alive, each cell would swim in a random direction, but if they were dead, they would either settle or float, so this was confirmed. From then on, the stereomicroscope used was the OLYMPUS SZX7. To determine whether cells that are not swimming are alive or dead, a drop of water containing the cells is placed on a slide, a cover glass is placed on top, and the cells are observed under a microscope.If the two contractile vesicles open and close alternately, the cells are considered alive, and if they remain open, the cells are considered dead. Changes in the number of cells are recorded. Initially, the number of individuals per mL was 0.5. As an initial counting method for small numbers of individuals, 1 mL was dispensed with a micropipette and counted using a stereomicroscope. To prevent sampling error, we performed the same experiment five times and calculated the average. When the number of individuals increased, 2 mL of the sample was taken, saturated picric acid was added, and the samples were fixed and counted under an optical microscope (OLYMPUS CX21). An ocular micrometer was used for easy counting. The results were calculated based on the amount of dilution to determine the number of individuals in 500 mL. The same method was used in all subsequent experiments with Paramecium.

[0028] <Example 7> Paramecium experiment Various tap water and well water (water collected on January 17, 2021) Next, I conducted an experiment on the number of divisions of Paramecium in tap water from Yokkaichi City, tap water from Kakogawa, tap water from Sasayama, and well water from Yokkaichi City, well water from Kakogawa, and well water from Sasayama, using the same method. From then on, the method was the same for all experiments on Paramecium. An experiment was conducted on January 17, 2021 using the same types of tap water and well water as above to see whether they affected the reproduction of the single-celled organism Paramecium. The results of paramecium proliferation in Yokkaichi tap water (x), Kakogawa tap water (★), Sasayama tap water (●), Yokkaichi well water (▲), Kakogawa well water (■), and Sasayama well water (x in a circle) are shown in Table 2. The explanation of each mark corresponds to the explanation on the graph (the same applies below). The population peaked between the 8th and 12th and began to decline on the 16th. The difference between the tap water group and the well water group was clear. One factor may be that tap water contains chlorine. The change in population from the above results is shown in Figure 7. Well water seemed to favor the paramecium, but the growth rate was much slower than in saline.

[0029] [Table 2]

[0030] <Example 8> Table 3 shows the change in the population of Paramecium in Yokkaichi tap water and in water obtained by converting Yokkaichi tap water into 0.8% physiological saline. Figure 8 shows a graph of the change in the number of paramecium in Yokkaichi tap water with 0.8% salt dissolved in it. The proliferation of paramecium in the salt solution was as described above. Perhaps due to the osmotic pressure, paramecium divided vigorously.

[0031] [Table 3]

[0032] <Example 9> Paramecium was cultured after applying sounds of 23 Hz, 24 Hz, and 25 Hz to tap water in Yokkaichi. The results are shown in Table 4. Figure 9 shows a graph of the change in the number of Paramecium in Yokkaichi tap water when sounds of 23 Hz, 24 Hz, and 25 Hz were applied.

[0033] [Table 4]

[0034] <Example 10> Paramecium was cultured in tap water from Yokkaichi City that had been subjected to 1 / f fluctuations. The results are shown in Table 5. Figure 10 shows a graph of the change in the number of paramecium caused by tap water in Yokkaichi that had come into contact with "1 / f fluctuations." "1 / f fluctuations" also seemed to be effective.

[0035] [Table 5]

[0036] <Example 11> Paramecium was cultivated in tap water from Yokkaichi City, which was given 23 Hz, 24 Hz, and 25 Hz sounds plus "swells." Next, an experiment was conducted in the same way as above to see whether the reproduction of single-celled organisms, Paramecium, was affected by the vibrations of water from different meteorites. The meteorite-passing vibrational water used for cultivation was prepared by soaking 1.0 g of each meteorite (40 g in total) in 1000 mL of Yokkaichi tap water for 100 seconds and stirring the water, in the same manner as above. The meteorites used were (A) stony meteorite, (B) iron meteorite, (C) stony-iron meteorite, (D-1) tektite, (D-2) moldavite, (D-3) Libyan glass). The vibration water used for cultivation was made by stirring 1000mL of Yokkaichi tap water and applying sounds of 23 Hz, 24 Hz, and 25 Hz for 100 seconds. After that, the 23 Hz and 24 Hz sounds were applied simultaneously to create an "undulation" and the water was then applied to Yokkaichi tap water. Next, the 23 Hz and 25 Hz sounds were applied simultaneously to create an "undulation" and the water was then used to cultivate the paramecium. Table 6 shows the changes in the population of paramecium.

[0037] [Table 6]

[0038] Figure 11 shows a graph of the change in the number of paramecium in Yokkaichi City tap water after exposure to 23 Hz, 24 Hz, and 25 Hz sounds plus "1 / f fluctuations." The inventor was surprised to find that water that affects the growth of paramecium simply by applying sound and pulsation was created. Here we will discuss 1 / f fluctuations. The mechanism by which 1 / f fluctuations occur has not yet been clearly elucidated, but it is a phenomenon that is seen in many places in nature and is said to be a kind of fundamental law for the way groups of things move. Specific examples include the interval between human heartbeats, the flickering of a candle flame, the swaying of a train, the sound of a babbling brook, the movement of the eyes, sunlight filtering through the trees, the glow of fireflies, the settings of an electric fan, the swaying of a skirt, and the swaying of hair. In terms of physical properties, examples include the resistance of metals and the flow of information in a network, but the actual situation is unclear. The swell caused by the difference in frequency used here is also thought to be a 1 / f fluctuation. It is said that the human heartbeat rhythm also has 1 / f fluctuation, and that a normally functioning heart does not simply beat regularly, but maintains human life with 1 / f fluctuation. In addition, it is said that the electrical pulse intervals of the biosignals emitted by human nerve cells in biological rhythms, such as the frequency fluctuation of alpha waves in brain waves, also have 1 / f fluctuation. Like the golden ratio, 1 / f fluctuation is not just a cause of what people find comfortable, but it is said to be similar to the fundamental law of how all things in the universe move, although its origin is still a mystery. In other words, if you feel that undulations are comfortable, it is 1 / f fluctuation. I asked a pear farmer about this, and he told me that playing music (Motzwald) to pears improves the fruit's growth and sugar content, which may explain the story. In other words, sound, or 1 / f fluctuations, have a positive effect on the cellular level. I later conducted an experiment and found that high-frequency sounds do not seem to have a very positive effect on cells. In other words, it is best to use water with a frequency of a sound in Hz that is within the audible range and not generally unpleasant. Therefore, the wavelength of sound waves is 20Hz to 10,000Hz, and a water purifier that can apply 1 / f fluctuation is considered to be good. The wavelength of sound waves will be explained later using Xenopus eggs.

[0039] <Example 12> Water filtered through various meteorites Next, to examine whether there were differences depending on the type of meteorite, the following waters (D-1) to (D-4) were used. (D-1) Yokkaichi tap water in contact with tektite, (D-2) Yokkaichi tap water in contact with moldavite, and (D-3) Yokkaichi tap water in contact with Libyan glass were individually examined. The conditions were the same as above, except that 1.0 g of each was immersed in 1000 mL of Yokkaichi tap water for 100 seconds and stirred. Table 7 shows the change in paramecium population due to different meteorites. Figure 12 shows a graph of the population changes from the above results. As shown above, it was found that passing the water through at least tektite, moldavite, and Libyan glass had the same effect as well-water. Moldavite, tektite, and Libyan glass had almost the same effect, probably because they are formed in a similar way. The proliferation rate increased, although not as much as with saline water.

[0040] [Table 7]

[0041] <Example 13> Next, using a similar method, breeding experiments were conducted on Paramecium caudatum in various meteorites: (A) Yokkaichi tap water that had come into contact with a stony meteorite, (B) Yokkaichi tap water that had come into contact with an iron meteorite, and (C) Yokkaichi tap water that had come into contact with a stony-iron meteorite. The results are shown in Table 8. The order of most effective was stony-iron meteorites, followed by iron meteorites and then stony meteorites. Figure 13 shows the data in graph form. The meteorites had a positive effect on the single-celled organism Paramecium. As the human body is also an assembly of single cells, these meteorites should have a positive effect on human somatic cells. It is clear that there is a big difference compared to when only Yokkaichi tap water was consumed. In other words, this suggests that there is a positive effect on the human body as well.

[0042] [Table 8]

[0043] <Example 14> Water passing through various meteorites and all minerals Next, minerals were added to the meteorite-derived vibrational water and stirred to obtain vibrational water. An experiment was conducted in the same way as above to see if this water would affect the reproduction of the single-celled organism, Paramecium caudatum. Table 9 shows the change in the number of paramecium in Yokkaichi tap water that came into contact with tektite and total minerals, Yokkaichi tap water that came into contact with moldavite and total minerals, and Yokkaichi tap water that came into contact with Libyan glass and total minerals, in order from the top to bottom. Figure 14 also shows the data in graph form. It peaked on the 8th and continued until the 16th, then died out and reached a minimum on the 26th. The difference was clear when graphed. It wasn't because the composition of the water had changed. It was a mysterious phenomenon. The meteorite + gemstone vibrational water is thought to be useful for single-celled organisms. The method for selecting the minerals used will be described later.

[0044] [Table 9]

[0045] <Example 15> Next, Table 10 shows the change in the number of paramecium in the tap water of Yokkaichi that had been in contact with stony meteorites and total minerals, the water of Yokkaichi that had been in contact with iron meteorites and total minerals, and the water of Yokkaichi that had been in contact with stony-iron meteorites and total meteorites. Figure 15 shows the data in a graph. As shown in the figure, a clear difference was observed in the water that had been in contact with minerals compared to the tap water.

[0046] [Table 10]

[0047] <Example 16> Next, an experiment was conducted in the same way as above to see whether the vibrational water from different meteorites would affect the reproduction of the single-celled organism Paramecium. The vibrational water used for the cultivation was made from various meteorites ((A) stony meteorite, (B) iron meteorite, (C) stony-iron meteorite, (D-1) tektite, (D-2) moldavite, (D-3) Libyan glass), and 1.0 g of each meteorite (total of 40 g) was soaked in 1000 mL of Yokkaichi tap water for 100 seconds and stirred. The same test as above was conducted, except that the water used was the water that had been soaked in 1000 mL of Yokkaichi tap water for 100 seconds. The total meteorites used here include, in addition to tektites, moldavite, and Libyan glass, (A) stony meteorites, including 1. achondrite meteorite, 2. LL3 chondrite meteorite, 3. H3-5 chondrite meteorite, 4. CV3 chondrite meteorite, 5. R chondrite meteorite, 6. carbonaceous chondrite meteorite, 7. MC chondrite meteorite, 8. Bekaa 001, 9. NWA532 meteorite, 10. Allende meteorite, 11. Murchison meteorite, 12. Bashkounou meteorite, 13. Chelyabinsk meteorite, 14. Tarda meteorite, 15. Orgeir meteorite, 16. Gao meteorite, 17. Zag meteorite, 18. Ben Soul meteorite, 19. Vega meteorite, 20. Tamduct meteorite, 21. Porter-Lesparay meteorite, 22. Vega 001, 23. Cherga meteorite, 24. Rumuruti chondrite meteorite, 25. Enstatite chondrite meteorite, 26. Al-Hagounia meteorite, 27. NWA1180 meteorite, 28. NWA1232 meteorite, 29. NWA11900 meteorite, 30. NWA11304 meteorite, 31. Oum Dreyga meteorite, 32. Maricopa meteorite, 33. Mount Yirtkuq Bulak 006 meteorite, 34. NWA869 meteorite, 35. North West Africa 869 meteorite, 36. Acapulcoite-lodranites meteorite, 37. Ureilite, 38. 2008TC3 meteorite, 39. Almahata 50 types of meteorites: (A) iron meteorites, such as 1. Nantan meteorite, 2. Gibeon meteorite, 3. Sitta meteorite, 30. Muoninalusta meteorite, 31. angrite meteorite, 32. howardite meteorite, 33. diogenite meteorite, 34. Milbililii meteorite, 35. eucrite meteorite, 36. Meteorlong meteorite, 37. NWA7831 meteorite, 38. shergottite meteorite, 39. chasinite meteorite, and 40. NWA1180 meteorite. On meteorite, 3. Campo del Cielo meteorite, 4. Ulak meteorite, 5. Canyon Diablo meteorite, 6. Gebel Kamil meteorite, 7. Mundra Villa meteorite, 8. Agdal meteorite, 9. Altai meteorite, 10. Doronino meteorite, 11. Sikhote-Alin meteorite, 12. Swedish Muonionalusta meteorite, 13. Tsingur meteorite, 14. San-Auban meteorite, 15. Xinjiang meteorite, 16. Madagascar meteorite, 17. Taza (NWA859) meteorite, 18. Toluca meteorite, 19. Mandrabira meteorite, 20. Odessa meteorite, 21. Turgut meteorite, 22. Ataxite meteorite, 23. Imiltil meteorite, 24.24 types of Doronimo meteorites and (C) stony-iron meteorites: 1. Brahin meteorite, 2. Imilak meteorite, 3. Esquel meteorite, 4. NWA4747 meteorite, 5. Serico meteorite, 6. Seymchan meteorite, 7. Sublimated iron meteorite, 8. Hakkitta meteorite, 9. Mesosiderite meteorite, 10. Blenheim meteorite, 11. Quising meteorite, 12. Zinder meteorite, 13. Springwater meteorite, 14. Mount Yirtkuq Bulak A total of 100 types of meteorites, including 20 types of meteorites (1.006 meteorite, 15. Vaca Muerta meteorite, 16. Krasnoyarsk meteorite, 17. Fukang meteorite, 18. NWA4747 meteorite, 19. Fukan meteorite, 20. Esquel meteorite, and 3 unclassified types), were crushed to diameters of 20~40μm and approximately 300μm to obtain meteorite powder. From these, exactly 1.00g of each was taken, and 100 types of meteorite powder was obtained in total. In the following, the term "total meteorites" indicates that the 100 types of meteorites listed above were used.

[0048] In addition, various minerals (arcade, aquamarine, apatite, amazonite, alexandrite, andesine, amber, Iwo stone, ichikaku, Inca rose, wollastonite, emerald, ochre, onyx, opal, garnet, carnelian, kaolinite, amphibole, granite, volcanic glass, volcanic rock (Qinghai medicinal stone) Itoigawa, volcanic rock (lava), talc, limonite, calcite, guiyang stone, fish brain stone, fish, squid, and octopus otoliths, gold, silver, kinka stone (no mineral name), chrysocolla) (malachite), crystal quartz, chrysoprase, kunzite, quesera stone, basalt, calcareous, obsidian, amber, sapphire, samarskite, yttrium oxide, copper oxide, coral, sunstone, native copper (pyrite), red quartz, autumn stone, stalactite, silica, silicic cyst, zirconia (artificial), zircon (natural), super seven, sugilite, soft-shelled turtle shell, spinel, hematite, lime (quicklime), coal, abalone shell, xenotime, selenite, diorite , Zoisite, Ivory, Sodalite, Turquoise, Tiger's Eye, Diamond, Marble, Tanzanite, Chert, Terahertz Ore, Eye of the Eye, Topaz, Tourmaline, Herkimer Diamond, Pearl, Maifan Stone, Platinum, Palladium, Banded Carnelian, Jade, Bismuth, Himekawa Yakuseki, Fluorite, Black Star, Black Stone, Clam Shell (Bifid Shell), Hematite, Peridot, Sodalite, Hornhell, Malachite, Sea Pine, Moonstone The same conditions as above were used, except that the water used was 1.0 g of water treatment filters (corresponding to claim 1) containing 0.001 g (1 mg) of at least one raw material selected from 115 types (i.e., thorn, Mumyoui ware, agate, meng stone, yangki stone, raspirazuri, labradorite, limonite, ruby, ruby ​​in zoisite, antelope horn, lepidolite, roselite, rhodonite, hearth eye, deer antler, and wild horse), totaling 114 g, soaked in 1000 mL of Yokkaichi tap water for 100 seconds and stirred. Hereafter, "total minerals" refers to the 115 types of minerals listed above.

[0049] Example 17: Changes in the population of Paramecium due to tap water from Yokkaichi City exposed to total minerals Table 11 shows the change in the population of Paramecium due to contact with total minerals in Yokkaichi tap water. Figure 16 shows the total changes in the population of Paramecium caused by contact with the tap water of Yokkaichi City after contact with the total minerals listed above.

[0050] [Table 11]

[0051] <Example 18> Change in the population of Paramecium due to tap water in Yokkaichi City exposed to total meteorites + total minerals + sound waves Table 12 shows the results of investigating the change in the population of paramecium caused by contact with total meteorites, total minerals, and sound waves in Yokkaichi tap water. Figure 17 shows the total changes in the population of paramecium cultured in Yokkaichi tap water that had been exposed to the above total meteorites and minerals and sound waves.

[0052] [Table 12]

[0053] <Example 19> Change in the population of Paramecium in tap water in Yokkaichi City using infrared radiation ceramics For infrared radiation, the following infrared radiation material "Ash that emits far-infrared rays and ash of a composition that emits far-infrared rays" was used, which was patented by Yasunori Hori in JP 08-104609. The graph of the infrared emissivity is shown in Figure 18. This ash was mixed with pottery material and then fired to make ceramic. As shown in the figure, it was a ceramic with an infrared emissivity of about 95%.

[0054] <Example 20> Tap water from Yokkaichi in contact with infrared radiation ceramic The change in population of paramecium cultured in tap water from Yokkaichi that had been in contact with the infrared radiation ceramic is shown in Table 13 and Figure 19. It was found that infrared radiation had an effect, although the effect was small.

[0055] [Table 13]

[0056] <Example 21> Table 14 shows the results of investigating the change in the population of paramecium due to Yokkaichi tap water that had been in contact with total meteorites + total minerals + infrared rays + sound waves + 1 / f. The water used for cultivation was 1000mL of Yokkaichi tap water, which was stirred, and 100g of the above total meteorites (1.0g of each meteorite) were added to it to bake the ceramic, and after stirring for 100 seconds, the meteorite ceramic was removed. Then, 1.0g of each of the above minerals was added to the water, totaling 114g. After that, sounds of 23 Hz, 24 Hz, and 25 Hz were applied for 100 seconds. After that, 23 Hz and 24 Hz sounds were played simultaneously to create a "swell" and applied to Yokkaichi tap water. Next, 23 Hz and 25 Hz sounds were played simultaneously to create a "swell" and applied to Yokkaichi tap water for 100 seconds, and the water was irradiated with far infrared rays for 100 seconds, and the paramecium was cultivated using this water. Here, we will explain 1 / f fluctuations. The mechanism by which 1 / f fluctuations occur has not yet been clearly elucidated, but it is a phenomenon that is seen in many places in nature, and we know that it seems to be a kind of fundamental law of how groups of things move. The ripples caused by this difference in frequency also seem to correspond to 1 / f fluctuations.

[0057] <Example 22> The results of an investigation into changes in the population of paramecium in Yokkaichi tap water that had come into contact with total meteorites and total minerals were presented. A clear difference was found when compared to culturing with only Yokkaichi tap water. It should be noted here that the number of individuals began to decrease from the 16th, but after 28 days, the number of individuals in the group that was exposed to Yokkaichi tap water + total meteorites + total minerals + sound waves had recovered slightly. This was thought to be because the dead members of the group had started to decompose and the paramecium were able to extract nutrients from them. Naturally, the same phenomenon should have occurred with Yokkaichi tap water, but the paramecium had no power left in tap water or well water, and it was thought that they had died. What is amazing here is that the effect of the water was still there even after 30 days. It was as if the tap water had been completely transformed after only a few minutes of contact with meteorites, minerals, sound, and 1 / f fluctuations. It was a difference in advantage that went beyond a simple advantage. It was a phenomenon that was difficult to imagine with common sense. Figure 20 shows the total changes in the population of cultured Paramecium. This is a phenomenon that I believe may be occurring, as Benveniste said, that water has memory. I was very hesitant to write this because it was unscientific and because Benveniste's paper was later recalled. However, although it may seem ridiculous, it is a factual result. If I had not been able to obtain such results, I would never have wanted to write a patent.

[0058] [Table 14]

[0059] Next, we examined whether there was a difference in the water before and after the meteorite was dropped. <Example 23> Next, we verified whether meteorite components would dissolve in water. We conducted water quality tests on tap water collected at 7-6 Tomari-cho, Yokkaichi City, Mie Prefecture on January 17, 2011, and on water after soaking and filtering various meteorites. We used 100g of each meteorite per liter of tap water. Each meteorite was left in running water for 72 hours. The method used included seven magnetic stirrers and a 2L beaker, and all operations were carried out in a drive chamber manufactured by Soda Kogyo Co., Ltd. to prevent contamination. (a) To cut out the various meteorites, a dental technician's magnifying glass was used, minerals were cut out with a dental diamond desk, and scraped with a dental diamond bur, and 10g was added to make 100g. (b) The measuring device used was a Shimadzu Corporation high-precision analytical electronic balance BM capable of measuring 0.01mg. (c) The water used was 1,000mL of tap water, after the various meteorites had been thoroughly washed with tap water from Yokkaichi City, Mie Prefecture. (d) Stirring was performed using a REXIM magnetic stirrer at 100 rpm for 72 hours. Ten 10g samples of various meteorites ((A) stony meteorite, (B) iron meteorite, (C) stony-iron meteorite, (D-1) tektite, (D-2) moldavite, (D-3) Libyan glass) were soaked in water weighing 100g each for 72 hours. (f) To extract the minerals, the water was filtered using a single coffee filter, and the components of the water were examined. The results are shown in Table 15. In the table, "cis-1,2-dichloroethylene, etc." refers to cis-1,2-dichloroethylene, trans-1,2-dichloroethylene, dichloromethane, tetrachloroethylene, trichloroethylene, benzene, chloroform, dibromochloromethane, bromic acid, total trihalomethanes, bromodichloromethane, and bromoform. No scientific changes were found in tap water that had been in contact with various meteorites ((A) stony meteorite, (B) iron meteorite, (C) stony-iron meteorite, (D-1) tektite, (D-2) moldavite, (D-3) Libyan glass) for 72 hours. In other words, no scientific changes such as the release of ions or the removal of harmful substances were found in the tests. [Table 15]

[0060] <Example 24> A magnetic stirrer and a 2L beaker were prepared, and all operations were carried out in a drive chamber manufactured by Soda Kogyo Co., Ltd. to prevent contamination. To extract the various meteorites, (a) a dental technician's magnifying glass was used to extract the minerals with a dental diamond desk, and a dental diamond bur was used to cut them into 100g pieces. (b) The measuring device used was a Shimadzu Corporation high-precision analytical electronic balance BM capable of measuring 0.01mg. (c) The water used was from the tap water of Yokkaichi City, Mie Prefecture, after thoroughly rinsing the various meteorites, and 1,000mL of tap water was used. (d) A magnetic stirrer REXIM was used for stirring at 500 rpm for 72 hours. 100 g of various meteorites ((A) stony meteorite, (B) iron meteorite, (C) stony-iron meteorite, (D-1) tektite, (D-2) moldavite, (D-3) Libyan glass) were soaked for 72 hours. (f) Tweezers were used to remove the minerals. The meteorite was immersed in tap water (temperature 25°C) and the electrical resistivity (Ω·cm) and electrical conductivity (μs / cm) were measured. The measurement equipment used was a portable electrical conductivity meter CM-31P-W (for pure water) manufactured by Toa DKK. Table 16 shows the analysis results. Although they soaked it for 72 hours instead of the usual 100 seconds, no change was observed. In other words, it was not thought that anything had dissolved. Substances can have both good and bad effects. A drug can be thought of as a substance that emphasizes its good points. A substance can induce or inhibit enzyme activity, and in combination with other substances, can become toxic. These phenomena are important issues in toxicology, but it has been reported that a major difference between meteorites and terrestrial rocks is the composition of the isotopes of He, Ne, Ar, Kr, and Xe. The most notable is helium, with meteorites showing a higher isotope composition than rocks on Earth. 3 He / 4 He isotope ratio is 10 -4 on the order of magnitude, whereas that of Earth's rocks is 10 -6 The amount of uranium and thorium produced by the nuclear decay of rocks on Earth is very low. 4 In meteorites, the helium is added to the rocks. 3 He / 4There are many isotopes of He. However, it is unlikely that these will chemically affect water and thus affect the body.

[0061] [Table 16]

[0062] <Example 25> The same experiment was conducted using distilled water to determine whether meteorite components would dissolve in it. Pure water is water with a high degree of purity from which all impurities have been removed. Water that is infinitely more pure than pure water is called ultrapure water. There are no quantitative values ​​or rules for the distinction between pure water and ultrapure water, and it varies across academic societies and industries, so there is no clear distinction, but sometimes water with a purity of 18MΩcm is called ultrapure water (water temperature of 25°C is the standard). The distilled water used had an electrical resistivity (Ω·cm) of 1.001MΩcm and an electrical conductivity (μs / cm) of 0.99μs / cm. The results are shown in Table 17. Even with distilled water, no difference was found in electrical resistivity (Ω·cm) and electrical conductivity (μs / cm) at 1.001M. In other words, it is unlikely that something has dissolved. As mentioned above by Masato Yasui et al., K. Liu et al., and Richard J. et al., it is possible that something has affected the properties of water itself to create structured water, but we cannot explain it.

[0063] [Table 17]

[0064] Example 26: Measurement of the oxidation-reduction potential of water Next, a test was performed to examine the change in the oxidation-reduction potential. The measurement device used was a digital oxidation-reduction potential meter (ORP) YK-23RP MotherTool manufactured by MotherTool Co., Ltd. The measurement results for each water are shown in Table 18 (water temperature was 25°C). It was found that the well water had a lower redox potential.

[0065] [Table 18]

[0066] <Example 27> Measurement of oxidation-reduction potential when meteorites etc. are used Each meteorite was weighed using a Shimadzu Corporation high-precision analytical electronic balance BM (0.01 mg weighing capacity). 500 mL was taken out using a 500 mL measuring cylinder. Yokkaichi tap water (7-6 Tomari-cho, Yokkaichi, Mie Prefecture, collected on January 17, 2012), (A) Yokkaichi tap water + stony meteorite, (B) Yokkaichi tap water + iron meteorite, (C) Yokkaichi tap water + stony-iron meteorite, (D-1) Yokkaichi tap water + tektite, (D-2) Yokkaichi tap water + moldavite, (D-3) Yokkaichi tap water + Libyan glass, 100g of each was cut out with a dental diamond desk using a dental magnifying glass or scraped with a dental diamond bur to match the weight. Yokkaichi tap water, Mie Prefecture, was dispensed into a 1000mL beaker and stirred slowly (using a magnetic stirrer REXIM, rotation speed 500 rpm) to avoid creating air bubbles. The meteorite was immersed in it for 100 seconds and then removed. The removal was done with tweezers. The same experiment was performed five times and the average values ​​were calculated, and the results are shown in Table 19. The change in the reduction potential of the tap water in Yokkaichi City after soaking the various meteorites was within the margin of error, and the oxidation-reduction potential was almost the same as that of the original tap water. In other words, it was not thought that the reduction potential was related to the change. Figure 21 shows some of the shapes of the stones used in the experiment, and Figure 22 shows meteorites (A) crushed to a diameter of 300 μm and meteorites (B) crushed to diameters of 22 μm to 40 μm. The meteorites used in this experiment were created in a variety of shapes, including pyramid-shaped, spherical, hexagonal prism, magatama-shaped, cubic, egg-shaped, ring-shaped, disc-shaped, triangular, egg-shaped, and diamond-cut shapes. The difference between the above shapes seems to be that effectiveness increases in the order of hexagonal prism, sphere, pyramid, and natural, but since the natural shape is effective enough, we felt that there was no need to specify the shape.

[0067] [Table 19]

[0068] Example 28: Trunk Gravity Axis Test The subjects were divided into 10 groups by weight, regardless of gender: Group 1: body weight 60.0kg-62.5kg, Group 2: body weight 62.5kg-65.0kg, Group 3: body weight 65.0kg-67.5kg, Group 4: body weight 67.5kg-70.0kg, Group 5: body weight 70.0kg-72.5kg, Group 6: body weight 72.5kg-75.0kg, Group 7: body weight 75.0kg-77.5kg, Group 8: body weight 77.5kg-80.0kg, Group 9: body weight 80.0kg-82.5kg, Group 10: body weight 82.5kg-85.0kg. A total of 70 subjects, 7 people in each group, were tested for their trunk gravitational axis in addition to weight. Individuals who were extremely weak or extremely strong were excluded, and the results are presented for a total of 50 subjects, 5 people in each group. In the following examples, data was obtained from 50 subjects in this group for the trunk gravitational axis test by weight. Each person also took three control tests and three tests after eating and drinking the test sample, and the average values ​​were calculated. The method was to dispense various types of water into 100mL beakers. The water was stirred at 500 rpm using a magnetic stirrer REXIM. ​​Minerals were then added and filtered using three coffee filters. The time from addition to filtration was divided into 100 seconds to obtain the filtered water. The same procedure was repeated regardless of whether minerals were present or not to obtain a control. For the experiment, data was used from a trunk gravitational axis test conducted immediately after each subject drank 5 mL of filtered water (the large intestine has a strong water absorption capacity that can even absorb bound water. However, most of the water is absorbed in the small intestine, and it takes about 30 minutes, so it was thought that there would not be time for absorption). The subjects were not informed of anything and underwent a trunk gravitational axis test once a day as a control and once after eating or drinking the sample. The trunk gravitational axis test was conducted three times for each type of water, and the average value of the five subjects was calculated. Furthermore, a control was taken each day, and the difference from the control was recorded in 100g units based on this. This was judged by taking a photograph and enlarging it. The series of operations (dispensing, stirring, filtration) was carried out under the same conditions as when the minerals were added. In addition, the scale is in 1kg increments, so the center of the scale is set to 0.5kg. To ensure the highest possible accuracy, I took a photo, enlarged it, and read the values.

[0069] <Example 29> Creation and use of a trunk gravity axis test device In the trunk gravitational axis test, it is difficult for the individual to recognize whether their strength has increased or not between 0.0kg and 1.5kg. Therefore, in order to increase objectivity, the following device was devised. Figure 23 shows the device used for the trunk gravitational axis test, and Figure 24 shows the procedure for conducting the test. The trunk gravitational axis test device 1 (hereinafter simply referred to as "device 1") is an improved version of a 100 kg grip strength meter. This device 1 is capable of measuring the pressure applied between the left and right hands on the back of the subject. The device 1 is equipped with a first pressing operation unit 2 that can be pressed with either the left or right palm of the subject, a second pressing operation unit 3 that can be pressed with the other palm and in a direction opposite to the pressure of the first pressing operation unit 2, and a measurement unit 4 that can measure the force applied to both pressing operation units 2, 3. The device 1 can be operated by one person, or by two people as described below. For more accurate measurements, it is preferable to operate it with two people. First, the handle is enlarged so that it can be pushed straight down, and the grip that would get caught when holding it down is cut off. Also, to prevent it from slipping when holding it straight down, a handle is attached so that it can be held at two points. For subjects who require strength, weights such as 5kg or 10kg are added to this handle in advance to minimize the force required by the surgeon. This is because if the surgeon requires strength, the results will vary and lack accuracy. In this way, the quality is visualized in kg. The results are photographed and enlarged, and the kg and kg↑ are recorded. With the photo judgment, it is possible to judge up to kg, kg↑, and kg↓, but anything below 0.5 is within the margin of error, so it is standardized to kg and kg↑. During this time, both the surgeon and the subject practiced how to relax. Because everyone will try to resist by using force at first, this is not a show-off of strength, but rather an observation of how it affects the trunk's gravitational axis, so it is necessary to relax while doing this. The conditions were: drinking water temperature 25°C, humidity 65%, brightness Mitsubishi Electric OSRAM NHT270·L, 100V, wind force 0m, regardless of the season. Yokkaichi tap water was used as the control, with 0.0 kg. As a simple method, you can use the surgeon's fist instead of the test machine to determine the difference in the amount of force applied, but if the force is less than 1.5kg, you will not feel much of a difference. It seems that in most cases, at least 1.5kg or more is necessary. After that, the trunk gravity axis test was carried out one by one. The memory was judged by taking a photograph and judging the weight in kg, as shown in Figure 25. It was a little tricky within 1 kg, but it was clearly different from 1.5 kg or more.

[0070] As shown in Figure 24, (1) the subject looked straight ahead, stood with his toes and heels together, and clasped his hands behind his back, (2) stood with his toes and heels together, and (3) clasped his hands behind his back so that they would not come apart even if someone applied force to them. (4) The first pressing operation part 2 of the device 1 was placed on the palm of the clasped hand behind his back, and the surgeon applied force to the second pressing operation part 3 directly below. Since this was not a test of strength, the device 1 was placed directly below the subject (so as not to cause any positional shifts forward, backward, left, or right) so as not to injure his shoulders. The applied force was gradually increased, and the weight at which the subject collapsed was photographed. As a warning to the subjects, they were instructed not to force themselves, to stand in a natural posture without straining, to clasp their hands behind their backs, and to practice relaxing several times before carrying out the test. In addition, in all trunk gravity axis tests, subjects who complained of pain such as lower back pain, shoulder pain, or tendonitis were excluded from the test. The photograph of the subject when he collapsed was enlarged and the weight scale was read. Figure 25 shows a photographic diagram explaining how to read the scale. Next, the subjects drank the test sample (water) and immediately repeated the same procedure. The water that the subjects drank had been passed through two filters: a syringe filter DISMIC AS type and a sterilizing Millex filter unit 33 mm. Table 20 shows the criteria for evaluating the difference in weight tolerance before and after drinking the test substance (weight tolerance before drinking - weight tolerance after drinking) (g). In the example, 0.0 means the same as the control. "↑" means exactly to +500g, that is, "0.0↑" means 0g to 500g, and "1.0↑" means 1000g to 1500g or less.

[0071] [Table 20]

[0072] <Example 30> Tap water, various well water and trunk gravity axis test (1) The sample used was tap water collected from 7-6 Tomari-cho, Yokkaichi, Mie Prefecture on January 17, 2002. The results are shown in Table 21.

[0073] [Table 21]

[0074] <Example 31> Tap water, various well water and trunk gravity axis test (2) The sample used was tap water collected on August 28, 2001 from a water supply adjacent to the well in Kobo Daishi, Nishikanyoshi-cho, Kakogawa City. The results are shown in Table 22.

[0075] [Table 22]

[0076] <Example 32> Tap water, various well water and trunk gravity axis test (3) The sample used was tap water collected from 148 Inuishinmachi, Tanba Sasayama City on August 28, 2001. The results are shown in Table 23.

[0077] [Table 23]

[0078] <Example 33> Tap water, various well water and trunk gravity axis test (4) The specimen used was well water collected on August 28, 2001 at Oiwake Torii, 3-1-3013-1, Oiwake, Yokkaichi City, Mie Prefecture. The results are shown in Table 24.

[0079] [Table 24]

[0080] <Example 34> Tap water, various well water and trunk gravity axis test (5) The sample used was well water collected from the Kobo Daishi well in Nishikanyoshi-cho, Kakogawa City on August 28, 2001. The results are shown in Table 25.

[0081] [Table 25]

[0082] <Example 35> Tap water, various well water and trunk gravity axis test (6) The specimen used was well water collected at 148 Inuishinmachi, Tanba Sasayama City on August 28, 2001. The results are shown in Table 26. Strangely, there was a difference of more than 3.5 kg between the tap water in Yokkaichi and the well water in Tanba. There is no explanation for this, but it is a fact. Moreover, strangely enough, the negative effects of water were greater in those with lighter body weights, while the positive effects were greater in those with heavier body weights.

[0083] [Table 26]

[0084] <Example 36> Various tap water and well water and trunk gravity axis test (7) The trunk gravity axis test was conducted using water collected on January 17, 2021 as a specimen. The collection location was the same as in Examples 29 to 34 above. Compared to the experiment conducted in 1993, similar results were obtained, although the subjects were different. The water collection location and test method were the same as above. The results are shown in Table 27. There was no significant difference in the results of the trunk gravity axis test conducted in 1993 and 2021 using well water from Tanba and Kakogawa. We thought that the water veins in Kakogawa and Tanba may have changed due to the Great Hanshin-Awaji Earthquake that occurred on January 17, 1995, but there was no significant difference in the results. Overall, since 28 years have passed, we had imagined that the water pollution would have produced more serious results in the trunk gravity axis test, but the changes between 1993 and 2021 were only within the margin of error. In other words, it was thought that one of the reasons why there are so many people over 100 years old is that many people drink well water as mineral water.

[0085] [Table 27]

[0086] <Example 37> The meteorites were examined for their composition, and analysis revealed that apart from oxidation due to high temperatures in the atmosphere, there were no notable differences between the meteorites and materials on Earth. There may be very small differences, but no major differences from materials on Earth. Therefore, we conducted a trunk gravity axis test using water obtained by putting all the same things into a container and running water through it, but strangely, no results like those obtained with meteorites were obtained for any of the six types. We will discuss this below. The following shows the results of the component analysis table and the trunk gravity axis test for various meteorites. The samples were originally submitted for testing on August 28, 1993, but due to data loss, new data was taken on November 25, 2022. The samples tested were the same lot number as the ones submitted for testing on August 28, 1993. The results of the component analysis of stony meteorites are shown in Figure 26. (A) Breakdown of stony meteorites: 1. Achondrite meteorite, 2. LL3 chondrite meteorite, 3. H3-5 chondrite meteorite, 4. CV3 chondrite meteorite, 5. R chondrite meteorite, 6. Carbonaceous chondrite meteorite, 7. MC chondrite meteorite, 8. Bekaa 001, 9. NWA532 meteorite, 10. Allende meteorite, 11. Murchison meteorite, 12. Bashkounou meteorite, 13. Chelyabinsk meteorite, 14. Tarda meteorite, 15. Orgeir meteorite stone, 16. Gao meteorite, 17. Zag meteorite, 18. Ben Soul meteorite, 19. Vega meteorite, 20. Tamduct meteorite, 21. Porter-Lesparay meteorite, 22. Vega 001, 23. Cherga meteorite, 24. Rumuruti chondrite meteorite, 25. Enstatite chondrite meteorite, 26. Al-Hagounia meteorite, 27. NWA1180 meteorite, 28. NWA1232 meteorite, 29. NWA11900 meteorite, 30. NWA11304 meteorite, 31. Oum Dreyga meteorite, 32. Maricopa meteorite, 33. Mount Yirtkuq Bulak 006 meteorite, 34. NWA869 meteorite, 35. North West Africa 869 meteorite, 36. Acapulcoite-lodranites meteorite, 37. Ureilite, 38. 2008TC3 meteorite, 39. Almahata 50 types of meteorites were ground into powder: 40. Sitta meteorite, 41. Angrite meteorite, 42. Howardite meteorite, 43. Diogenite meteorite, 44. Milbililii meteorite, 45. Eucrite meteorite, 46. Meteorlong meteorite, 47. NWA7831 meteorite, 48. Shergottite meteorite, 49. Chasinite meteorite, and 50. NWA1180 meteorite. The meteorites were ground into powder in equal amounts using a Chuo Kakoki Co., Ltd. FV-250 grinder to an average particle size of 20 μm to 40 μm, and then mixed well for component analysis. Since one meteorite may stand out, the stony meteorites were calculated as the average of the 50 types above. All stony meteorites that will be introduced later will use the same 50 types.

[0087] <Example 38> The trunk gravitational axis test was conducted after August 28, 2011. The following components were collected, almost identical to those of a stony meteorite: silicon oxide (39.0128g), magnesium oxide (24.7793g), iron oxide (22.8868g), sulfur oxide (3.82277g), aluminum oxide (3.7147g), calcium oxide (2.1645g), sodium oxide (1.4244g), chromium oxide (0.5858g), nickel oxide (0.4593g), manganese oxide (0.3 A total of 100g of the following substances were placed in running water and then the trunk gravity axis test was performed using the water. The method was as described above. The measuring device used was a Shimadzu Corporation high-precision analytical electronic balance BM capable of measuring 0.01mg. The amounts above are slightly different from those obtained by quantitative analysis, but the difference is not significant, so the above values ​​were used. The results are shown in Table 28. As shown above, the trunk gravity axis test was almost the same. In other words, even though the composition is almost the same as that of a stony meteorite, the difference with a stony meteorite was obvious at less than 1.0 kg, and the same effect was not observed. This is the mystery of the universe.

[0088] [Table 28]

[0089] <Example 39> (B) The compositional analysis of iron meteorites is shown in Figure 27. (B) The breakdown of iron meteorites is as follows: 1. Nantan meteorite, 2. Gibeon meteorite, 3. Campo del Cielo meteorite, 4. Ulak meteorite, 5. Canyon Diablo meteorite, 6. Gebel Kamil meteorite, 7. Mundra Bira meteorite, 8. Agdal meteorite, 9. Altai meteorite, 10. Doronino meteorite, 11. Sikhote-Alin meteorite, 12. Swedish Muonionalusta meteorite, 13. Tsingur meteorite, 14. Santo The 24 meteorites used were the 1. Aban meteorite, 2. Xinjiang meteorite, 3. Madagascar meteorite, 4. Taza (NWA859) meteorite, 5. Toluca meteorite, 6. Mandrabira meteorite, 7. Odessa meteorite, 8. Turgut meteorite, 9. Ataxite meteorite, 10. Imilchil meteorite, and 11. Doronimo meteorite. They were crushed to 20-40μm, and equal amounts of these were mixed well and analyzed for composition. Since one meteorite may have something that stands out, the average of the 24 types was taken for the stony meteorites. All iron meteorites that came out from then on were crushed to the same 24 types. The crusher used was a Chuo Kakoki Co., Ltd. FV-250 model, and meteorites were crushed to an average particle size of 20μm to 40μm. Equal amounts of the meteorites were mixed well and analyzed for their composition. Since one meteorite may stand out in particular, the average of the 24 types above was taken for iron meteorites. From then on, all stony meteorites that were found were the same 24 types. Iron meteorites were sticky when crushed, and took the longest time to crush.

[0090] <Example 40> The following components, almost the same as those of the iron meteorite, were collected, and the trunk gravity axis test was conducted through water containing iron oxide (88.7363g), nickel oxide (7.5788g), phosphorus oxide (2.2354g), cobalt oxide (0.5044g), sodium oxide (0.4105g), chromium oxide (0.2068g), magnesium oxide (0.1312g), sulfur oxide (0.0911g), silicon oxide (0.0586g), manganese oxide (0.0296g), and chlorine (0.0174g). The method was as described above. The measuring device used was a Shimadzu Corporation high-precision analytical electronic balance BM, capable of measuring 0.01mg. The amounts above are slightly different from those obtained by quantitative analysis, but the difference is not significant, so the above values ​​were used. The results are shown in Table 29. As mentioned above, the trunk gravity axis test was almost the same. In other words, even though the composition is almost the same as that of iron meteorites, the difference with stony meteorites was obvious at less than 1.0 kg, and the same effect was not observed. This is the mystery of the universe.

[0091] [Table 29]

[0092] <Example 41> The results of the compositional analysis of stony-iron meteorites are shown in Figure 28. (C) Stony-iron meteorites: 1. Brahin meteorite, 2. Imilak meteorite, 3. Esquel meteorite, 4. NWA4747 meteorite, 5. Serico meteorite, 6. Seymchan meteorite, 7. Sublimated iron meteorite, 8. Hakkitta meteorite, 9. Mesosiderite meteorite, 10. Blenheim meteorite, 11. Kuising meteorite, 12. Zinder meteorite, 13. Springwater meteorite, 14. Mount Yirtkuq Bulak Twenty types of meteorites were used: 006 meteorite, 15. Vaca Muerta meteorite, 16. Krasnoyarsk meteorite, 17. Fukang meteorite, 18. NWA4747 meteorite, 19. Fukan meteorite, and 20. Esquel meteorite. They were crushed to 20-40 μm, and equal amounts of these were mixed well and analyzed for their components. Since one meteorite may stand out in some way, the average of 20 types of stony-iron meteorites was calculated. All iron meteorites that will be presented from now on will use the same 20 types. All the same 20 types of stony-iron meteorites were ground into powder. The meteorites were ground into an average particle size of 20μm to 40μm using a Chuo Kakoki Co., Ltd. FV-250 grinder, and equal amounts of the meteorites were mixed well and analyzed for their components.

[0093] <Example 42> Stony-iron meteorite The following components, almost identical to those of the stony-iron meteorite, were collected, and the trunk gravity axis test was conducted through water containing iron oxide (94.7157g), silicon oxide (2.3166g), aluminum oxide (1.9675g), manganese oxide (0.3191g), magnesium oxide (0.1925g), calcium oxide (0.1262g), chromium oxide (0.0833g), tin oxide (0.0732g), titanium oxide (0.0583g), zinc oxide (0.0381g), nickel oxide (0.0354g), potassium oxide (0.0245g), sulfur oxide (0.0192g), chlorine (0.0147), and zirconium oxide (0.0137g). The method was the same as above. The measuring device used was a Shimadzu Corporation high-precision analytical electronic balance BM capable of measuring 0.01 mg. The amounts above are slightly different from those obtained by quantitative analysis, but the difference is not significant, so the above values ​​were used. The results are shown in Table 30. As shown above, the trunk gravity axis test was almost the same. In other words, even though the composition is almost the same as that of a stony-iron meteorite, the difference with a stony meteorite was obvious at less than 1.0 kg, and the same effect was not observed. This is the mystery of the universe.

[0094] [Table 30]

[0095] <Example 43> The results of the tektite composition analysis are shown in Figure 29. <Example 44> Tektite The following compounds, which are almost the same as those in tektites, were collected: silicon oxide (70.8096g), aluminum oxide (13.2208g), iron oxide (6.1699), potassium oxide (2.6849g), calcium oxide (2.1806g), magnesium oxide (0.1337g), sodium oxide (1.2537g), titanium oxide (0.9113g), chromium oxide (0.4996g), manganese oxide (0.1337g), sulfur oxide (0.0539g), nickel oxide (0.0425g), zirconium oxide (0.0415), strontium oxide (0.0239), rubidium oxide (0.0141), and yttrium oxide (0.0040g). The trunk gravitational axis test was conducted in water using the same method as above. The measuring device used was a Shimadzu Corporation high-precision analytical electronic balance BM capable of measuring 0.01 mg. The amounts above are slightly different from those obtained by quantitative analysis, but the difference is not significant, so the above values ​​were used. The results are shown in Table 31. As shown above, the trunk gravity axis test was almost unchanged. In other words, even though the ingredients are almost the same as tektite, the same effect as tektite was not observed at less than 0.5 kg. This is the mystery of the universe.

[0096] [Table 31]

[0097] <Example 45> The results of the component analysis of moldavite are shown in Figure 30. <Example 46> Moldavite The following components, almost the same as Moldavite, were collected: silicon oxide (74.5027g), aluminum oxide (11.0192g), potassium oxide (4.9036g), calcium oxide (3.5360g), iron oxide (2.9962), magnesium oxide (2.1168g), titanium oxide (0.4394g), chromium oxide (0.1562g), barium oxide (0.1236g), manganese oxide (0.1204g), zirconium oxide (0.0176g), nickel oxide (0.0138g), and phosphorus oxide (0.0127g). The trunk gravity axis test was conducted through water. The method was the same as above. The measuring device used was Shimadzu Corporation's high-precision analytical electronic balance BM, capable of measuring 0.01mg. The amounts above are slightly different from those obtained by quantitative analysis, but the difference is not significant, so the above values ​​were used. The results are shown in Table 32. As shown above, the trunk gravity axis test showed almost no change. In other words, even though the ingredients are almost the same as Moldavite, the same effect was not observed within the margin of error of 0.5 kg or less. This is the mystery of the universe.

[0098] [Table 32]

[0099] <Example 47> The results of the component analysis of Libyan glass are shown in Figure 31. <Example 48> The following components, almost the same as those of Libyan glass, were collected: silicon oxide (97.8135), aluminum oxide (1.6069g), iron oxide (0.2332), titanium oxide (0.1441g), chromium oxide (0.1090g), calcium oxide (0.0308g), potassium oxide (0.0240g), zirconium oxide (0.0142g), nickel oxide (0.0126g), manganese oxide (0.0090g), and strontium oxide (0.0017). The trunk gravity axis test was conducted through water. The method was the same as above. The measuring device used was a Shimadzu Corporation high-precision analytical electronic balance BM, capable of measuring 0.01mg. The amounts above are slightly different from those obtained by quantitative analysis, but the difference is not significant, so the above values ​​were used. The results are shown in Table 33. As mentioned above, the trunk gravity axis test showed almost no change. In other words, even though the ingredients are almost the same as Libyan grass, the same effect was not observed at less than 0.5 kg. This is the mystery of the universe. Although there are differences in the composition of tektite, moldavite, and Libyan glass, there was almost no difference in the trunk gravity axis test. From this, it is thought that there is a high possibility that the effect is due to the formation of each rock, rather than differences in composition.

[0100] [Table 33]

[0101] <Example 49> Next, we verified whether meteorite components would dissolve in water. We conducted water quality tests on tap water collected at 7-6 Tomari-cho, Yokkaichi City, Mie Prefecture on January 17, 2011, and on water after soaking and filtering various meteorites. We used 100g of each meteorite per liter of tap water. Each meteorite was left in running water for 72 hours. For this method, seven magnetic stirrers and 2L beakers were prepared, and all operations were carried out in a drive chamber manufactured by Soda Kogyo Co., Ltd. to prevent contamination. To extract the various meteorites, (a) a dental technician's magnifying glass was used to extract the minerals with a dental diamond desk, and a dental diamond bur was used to cut them into 100g pieces. (b) The measuring device used was a Shimadzu Corporation high-precision analytical electronic balance BM capable of measuring 0.01mg. (c) The water used was from the tap water of Yokkaichi City, Mie Prefecture, after thoroughly rinsing the various meteorites, and 1,000mL of tap water was used. (d) A magnetic stirrer REXIM was used for stirring at 100 rpm for 72 hours, and 500 g of various meteorites ((A) stony meteorite, (B) iron meteorite, (C) stony-iron meteorite, (D-1) tektite, (D-2) moldavite, (D-3) Libyan glass) were soaked for 72 hours. (f) To extract the minerals, the water was filtered using three coffee filters, and the components of the water were examined. The results are shown in Table 34. No scientific changes were found in tap water that had been in contact with various meteorites ((A) stony meteorite, (B) iron meteorite, (C) stony-iron meteorite, (D-1) tektite, (D-2) moldavite, (D-3) Libyan glass) for 72 hours. In other words, no scientific changes such as the release of ions or the removal of harmful substances were found in the tests.

[0102] [Table 34]

[0103] <Example 50> A magnetic stirrer and a 2L beaker were prepared, and all operations were carried out in a drive chamber manufactured by Soda Kogyo Co., Ltd. to prevent contamination. To extract the various meteorites, (a) a dental technician's magnifying glass was used to extract the minerals with a dental diamond desk, and 500g was added by scraping with a dental diamond bur. (b) The measuring device used was a Shimadzu Corporation high-precision analytical electronic balance BM capable of measuring 0.01mg. (c) The water used was 1,000mL of tap water, which had been used to thoroughly rinse the various meteorites from the tap water in Yokkaichi City, Mie Prefecture. (d) A magnetic stirrer REXIM was used for stirring at 500 rpm for 72 hours. 500 g of various meteorites ((A) stony meteorite, (B) iron meteorite, (C) stony-iron meteorite, (D-1) tektite, (D-2) moldavite, (D-3) Libyan glass) were soaked for 72 hours. (f) Tweezers were used to remove the minerals. The meteorite was immersed in tap water and the electrical resistivity (Ω·cm) and electrical conductivity (μs / cm) were measured. The equipment used was a portable electrical conductivity meter CM-31P-W (for pure water) from Toa DKK (water temperature was 25°C). The results are shown in Table 35. Although they soaked it for 72 hours instead of the usual 100 seconds, no change was observed. In other words, it was unlikely that anything had dissolved. Substances can have both good and bad effects. A drug can be thought of as a substance that emphasizes its good points. A substance can induce or inhibit enzyme activity, and in combination with other substances, can become toxic. These phenomena are important issues in toxicology, but it has been reported that a major difference between meteorites and terrestrial rocks is the composition of the isotopes of He, Ne, Ar, Kr, and Xe. The most notable is helium, with meteorites showing a higher isotope composition than rocks on Earth. 3 He / 4 He isotope ratio is 10 -4 on the order of magnitude, whereas that of Earth's rocks is 10 -6 The amount of uranium and thorium produced by the nuclear decay of rocks on Earth is very low. 4 In meteorites, the helium is added to the rocks. 3 He / 4 There are many isotopes of He. However, it is unlikely that these will chemically affect water and thus affect the body.

[0104] [Table 35]

[0105] <Example 51> So, we performed the same experiment using distilled water. Pure water is water with a high purity from which all impurities have been removed. Water that is infinitely more pure than pure water is called ultrapure water. There is no clear distinction between pure water and ultrapure water, and there are no quantitatively determined values ​​or rules, and it varies among academic societies and industries, but in some cases (18MΩcm) is considered ultrapure water (in this case, the water temperature is 25℃). The distilled water used had an electrical resistivity (Ω·cm) of 1.001 MΩcm and an electrical conductivity (μs / cm) of 0.99 μs / cm. The results are shown in Table 36. Even with distilled water, no difference was found in the electrical resistivity (Ω·cm) and electrical conductivity (μs / cm) at 1.001 M. In other words, it was not thought that this was due to something having dissolved. As Masato Yasui et al., K. Liu et al., and Richard J. et al. say above, it is possible that something has affected the properties of the water itself to create structured water, but I could not explain it.

[0106] [Table 36]

[0107] <Example 52> Next, the change in the oxidation-reduction potential was measured. The equipment used was a digital oxidation-reduction potential meter (ORP) YK-23RP (MotherTool) manufactured by MotherTool Co., Ltd. (water temperature was 25°C). The measurement results for each water are shown in Table 37.

[0108] [Table 37]

[0109] <Example 53> Each meteorite was weighed using a Shimadzu Corporation high-precision analytical electronic balance BM 0.01 mg weighing capacity. 500 mL was taken out using a 500 mL measuring cylinder. Yokkaichi tap water (7-6 Tomari-cho, Yokkaichi, Mie Prefecture, collected on January 17, 2012), (A) Yokkaichi tap water + stony meteorite, (B) Yokkaichi tap water + iron meteorite, (C) Yokkaichi tap water + stony-iron meteorite, (D-1) Yokkaichi tap water + tektite, (D-2) Yokkaichi tap water + moldavite, (D-3) Yokkaichi tap water + Libyan glass, 100g of each was cut out with a dental diamond desk using a dental magnifying glass or scraped with a dental diamond bur to match the weight. Yokkaichi tap water, Mie Prefecture, was dispensed into a 1000mL beaker and stirred slowly (using a magnetic stirrer REXIM, rotation speed 500 rpm) to avoid creating air bubbles. The meteorite was immersed in it for 100 seconds and then removed. The removal was done with tweezers. The same experiment was performed five times and the average values ​​were calculated. The results are shown in Table 38. The change in the reduction potential of the tap water in Yokkaichi after soaking various meteorites was within the margin of error, and the redox potential was almost the same as the original tap water. In other words, it does not seem that the reduction potential is related. Incidentally, the photos below are examples of some of the shapes used in the experiment. The meteorites used in this experiment were created in various shapes, such as pyramid, sphere, hexagonal prism, magatama, cube, egg, ring, disk, triangle, egg, and diamond cut shapes, as they fell. The shapes are as shown in Figures 21 and 22. The difference due to the difference in shape seems to be that the effectiveness increases in the order of hexagonal prism, sphere, pyramid, and natural, but it was found that the natural shape was sufficiently effective. [Table 38]

[0110] <Example 54> Trunk gravity axis test and water temperature The specific gravity is highest when the water temperature is around 4°C, and it was found that the trunk gravitational axis test for water follows a similar arc. The results are shown in Figure 32. There is a slight margin of error in the maximum and minimum values, but these are the results of the trunk gravitational axis test. In the graph, "★" indicates the results for third-year high school boys, "× in a circle" indicates the results for first-year high school boys, "◆" indicates the results for third-year junior high school boys, "●" indicates the results for first-year junior high school boys, "▲" indicates the results for sixth-year elementary school boys, and "hexagonal star" indicates the results for first-year elementary school boys. The mineral water used was Evian. All meteorites (tektites, moldavite, Libyan glass, and the 100 types of meteorites described in <Example 16>) were crushed to 20 μm to 40 μm in 1 liter of Evian to obtain meteorite powder. From the powder, exactly 1.00 g of each was taken out to obtain 100 types of meteorite powder, totaling 100 g. The total minerals were 115 types from group (b) above. First, 1,000 mL of tap water from Yokkaichi was taken and stirred, and the total meteorites (1g of each meteorite, total of 100g) were soaked in it for 100 seconds, after which the meteorites were removed. The same water was stirred, and 115g of 115 types of minerals (1g each) were soaked in it for 100 seconds, and then removed. The water was exposed to sound waves of 23Hz, 24Hz, and 25Hz for 100 seconds each. After that, 13Hz and 24Hz were applied simultaneously, and waves were applied for 100 seconds. Similarly, 24Hz and 25Hz were applied simultaneously, and waves were applied for 100 seconds. Testing was performed with water that had been exposed to 23Hz and 25Hz simultaneously, and waves were applied for 100 seconds. Children who have just graduated from kindergarten and are in the first grade of elementary school have less strength than sixth graders. It appears that their strength has increased by about four times in six years. The figure shows the results of a trunk gravitational axis test immediately after drinking 5 mL of the water. The results of the six people mentioned above all showed that the force was almost the same at 24℃~30℃. The force suddenly weakened once the temperature exceeded 70℃. At 80℃, it had almost no effect, and was almost the same as tap water in Yokkaichi. In other words, this result suggests that the structured clusters may break down at temperatures above 70℃. From this result, it was thought that it was correct to say that meltwater contains a lot of hexameric water molecules. In particular, the values ​​were almost the same from 24℃ to 30℃. For this reason, all subsequent trunk gravitational axis tests were conducted using water whose temperature was set to 24℃~30℃. Although not shown in the figure, the results of experiments conducted on rugby players showed that the maximum weight gained by water at 4°C after stirring the total amount of meteorites, total minerals, and infrared radiation was added to the water, and then sound waves and 1 / f fluctuations were added, was an astonishing 32.5kg↑, excluding the base (Evian).

[0111] <Example 55> Example of trunk gravity axis test according to meteorite type, weight, and time Each meteorite was weighed using a Shimadzu Corporation high-precision analytical electronic balance (BM 0.01 mg weighing capacity) at the Toxicology Laboratory of the School of Pharmaceutical Sciences, Showa University. 100 mL was taken out into a 500 mL measuring cylinder. The above 100 types of meteorites, including (A) stony meteorites, (B) iron meteorites, (C) stony-iron meteorites, (D-1) tektites, (D-2) moldavite, (D-3) Libyan glass, and unclassified meteorites, were crushed to an average particle size of 20μm to 40μm using a crusher manufactured by Chuo Kakoki Co., Ltd., FV-250, to obtain meteorite powder. From these, exactly 1.00g of each was taken out to obtain 100g of meteorite powder for each of the 100 types. This was used to obtain a total of 100g of meteorite powder. For meteorites smaller than that, tap water from Yokkaichi City, Mie Prefecture was dispensed into a 1000mL beaker and stirred (magnetic stirrer REXIM, 500 rpm). After immersing the meteorite in the water, it was removed. Three coffee filters were used to remove the meteorite. The filtration time was rounded up to 100 seconds, including the time the water was in contact with the sample, even if some water remained. In the experiment, participants were asked to drink 5 mL of the water and then immediately performed the trunk gravitational axis test. The test was performed immediately after drinking the water, so there was no time for absorption from the stomach and intestines. Even though they could be removed with tweezers, three filters were used to ensure that all conditions were the same, including the 0.000001g (0.001mg) dose. In addition, immediately after drinking the beverage, the subjects performed one type of trunk gravitational axis test each day without being informed of anything. For each mineral, one subject performed the trunk gravitational axis test three times, and the average was calculated by excluding those who were extremely weak or extremely strong.

[0112] In all subsequent experiments, unless otherwise noted, (a) Shimadzu Corporation's high-precision analytical electronic balance BM 0.01 mg weighing was used to measure the minerals. (b) Using a dental magnifying glass, the minerals were cut out with a dental diamond desk or scraped with a dental diamond bur to adjust the weight of each mineral to the desired value. (c) 100 mL of tap water from Yokkaichi City, Mie Prefecture was used for the experiment. (d) Water was stirred at 500 rpm using a magnetic stirrer REXIM. ​​(e) Minerals were immersed in the stirred water. (f) Minerals were removed from the stirred water by filtering using three coffee filters and collecting them in a beaker under the filter paper. (g) The filtration time was set to two types, 100 seconds and 10 seconds in total, during which the mineral was in contact with the water even if the water remained. (h) The subjects drank 5 mL of the water that had been soaked in the minerals and filtered. (i) Immediately after drinking, the subjects performed only one trunk gravity axis test per day without being informed of anything. (j) For each mineral, one person took the trunk gravity axis test three times, and those who were extremely weak or extremely strong were excluded, after which the average value was calculated and recorded. Experiments were conducted using various meteorites ((A) stony meteorite, (B) iron meteorite, (C) stony-iron meteorite, (D-1) tektite, (D-2) moldavite, (D-3) Libyan glass in amounts of 100g, 10g, 1g, 100mg, 10mg, 1mg, 0.1mg, 0.01mg, and 0.001mg, following the procedures (A) to (J) above. In the following, meteorites of less than 100 mg were crushed into powder form. The crusher used was the FV-250 model from Chuo Kakoki Co., Ltd., which crushed meteorites to an average particle size of 20 μm to 40 μm. Smaller amounts were crushed using the NH-34S crusher (hammer type) from Sansho Industry Co., Ltd., which crushed meteorites to an average particle size of 20 μm to 40 μm. Up to 0.1 mg, direct measurements were made using a Shimadzu Corporation high-precision analytical electronic balance BM (0.01 mg measurement possible). Since amounts below that are too small to measure directly, 1 mg was mixed with 100 mL of distilled water using a magnetic stirrer REXIM at 500 rpm, 1 mL was dispensed from the mixture, and the mixture was filtered through three layers of coffee filters to obtain the crushed mineral. The mineral was then allowed to dry naturally to obtain 0.01 mg. Since measurements were impossible, these were used as theoretical values. Minerals below that were measured were calculated as shown in Table 39.

[0113] [Table 39]

[0114] For all minerals, amounts less than 0.1 mg were measured using the same method as above. The experiments from here onwards varied in the weight of the meteorite and the time the meteorite was in contact with Yokkaichi's tap water - 100 seconds and 10 seconds respectively - but the basics were all the same. Experiments were conducted with 100 mL of stirred Yokkaichi tap water and a fixed amount of water using 100 g of meteorite for 100 seconds and 10 seconds, 10 g of meteorite for 100 seconds and 10 seconds, 1 g of meteorite (1,000 mg) for 100 seconds and 10 seconds, 0.1 g of meteorite (100 mg) for 100 seconds and 10 seconds, 0.01 g of meteorite (10 mg) for 100 seconds and 10 seconds, 0.001 g of meteorite (1 mg) for 100 seconds and 10 seconds, 0.0001 g of meteorite (0.1 mg) for 100 seconds and 10 seconds, 0.00001 g of meteorite (0.01 mg) for 100 seconds and 10 seconds, and 0.000001 g of meteorite (0.001 mg) for 100 seconds and 10 seconds. The total number of meteorites used here was the same as the total number of meteorites mentioned above (100 types of meteorites). First, the results for each type of meteorite weighing 100g and exposed to Yokkaichi tap water for 100 seconds are shown in Table 40.

[0115] [Table 40]

[0116] <Example 56> The experimental procedure was the same as above, but the time for soaking the meteorite in the tap water of Yokkaichi was changed from 100 seconds to 10 seconds. The results for each type of meteorite weighing 100g for 10 seconds are shown in Table 41.

[0117] [Table 41]

[0118] <Example 57> The results for each type of meteorite weighing 10g and exposed to Yokkaichi tap water for 100 seconds are shown in Table 42.

[0119] [Table 42]

[0120] <Example 58> The experiment was carried out by changing the time for which the meteorites were immersed in the tap water of Yokkaichi from 100 seconds to 10 seconds. The results for each type of meteorite weighing 10.00g and 10 seconds are shown in Table 43. The results were almost the same even when the 100 seconds was changed to 10 seconds.

[0121] [Table 43]

[0122] <Example 59> Table 44 shows the results for each type of meteorite weighing 1g and exposed to Yokkaichi tap water for 100 seconds.

[0123] [Table 44]

[0124] <Example 60> An experiment was conducted in which the meteorite was immersed in the tap water of Yokkaichi for 10 seconds instead of 100 seconds. The results are shown in Table 45. The results were almost the same even when the 100 seconds was changed to 10 seconds.

[0125] [Table 45]

[0126] <Example 61> Table 46 shows the results for each type of meteorite weighing 0.1g (100mg) and exposed to Yokkaichi tap water for 100 seconds.

[0127] [Table 46]

[0128] <Example 62> The experiment was carried out by changing the time for soaking the meteorites in the tap water of Yokkaichi from 100 seconds to 10 seconds. The results for each type of meteorite weighing 0.100g (100mg) for 10 seconds are shown in Table 47. The results were almost the same even when the 100 seconds was changed to 10 seconds.

[0129] [Table 47]

[0130] <Example 63> The results for each type of meteorite weighing 0.01g (10mg) and exposed to Yokkaichi tap water for 100 seconds are shown in Table 48.

[0131] [Table 48]

[0132] <Example 64> The experiment was carried out by changing the time for soaking the meteorites in the tap water of Yokkaichi from 100 seconds to 10 seconds. The results for each type of meteorite weighing 0.010g (10mg) for 10 seconds are shown in Table 49. The results were almost the same even when the time was changed from 100 seconds to 10 seconds.

[0133] [Table 49]

[0134] <Example 65> The results for each type of meteorite weighing 0.001g (1mg) and exposed to Yokkaichi tap water for 100 seconds are shown in Table 50. There was almost no difference in the size of the meteorite from 100g to 0.001g (1mg), and it was found that all were effective.

[0135] [Table 50]

[0136] <Example 66> An experiment was conducted by changing the time for soaking the meteorites in Yokkaichi tap water from 100 seconds to 10 seconds. The results for each type of meteorite weighing 0.001g (1mg) for 10 seconds are shown in Table 51. The results were almost the same even when the 100 seconds was changed to 10 seconds. In other words, it was found that there was almost no difference in effectiveness depending on the size of the meteorite or the time from 100g to 0.001g (1mg).

[0137] [Table 51]

[0138] <Example 67> The results for each type of meteorite weighing 0.0001g (0.1mg) and exposed to Yokkaichi tap water for 100 seconds are shown in Table 52. It was found that the effectiveness of meteorites was halved when the meteorite weight was 0.0001g (0.1mg).

[0139] [Table 52]

[0140] <Example 68> An experiment was conducted by immersing meteorites in tap water from Yokkaichi for 10 seconds instead of 100 seconds. The results for each type of meteorite weighing 0.0001g (0.1mg) for 10 seconds are shown in Table 53. When the meteorite weighed 0.0001g (0.1mg), its effectiveness was halved, but it was found that it still had the power to eliminate the harmful effects of tap water.

[0141] [Table 53]

[0142] <Example 69> The results for each type of meteorite, weighing 0.00001g (0.01mg), exposed to Yokkaichi tap water for 100 seconds are shown in Table 54. It was found that a meteorite weighing 0.00001g (0.01mg) had enough power to cancel out the negative charge of the tap water. [Table 54]

[0143] <Example 70> An experiment was conducted by changing the time for soaking the meteorite in Yokkaichi tap water from 100 seconds to 10 seconds. The results for each type of meteorite weighing 0.00001g (0.01mg) for 10 seconds are shown in Table 55. When the meteorite weighed 0.00001g (0.01mg), it had enough power to cancel out the negative effects of the tap water. The results were almost the same when the time was changed from 100 seconds to 10 seconds.

[0144] [Table 55]

[0145] <Example 71> Table 56 shows the results for each type of meteorite weighing 0.000001g (0.001mg) and exposed to Yokkaichi tap water for 100 seconds. Even with a meteorite weight of 0.000001g (0.001mg), stony meteorites, iron meteorites, and stony-iron meteorites have enough power to offset the negative effects of tap water, but this was not seen in tektites, moredavite, or Libyan glass. It was found that the effect of a meteorite lasts for 100 seconds per 100 mL when the meteorite's weight is (0.00001 g (0.01 mg)) or more.

[0146] [Table 56]

[0147] <Example 72> The experiment was carried out by immersing the meteorites in the tap water of Yokkaichi for 10 seconds instead of 100 seconds. The results for each type of meteorite weighing 0.000001g (0.001mg) for 10 seconds are shown in Table 57. Even with a meteorite weight of 0.000001g (0.001mg), stony meteorites, iron meteorites, and stony-iron meteorites have the power to cancel out the negative effects of tap water, but this was not seen in tektites, moredavite, or Libyan glass. The results were almost the same when the time was reduced from 100 seconds to 10 seconds. It was proven that there is not much difference between 1 mg and 10 seconds and 100 g and 100 seconds. In other words, even if a meteorite that has gained 10 kg is soaked in water for an extra hour, it will not gain 15 kg. Also, even if the meteorite was ten times larger, its power would not have been ten times greater. However, it is true that if it is too small, it loses its effect.

[0148] [Table 57]

[0149] As a result, it is unclear whether the presence of a meteorite in the flowing water passage in the container causes the meteorite to vibrate the water passing through and change the properties of the water itself (cluster size), but all the subjects were amazed at how the same water could have increased in strength. It's a true fact that sounds like a lie. The Earth was created 4.56 billion years ago by the accumulation of meteorites. The stones, trees, air, water, and even our bodies, all the things around us are directly related to meteorites at the atomic and molecular level, even though their appearance and form may have changed. It is safe to say that meteorites continue to hold the history of the evolution of the solar system, the origin and evolution of humankind, and even all information from before the formation of our solar system. Therefore, in order to elucidate this mechanism, we took the matter to the Department of Histology and Anatomy at Showa University School of Medicine. One of the inventors, Yasunori Hori, was appointed visiting professor of tissue anatomy at Showa University School of Medicine on July 1, 2009. At the time, it was the most prolific research lab in Japan, with over 70 papers published per year, and was accepted by Nature and Science. The professor was Seiji Shiota, who was doing 10 years' worth of research at other schools in one year. Shiota is a world authority on peptides. The lab had 65 excellent staff members, including overdoctors, and three technicians. The lab had received about 600 million yen in grants for three consecutive years. In October 2015, 81 people, including the tissue anatomy staff, biochemistry staff, toxicology staff from the School of Pharmacy, and other interested professors, discussed the project, but they looked at the data, experienced it, and were all puzzled, and no conclusion was reached. It was thought that the meteorite's vibrations (waves in quantum mechanics) were affecting the water clusters, but it was concluded that further progress in quantum mechanics was needed to explain this phenomenon. Therefore, this patent was written with a predetermined conclusion in mind. Water is essential for living cells, and it is well known that drinking water has a significant impact on human health. For example, it has been scientifically proven that certain types of mineral water boost human immunity and natural killer cell activity, promoting anti-cancer immunity in mice. Natural mineral water contains various dissolved substances, which is probably why it is said to be good for human health. In addition, 13 types of aquaporins (AQPs) are known in humans. AQP2 and AQP3 are involved in water reabsorption and are abundant in the kidneys, while AQP7 and AQP9 are involved in glycerol metabolism and are abundant in fat cells and the liver. There are various aquaporins in the intestines that are involved in water absorption.

[0150] <Example 73> Heavy Water On the other hand, it is conceivable that water treated with special meteorites, stones, and ceramics could have a beneficial effect on human health and the growth of animals and plants, even if no minerals are leached from it. If the above phenomenon occurs, it is believed that either the water molecule itself or the cluster has changed. When water itself changes, the water molecule that makes up the water is made up of two hydrogen atoms and one oxygen atom, but in addition to the majority of hydrogen and oxygen atoms, there are small amounts of atoms of different weights mixed in. As a result, even though it is simply water, in addition to ordinary water H2O, it also contains small amounts of water that is heavier than this. A typical example of heavy water is DO, which contains hydrogen D (deuterium), which has twice the mass of ordinary hydrogen H. However, there are no reports of heavy water having any effect on humans. Mice showed no abnormalities when 15% of normal water was replaced with heavy water. However, death occurs when the concentration exceeds 30%, and in 100% heavy water, frogs' muscles do not contract and bacteria grow significantly slower. However, palladium is not a major component of meteorites, and they are not discharged while immersed in heavy water, nor are they exposed to ultrasound. In other words, it does not seem that any excess heavy water was being produced, but we still conducted tests to see whether heavy water was produced or not. The following samples were taken and the heavy water concentration at 25°C was measured at Showa University School of Medicine using the zinc decomposition method and a mass spectrometer. The results are shown in Table 58. All results were the same as the naturally occurring 0.0149% water in Yokkaichi City, with no change whatsoever. Although there was an error of ±0.0001, it was thought that heavy water was not involved.

[0151] [Table 58]

[0152] <Example 74> Changes in water due to sound frequency It was confirmed that dripping water visibly changed when sound waves of 23Hz, 24Hz, 25Hz, 10,000Hz, 20,000Hz, 28,000Hz, and 40,000Hz were applied to it. In other words, the change in the structure of water due to the frequency of sound is clear. A photograph of this is shown in Figure 33. Yokkaichi tap water that was not exposed to sound waves was used as the control. As a result of the above, waves could be created at 23Hz, 24Hz, and 25Hz, but the wavelength became longer from 10,000Hz, and at 20,000Hz the water simply broke into droplets and did not create waves. 10,000Hz was thought to be the maximum frequency that could create waves. Aquaporins are found on the plasma membrane of cells and were discovered in 1992. They exist in all living organisms, from bacteria to mammals, and play an important role in connecting water and life. The function of aquaporins is to allow water molecules to pass through biological membranes. In the Examples, we determined whether meteorites can alter the structure (clusters) of water and whether the water clusters increase the water permeability of aquaporins. First, we conducted an experiment to see whether meteorites could transform the tap water in Yokkaichi into tap water with high aquaporin permeability. Figure 34 shows a schematic diagram of an aquaporin. Aquaporins are proteins with the special property of allowing water to pass through narrow pores of about 3 angstroms, through which water molecules can pass directly, one molecule at a time. When passing through, hydrogen bonds between water molecules are broken by interactions with the surrounding amino acids, temporarily forming single water molecules, so amino acids are thought to be extremely important elements. When water passes through an aquaporin, it is broken down into individual molecules, and it is thought that about 10 million of them pass through per second. It is strange that water clusters inside and outside the cell are involved in such a situation, but it has been suggested that the speed at which water passes through the pores of an aquaporin may change depending on the structure of the water. This report suggests that the structural changes in the water solvent as it passes through the aquaporins of meteorite-treated water can be measured by measuring the permeability of the aquaporins. Factors that affect the opening of aquaporins include phosphorylation, pH, and Ca. 2+The factors that influence water permeability through aquaporins are known to be the following: pressure, osmolality, temperature, and nutrients. If these factors are completely excluded, the differences in water permeability through aquaporins would depend on the properties of the water molecule itself. It was confirmed that the change in water permeability due to meteorites also occurred when distilled water was used, and the water permeability of the distilled water was almost the same as that of the tap water from which the distilled water was derived.

[0153] Water molecules are adsorbed and aggregated on the surfaces and interfaces of a wide variety of materials on Earth, exerting a significant influence on physical properties such as electrical and thermal conductivity, chemical properties such as corrosivity and catalytic activity, mechanical properties such as friction, and even vital functions. The properties and functions of such surface and interfacial water molecular aggregation systems are largely governed not only by the translational structure (oxygen arrangement) of water molecules in the hydrogen bond network, but also by their anisotropic up / down orientation structure (hydrogen arrangement). In particular, since water molecules are polar molecules, their orientation structure influences the potential distribution at the surface and interface. In addition, when a hydrogen bond is formed, the hydrogen of a water molecule is donated to another water molecule, and the oxygen of a water molecule has the property of accepting hydrogen from another water molecule. Therefore, it is believed that the orientation structure of water molecules determines the acid-base properties at the surface interface and the direction of proton transfer. Thus, the orientation of water molecules provides essential structural information that is related to the properties and functions of hydrogen bond networks at surfaces and interfaces. Water molecules on solid surfaces have been actively studied using various surface science experimental techniques such as electron beam, X-ray, and scanning probe microscopes. These studies have revealed that water molecules on the surfaces of metals and oxides sometimes form peculiar hydrogen bonds with ring structures consisting of 4·5·7·8 molecules and complex long-range structures, unlike the hydrogen bond network with six-membered ring structures found in the bulk of crystalline ice. We then conducted experiments on aquaporins using metals and oxides.

[0154] <Example 75> Measurement of water permeability of aquaporin 1. Materials and methods The study was conducted using tap water from Yokkaichi City. 1g of meteorite was placed in 500mL of tap water or distilled water and treated at room temperature for 3 hours. When treating the water sample in a microwave oven, a Panasonic microwave oven NE-1802 1100 was used, and it was treated at 700W for 5 minutes. Distilled water 32-160L (manufactured by Coolfurniture) was used to prepare the distilled water. In addition, the ultrasonic device (Branson 2510) was used for treatment at normal power with an oscillation frequency (40 kHz) at room temperature for 3 minutes. The meteorites used were all meteorites, and to ensure accuracy, all were weighed in the Toxicology Laboratory of the School of Pharmaceutical Sciences, Showa University, using a Shimadzu Corporation high-precision analytical electronic balance BM (capable of weighing 0.01 mg).

[0155] 2. Measurement of water permeability of aquaporins using Xenopus oocytes Figure 35 shows an experiment using Xenopus laevis. Xenopus laevis oocytes were used to measure the water permeability of aquaporins. RNA made from the aquaporin gene was injected into the oocytes. This resulted in the synthesis of aquaporins within the cells and their placement in the egg membrane. Oocytes expressing aquaporins were placed in various types of water. Specifically, egg masses (stage V-VI oocytes (1-1.2 mm)) were extracted from Xenopus laevis and treated with 1 mg / mL collagenase (Sigma type II, solution: 100 mM NaCl, 2 mM KCl, 1 mM MgCl2, and 5 mM Hepes-Tris pH 7.5) at 20°C for 2 hours to obtain oocytes. The oocytes from which the outer membrane had been removed were washed with modified Barth's medium (MBS, 88 mM NaCl, 1 mM KCl, 2.4 mM NaHCO3, 0.4 mM Ca(NO3)2, 0.4 mM CaCl2, 0.8 mM MgSO4, 100 μg / mL Na-penicillin, and 100 μg / mL streptomycin, 15 mM Tris-HCl pH 7.4). cRNA was injected at 50 ng / 50 nl using a nano-injection device (Narishige). The injected oocytes were cultured in MBS (200 mOsmin) for 2 days. To measure water permeability, injected and cultured oocytes were placed in test water (0 mOsmout), and oocyte swelling was measured using a digital camera (Shimadzu), and the swelling rate was calculated using Mortic Image Plus 21S (Shimadzu). Water permeability (Pf) is a function of the expansion rate (V / V0 (d(V / Vo) / dt), the initial magnitude (V0=9 × 10 -4 cm 3 ), the surface area of ​​the initial oocyte (S = 0.045 cm 2 ), and the molecular weight of water 4 (Vw = 18 cm 3 / mol) using the following formula (1). Pf=V0[d(V / V0) / dt] / [S × Vw(Osmin - Osmout)] (Equation 1) Xenopus frogs can be injected with hormones to produce eggs almost all year round. Adults live in water and feed by smell, so artificial feed can be used (raised on trout food). As long as the water quality is maintained, they are easy to raise.

[0156] The range of frequencies that can be heard by the normal ear is 20Hz to 20,000Hz, with frequencies as low as 1Hz to 1,200Hz being called low frequencies and frequencies above 10,000Hz being called high frequencies. The 18 types of experimental system shown in Table 59 were used.

[0157] [Table 59]

[0158] The expansion of the eggs was measured and the water permeability was calculated. The glycerol permeability was measured by placing the oocytes expressing aquaporin in a glycerol solution and measuring the amount of glycerol taken up by the oocytes after a certain period of time. Since there is a large individual difference in Xenopus oocytes, an experiment was performed using at least 10 oocytes in one experiment, and the average was calculated. The results are shown in Table 60 together with the results of Example 76. In the sound experiment, the aquaporin permeability of water showed good absorption when sound waves of 8.23Hz, 9.24Hz, and 10.25Hz were applied to the water, but absorption was poor when high sound waves were applied to the water. The absorption rate also decreased when water was microwaved. It was thought that the absorption rate would increase because the water molecules are broken down when microwaved, but the opposite was true. It seemed difficult to explain this phenomenon. The results are shown in bar graphs in Figures 36 and 37. From these, it was found that sound waves and 1 / f fluctuations are effective. In addition, it was found that a remarkable effect was observed by passing water near the mineral of this embodiment without contacting it (14, 15, 16). Aquaporin 3 (AQP3) is abundant in the skin and plays an important role in supplying water and glycerol to the skin. Thirteen types of aquaporins have been found in humans. Among them, AQP3 is a unique aquaporin that is permeable not only to water but also to glycerol, and is also called aquaglyceroporin.

[0159] In humans, in addition to AQP3, there are two other aquaporins called aquaglyceroporins, which are abundant in fat cells and the liver and are deeply involved in glycerol metabolism. Aquaglyceroporins are aquaporins commonly found in primitive microorganisms. Aquaporins are relatively small membrane proteins of around 30 kD, with an hourglass-shaped hole in the center. The narrowest part of the hourglass-shaped hole is only about 3 angstroms in size, allowing just one water molecule of 2.8 angstroms to pass through. Therefore, it is thought that aquaporins with high water permeability have a structure that allows water to pass through this narrow space more quickly. Because glycerol is larger than a water molecule, the hole in AQP3 is larger than other aquaporins. However, water passes through AQP3 one molecule at a time, just like other aquaporins, and it has been found that where water passes depends not only on the size of the hole but also on the electrical properties of the amino acids near the hole.

[0160] Example 76: Measurement of glycerol permeability Aquaporin 3 (AQP3) cRNA, which is also permeable to glycerol, was injected into Xenopus oocytes. Glycerol and ×10 Birth Medium salt solution were added to meteorite water (distilled water) or control distilled water as test water to create a final concentration of 200 mM glycerol and ×1 Birth Medium. A 24-well plastic culture plate was used to measure glycerol permeability. Oocytes were transferred into the wells of the plate, and 1 ml of glycerol-containing Birth Medium was added and allowed to stand at 20°C for 30 minutes. After washing three times with Birth Medium, the oocytes were transferred to a minitube, and 50 μL of Assay Buffer from the glycerol measurement kit (BioVision Free Glycerol Assay kit) was added. The oocytes were then burst and dissolved with a pipette, and centrifuged at 14,000 rpm for 5 minutes. After centrifugation, 5 μL of the enzyme mixture from the kit was added to 5 μL of the supernatant, and after 30 minutes of reaction, the absorbance was measured at OD562nm. The glycerol concentration was calculated based on the absorbance of the standards. The results are shown in Table 60. In this example, it was suggested that distilled water and tap water treated with meteorites are waters that easily pass through aquaporins, and furthermore, that they promote glycerol permeability. In addition, ceramics (including pottery clay) with infrared emissivity of 90% or more at wavelengths of 2 μm to 14 μm were also somewhat effective. Although we would like to conduct experiments with each meteorite, we have now completed the aquaporin experiments using Xenopus frog eggs. As mentioned above, high frequency (ultrasound) waves were not well absorbed in the experiment using Xenopus eggs. Therefore, it was found that the effective frequency of sound waves is 20Hz to 10,000Hz.

[0161] [Table 60]

[0162] <Example 77> Example of trunk gravity axis test by meteorite type, weight, second, and total meteorite The experiment was carried out according to the method described in Example 55. (A) Stony meteorite, (B) Iron meteorite, (C) Stony-iron meteorite, (D-1) Tektite, (D-2) Moldavite, and (D-3) Libyan glass were each weighed at 100g, 10g, 1g, 100mg, 10mg, 1mg, 0.1mg, 0.01mg, and 0.001mg, and the experiment was carried out according to the procedures (a) to (j) of Example 55 above. From then on, meteorites of 100 mg or less were crushed into powder and used. The conclusion was that there was no significant difference between the meteorites tested. The meteorites were crushed to an average particle size of 20μm to 40μm using a crusher FV-250 manufactured by Chuo Kakoki Co., Ltd. For small amounts, meteorites were crushed to an average particle size of 20μm to 40μm using a crusher (hammer type) NH-34S manufactured by Sansho Industry Co., Ltd. Up to 0.1 mg, direct measurements were made using a Shimadzu Corporation high-precision analytical electronic balance BM 0.01 mg weighable. Since amounts below that are too small to measure directly, 1 mg was mixed with 500 mL of distilled water using a magnetic stirrer REXIM at 500 rpm, 1 mL was dispensed from the mixture, and the mixture was filtered through three layers of coffee filters to obtain the crushed mineral. The mixture was then air-dried to obtain 0.01 mg, but this is a theoretical value and cannot be measured. Minerals below that amount were measured using the method shown in Table 39. The total meteorites used here were the 100 types of meteorites described in <Example 16>. Specifically, 1g of each of the 100 types of meteorites was taken out and mixed well each time to obtain 100g. In the case of 10g, 100g of well-mixed meteorite powder was mixed and 10g was taken out. In the case of 1g, 1g was taken out in the same manner. The trunk gravitational axis test was carried out in accordance with <Example 28>. The same applies below. The results of the 100-second trunk gravity axis test using various types of meteorites weighing 100 g are shown in Table 61.

[0163] [Table 61]

[0164] <Example 78> The results of the 10-second trunk gravity axis test using various types of meteorites weighing 100 g are shown in Table 62.

[0165] [Table 62]

[0166] <Example 79> The results of the 100-second trunk gravity axis test using various types of meteorites weighing 10 g are shown in Table 63.

[0167] [Table 63]

[0168] <Example 80> The experiment was carried out by changing the time the meteorite was immersed in water from 100 seconds to 10 seconds. The results of the trunk gravity axis test for each type of meteorite weighing 10.00g and for 10 seconds are shown in Table 64. The results were almost the same even when the time was changed from 100 seconds to 10 seconds.

[0169] [Table 64]

[0170] <Example 81> The results of the 100-second trunk gravity axis test using various types of meteorites weighing 1g are shown in Table 65.

[0171] [Table 65]

[0172] <Example 82> The experiment involved immersing the meteorite in water for 10 seconds instead of 100 seconds. The results of the 10-second trunk gravity axis test using each type of meteorite with a weight of 1.00 g are shown in Table 66. The results were almost the same when the test time was reduced from 100 seconds to 10 seconds.

[0173] [Table 66]

[0174] <Example 83> The results of the 100-second trunk gravity axis test using each type of meteorite weighing 0.1 g (100 mg) are shown in Table 67.

[0175] [Table 67]

[0176] <Example 84> The experiment involved immersing the meteorite in water for 10 seconds instead of 100 seconds. The results of the 10-second trunk gravity axis test using each type of meteorite weighing 0.100 g (100 mg) are shown in Table 68. The results were almost the same when the test time was changed from 100 seconds to 10 seconds.

[0177] [Table 68]

[0178] <Example 85> The results of the 100-second trunk gravity axis test using each type of meteorite weighing 0.01 g (10 mg) are shown in Table 69.

[0179] [Table 69]

[0180] <Example 86> The experiment involved immersing the meteorite in water for 10 seconds instead of 100 seconds. The results of the 10-second trunk gravity axis test using each type of meteorite weighing 0.010 g (10 mg) are shown in Table 70. The results were almost the same when the test time was reduced from 100 seconds to 10 seconds.

[0181] [Table 70]

[0182] <Example 87> The results of the 100-second trunk gravity axis test using meteorites of various weights of 0.001g (1mg) are shown in Table 71. The larger the meteorite, the better, from 100g to 0.001g (1mg), but it was found that there was almost no difference in size and they all had roughly the same effectiveness.

[0183] [Table 71]

[0184] <Example 88> The experiment involved immersing the meteorite in water for 10 seconds instead of 100 seconds. The results of the 10-second trunk gravity axis test using each type of meteorite weighing 0.001 g (1 mg) are shown in Table 72. The difference in the size of the meteorite was not that great, from 100g to 0.001g. Also, the results were almost the same when the time was reduced from 100 seconds to 10 seconds.

[0185] [Table 72]

[0186] <Example 89> The results of the 100-second trunk gravity axis test using various meteorites weighing 0.0001g (0.1mg) are shown in Table 73. The effectiveness of meteorites was reduced by half from 0.0001g (0.1mg) onwards.

[0187] [Table 73]

[0188] <Example 90> The experiment involved immersing the meteorite in water for 10 seconds instead of 100 seconds. The results of 10-second trunk gravity axis tests using various types of meteorites weighing 0.0001g (0.1mg) are shown in Table 74. The meteorites' effectiveness was halved from 0.0001g (0.1mg) weight, but they were found to have the power to completely eliminate the harmful effects of tap water.

[0189] [Table 74]

[0190] <Example 91> The results of the 100-second trunk gravity axis test using various types of meteorites weighing 0.00001g (0.01mg) are shown in Table 75. It was found that a meteorite weighing 0.00001g (0.01mg) had enough power to cancel out the negative effects of waterworks.

[0191] [Table 75]

[0192] <Example 92> The experiment involved immersing the meteorite in water for 10 seconds instead of 100 seconds. The results of the 10-second trunk gravity axis test using each type of meteorite weighing 0.00001 g (0.01 mg) are shown in Table 76. It was found that a meteorite weighing 0.00001g (0.01mg) had enough power to cancel out the negative effects of the water. The results were almost the same even when the time was reduced from 100 seconds to 10 seconds.

[0193] [Table 76]

[0194] <Example 93> The results of the 100-second trunk gravity axis test using various meteorites weighing 0.000001 g (0.001 mg) are shown in Table 77. Even with a meteorite weight of 0.000001g (0.001mg), stony meteorites, iron meteorites, and stony-iron meteorites have the power to cancel out the negative effects of tap water, but this was not seen in tektites, moredavite, or Libyan glass. It was found that the effect of meteorites is 100 seconds per 500mL for meteorites weighing 0.00001g (0.01mg) or more.

[0195] [Table 77]

[0196] <Example 94> The results of the 10-second trunk gravity axis test using various meteorites weighing 0.000001 g (0.001 mg) are shown in Table 78. Even with a meteorite weight of 0.000001g (0.001mg), stony meteorites, iron meteorites, and stony-iron meteorites have the power to cancel out the negative effects of tap water, but this was not seen in tektites, moredavite, or Libyan glass. The results were almost the same when the time was reduced from 100 seconds to 10 seconds. It was proven that there is not much difference between 1 mg and 10 seconds and 100 g and 100 seconds. In other words, even if a meteorite that has gained 10 kg is soaked in water for an extra hour, it will not gain 15 kg. As a result, it is unclear whether the presence of a meteorite in the flowing water passage in the container causes the meteorite to vibrate the flowing water passing through it, causing a change in the properties of the water itself (cluster size), but all the subjects were puzzled as to why the same water could have increased in strength. It is a true fact that sounds like a lie.

[0197] [Table 78]

[0198] <Example 95> Example of determining the effective value and meteorite grain size depending on the mixing ratio of meteorite to ceramic Each type of meteorite was crushed into powder with an average particle size of 20μm to 40μm using a Chuo Kakoki Co., Ltd. FV-250 crusher, mixed with silicon nitride (Si3N4) ceramic material, fired at 1,500℃ for 3 hours, and cooled naturally. In addition, 10g of meteorite-containing ceramic was created using 9g of ceramic material (alumina (Al2O3)) and 1g of meteorite, and the same experiment was performed. The subjects who drank 5 mL of tap water from Yokkaichi City, Mie Prefecture and then performed the trunk gravity axis test were used as the control, with the weight set at 0.0 kg. The data are shown in Table 79.

[0199] [Table 79]

[0200] Next, 10g of 100% silicon nitride ceramic was fired and the same experiment was carried out. The firing kiln used was a Motoyama Corporation ultra-fast heating electric furnace NE-4060H (maximum temperature 1800℃). First, the ceramic material alone was prepared and soaked in water for 100 seconds and 10 seconds, after which water was obtained and 5 mL was drunk before a trunk gravity axis test was conducted. The results are shown in Table 80. Therefore, we sintered 10g of ceramics made of 100% alumina, which is another ceramic material, and conducted a trunk gravity axis test. There seems to be a slight effect of infrared radiation, but when using only ceramic, there was a slight change in the range of the trunk gravity axis test in both the 100-second and 10-second tests. Therefore, we tested whether there was any difference when using other fine ceramic materials, and the results were almost the same.

[0201] [Table 80]

[0202] <Example 96> Table 81 shows the results of a trunk gravitational axis test performed immediately after immersing 10 g of zirconia in tap water from Yokkaichi for 100 seconds and 10 seconds, and then obtaining water and drinking 5 mL of it.

[0203] [Table 81]

[0204] <Example 97> Table 82 shows the results of a trunk gravitational axis test conducted immediately after immersing 10 g of silicon carbide in tap water from Yokkaichi for 100 seconds and then drinking 5 mL of the water.

[0205] [Table 82]

[0206] <Example 98> Table 83 shows the results of a trunk gravitational axis test performed immediately after immersing 10 g of cordierite in Yokkaichi tap water for 100 seconds and 10 seconds, obtaining water, and then drinking 5 mL of the water.

[0207] [Table 83]

[0208] <Example 99> Table 84 shows the results of a trunk gravitational axis test conducted immediately after immersing 10 g of barium titanate in tap water from Yokkaichi for 100 seconds and then 10 seconds, and then obtaining water and drinking 5 mL of it.

[0209] [Table 84]

[0210] <Example 100> Table 85 shows the results of a trunk gravitational axis test performed immediately after soaking 10 g of zircon in tap water from Yokkaichi for 100 seconds and then drinking 5 mL of the water.

[0211] [Table 85]

[0212] <Example 101> Table 86 shows the results of a trunk gravitational axis test performed immediately after immersing 10 g of mullite in tap water from Yokkaichi for 100 seconds and then 10 seconds, and then obtaining water and drinking 5 mL of it.

[0213] [Table 86]

[0214] <Example 102> Table 87 shows the results of a trunk gravitational axis test performed immediately after immersing 10 g of aluminum nitride in tap water from Yokkaichi for 100 seconds and then 10 seconds, and then obtaining water and drinking 5 mL of it.

[0215] [Table 87]

[0216] <Example 103> Table 88 shows the results of a trunk gravitational axis test performed immediately after immersing 10 g of silicon nitride in tap water from Yokkaichi for 100 seconds and then 10 seconds, and then obtaining water and drinking 5 mL of it.

[0217] [Table 88]

[0218] <Example 104> Table 89 shows the results of a trunk gravitational axis test conducted immediately after immersing 10 g of lead zirconate titanate in tap water from Yokkaichi for 100 seconds and then 10 seconds, and then obtaining water and drinking 5 mL of it. The results for lead zirconate titanate were not good, but the results for the trunk gravity axis test were otherwise similar. The lower results for lead zirconate titanate may be related to something other than infrared radiation. Since the main focus this time is on infrared radiation, we used a commonly used ceramic material (alumina) for the experiment.

[0219] [Table 89]

[0220] Example 105: Preparation of meteorite-containing ceramic I made them a little larger (1.3981g) so that they would weigh 1.0g after firing, and then used an Evans to remove the excess and make the weight even. Eight types of ceramics were fired with the following meteorite contents: 10% (1g = 1,000mg), 1% (0.1g = 100mg), 0.1% (0.01g = 10mg), 0.01% (0.001g = 1mg), 0.001% (0.0001g = 0.1mg), 0.0001% (0.00001g = 0.01mg), and 0.00001% (0.000001g = 0.001mg). The conclusion was that it would be more efficient to have a greater variety of meteorites.

[0221] <Example 106> Measurement under the conditions of 9g of ceramic material, 1g (1,000mg) of meteorite, 20μm~40μm, 100 seconds The above experiment was performed using 10 g of ceramic, and as no difference was found between this and the tap water of Yokkaichi City, Mie Prefecture, the tap water of Yokkaichi was used as the control, and the data for this was set to 0.0 kg. In the following experiments, the results will be corrected for alumina. In other words, the figures for groups 1 to 10 are calculated by subtracting 0.5 to 1.5 from the values. Each type of meteorite was crushed into powder with an average particle size of 20 μm to 40 μm using a Chuo Kakoki Co., Ltd. FV-250 crusher, mixed with ceramic material, fired at 1500°C for 3 hours, and allowed to cool naturally. Silicon nitride was used as the ceramic material and it was fired at 1,500°C for three hours. Meteorites were crushed to an average particle size of 20 μm to 40 μm, and 10 g of meteorite-containing ceramic was prepared using silicon nitride as a ceramic material, and then immersed in stirred water for 100 seconds. In other words, 10g of meteorite-containing ceramic was created using 9g of ceramic material and 1g (1,000mg) of meteorite, and the 10g of meteorite-containing ceramic was then immersed in stirred tap water for 100 seconds, after which 5mL of the water was drunk to conduct the trunk gravity axis test. According to the inventor's investigation, no significant difference was observed between the case where silicon nitride was used as the ceramic material and the case where alumina was used as the ceramic material, and almost the same results were obtained. Therefore, unless otherwise specified, the results when alumina was used as the ceramic material are shown in a table. In subsequent experiments, as shown in Example 95, for both 100 seconds and 10 seconds, the numbers listed are 0.5 minus for groups 1 and 2, 0.5↑ for groups 3 to 5, 1.0 for groups 6 and 7, 1.0↑ for groups 8 and 9, and 1.0↑ for group 10. Table 90 shows the results of an experiment in which alumina was used as the ceramic material instead of silicon nitride.

[0222] [Table 90]

[0223] <Example 107> Measurement under the conditions of 9g of ceramic material, 1g (1,000mg) of meteorite, 20μm~40μm, 10 seconds Next, the subjects were asked to drink 5 mL of water using the same meteorite crushed to an average particle size of 20 μm to 40 μm in the same manner as above, with a contact time of 10 seconds with tap water, and then a trunk gravity axis test was conducted. The results are shown in Table 91. There was no difference between 100 seconds and 10 seconds. Furthermore, the results were almost the same whether firing clay for outdoor use or for pottery.

[0224] [Table 91]

[0225] <Example 108> Measurement under the conditions of 9g of ceramic material, 1g (1,000mg) of meteorite, 300μm, 100 seconds Meteorite-containing ceramic was created in the same manner as above. Meteorite crushed to an average particle size of 300 μm and alumina ceramic material were used to create 10 g of meteorite-containing ceramic, which was then soaked in stirred water for 100 seconds. In other words, 10 g of meteorite-containing ceramic was created using 9 g of ceramic material (90%) and 1 g of meteorite (10%), and the 10 g of meteorite-containing ceramic was soaked in stirred tap water for 100 seconds, after which 5 mL of the water was drunk and a trunk gravity axis test was performed. The results are shown in Table 92. There was no difference compared to the results of Examples 106 and 107. The results were almost the same whether the clay was fired for open-air firing or for ceramics.

[0226] [Table 92]

[0227] <Example 109> Measurement under the conditions of 9g of ceramic material, 1g (1,000mg) of meteorite, 300μm, 10 seconds Next, the same meteorite was crushed to an average particle size of 300 μm, and the trunk gravity axis test was conducted by drinking 5 mL of water using the same method as above, with a contact time of 10 seconds with tap water. The results are shown in Table 93. There was no difference compared to the results of Example 108. The results were almost the same whether the clay was fired for open-air firing or for ceramics.

[0228] [Table 93]

[0229] <Example 110> Measurement under the conditions of 9.9g of ceramic material, 0.1g (100mg) of meteorite, 20μm to 40μm, and 100 seconds Meteorite-containing ceramic was prepared in the same manner as above. Meteorite was crushed to an average particle size of 20μm to 40μm, and 10g of meteorite-containing ceramic was prepared using alumina as the ceramic material, and was immersed in stirred water for 100 seconds. In other words, 10g of meteorite-containing ceramic containing 0.1g was created using 9.9g (99%) ceramic material, and the 10g of meteorite-containing ceramic was immersed in stirred tap water for 100 seconds, after which 5mL of the water was drunk to conduct the trunk gravity axis test. The results are shown in Table 94. There was almost no difference compared to the results of Example 109, etc. The results were almost the same whether the clay was fired for open-air firing or for ceramics.

[0230] [Table 94]

[0231] <Example 111> Measurement under the conditions of 9.9g of ceramic material, 0.1g (100mg) of meteorite, 20μm to 40μm, and 10 seconds Next, the same meteorite was crushed to an average particle size of 20μm to 40μm, and the same method was used to have the subjects drink 5mL of water after 10 seconds of contact with tap water, and then a trunk gravity axis test was conducted. The results are shown in Table 95. There was almost no difference compared to the results of Example 110, etc. The results were almost the same whether the clay was fired for open-air firing or for ceramics.

[0232] [Table 95]

[0233] <Example 112> Measurement under the conditions of 9.9g of ceramic material, 0.1g (100mg) of meteorite, 300μm, and 100 seconds Meteorite-containing ceramic was created in the same manner as above. Meteorites crushed to an average particle size of 300 μm and alumina were used as the ceramic material to create 10 g of meteorite-containing ceramic, using 9.9 g of ceramic material and 0.1 g (100 mg) of meteorite. The ceramic was then immersed in stirred tap water for 100 seconds, after which 5 mL of the water was drunk and a trunk gravity axis test was performed. The results are shown in Table 96. There was almost no difference compared to the results of Example 111, etc. The results were almost the same whether the clay was fired for open-air firing or for ceramics.

[0234] [Table 96]

[0235] <Example 113> Measurement under the conditions of 9.9g ceramic material, 0.1g meteorite (100mg), 300μm, 10 seconds Next, the same meteorite was crushed to an average particle size of 300 μm, and the same method was used to have the subjects drink 5 mL of water after 10 seconds of contact with tap water, and then a trunk gravity axis test was conducted. The results are shown in Table 97. There was almost no difference compared to the results of Example 112, etc. The results were almost the same whether the clay was fired for open-air firing or for ceramics.

[0236] [Table 97]

[0237] <Example 114> Measurement under the conditions of 9.99g of ceramic material, 0.01g (10mg) of meteorite, 20μm to 40μm, and 100 seconds Meteorite-containing ceramic was created in the same manner as above. Meteorites were crushed to an average particle size of 20μm to 40μm, and alumina was used as the ceramic material to create 10g of meteorite-containing ceramic, using 9.99g of ceramic material and 0.01g (10mg) of meteorite. This was then immersed in stirred tap water for 100 seconds, after which 5mL of the water was drunk and a trunk gravity axis test was performed. The results are shown in Table 98. There was almost no difference compared to the results of Example 113, etc. The results were almost the same whether the clay was fired for open-air firing or for ceramics.

[0238] [Table 98]

[0239] <Example 115> Measurement under the conditions of 9.99g of ceramic material, 0.01g (10mg) of meteorite, 20μm to 40μm, and 10 seconds Next, the same meteorite was crushed to an average particle size of 20μm to 40μm, and the same method was used to have the subjects drink 5mL of tap water with a contact time of 10 seconds, and then a trunk gravity axis test was conducted. The results are shown in Table 99. There was almost no difference compared to the results of Example 114, etc. The results were almost the same whether the clay was fired for open-air firing or for ceramics.

[0240] [Table 99]

[0241] <Example 116> Measurement under the conditions of 9.99g of ceramic material, 0.01g (10mg) of meteorite, 300μm, and 100 seconds Meteorite-containing ceramic was created in the same manner as above. Meteorites were crushed to an average particle size of 300 μm, and alumina was used as the ceramic material to create 10 g of meteorite-containing ceramic, using 9.99 g (99.9%) of ceramic material and 0.01 g (10 mg) of meteorite. The ceramic was then immersed in stirred tap water for 100 seconds, after which 5 mL of the water was drunk and a trunk gravity axis test was performed. The results are shown in Table 100. There was almost no difference compared to the results of Example 115, etc. The results were almost the same whether the clay was fired for open-air firing or for ceramics.

[0242] [Table 100]

[0243] <Example 117> Measurement under the conditions of 9.99g of ceramic material, 0.01g (10mg) of meteorite, 300μm, and 10 seconds Next, the same meteorite was crushed to an average particle size of 300 μm, and the trunk gravity axis test was conducted by drinking 5 mL of water using the same method as above, with a contact time of 10 seconds with tap water. The results are shown in Table 101. There was almost no difference compared to the results of Example 116, etc. The results were almost the same whether the clay was fired for open-air firing or for ceramics.

[0244] [Table 101]

[0245] <Example 118> Measurement under the conditions of 9.999g of ceramic material, 0.001g (1mg) of meteorite, 20μm to 40μm, and 100 seconds Meteorite-containing ceramic was created in the same manner as above. Meteorites were crushed to an average particle size of 20μm to 40μm, and alumina was used as the ceramic material to create 10g of meteorite-containing ceramic with 0.001g (1mg) of meteorite and 9.999g (99.99%) of ceramic material. The subjects were then immersed in stirred tap water for 100 seconds, after which they drank 5mL of the water and conducted a trunk gravity axis test. The results are shown in Table 102. There was almost no difference compared to the results of Example 117, etc. The results were almost the same whether the clay was fired for open-air firing or for ceramics.

[0246] [Table 102]

[0247] <Example 119> Measurement under the conditions of 9.999g of ceramic material, 0.001g (1mg) of meteorite, 20μm to 40μm, and 10 seconds Next, the same meteorite was crushed to an average particle size of 20μm to 40μm, and the same method was used to have the subjects drink 5mL of tap water with a contact time of 10 seconds, and then a trunk gravity axis test was conducted. The results are shown in Table 103. There was almost no difference compared to the results of Example 118, etc. The results were almost the same whether the clay was fired for open-air firing or for ceramics.

[0248] [Table 103]

[0249] <Example 120> Measurement under the conditions of 9.999g of ceramic material, 0.001g (1mg) of meteorite, 300μm, and 100 seconds Meteorite-containing ceramic was created in the same manner as above. Meteorites were crushed to an average particle size of 300 μm, and alumina was used as the ceramic material to create 10 g of meteorite-containing ceramic, using 9.999 g (99.99%) of ceramic material and 0.001 g (1 mg) of meteorite. The ceramic was then immersed in stirred tap water for 100 seconds, after which 5 mL of the water was drunk and a trunk gravity axis test was performed. The results are shown in Table 104. There was almost no difference compared to the results of Example 119, etc. The results were almost the same whether the clay was fired for field firing or for ceramics.

[0250] [Table 104]

[0251] <Example 121> Measurement under the conditions of 9.999g of ceramic material, 0.001g (1mg) of meteorite, 300μm, and 10 seconds Next, the same meteorite was crushed to an average particle size of 300 μm, and the trunk gravity axis test was conducted by drinking 5 mL of water using the same method as above, with a contact time of 10 seconds with tap water. The results are shown in Table 105. There was almost no difference compared to the results of Example 120, etc. The results were almost the same whether the clay was fired for open-air firing or for ceramics.

[0252] [Table 105]

[0253] <Example 122> Measurement under the following conditions: 9.9999g of ceramic material, 0.0001g (0.1mg) of meteorite, average particle size 20μm to 40μm, 100 seconds Meteorite-containing ceramic was created in the same manner as above. Meteorites were crushed to an average particle size of 20μm to 40μm, and alumina was used as the ceramic material to create 10g of meteorite-containing ceramic with 0.0001g (0.1mg) of meteorite and 9.9999g of ceramic material. The ceramic material was then soaked in stirred tap water for 100 seconds, after which 5mL of the water was drunk and a trunk gravity axis test was performed. The results are shown in Table 106. At 0.0001g (0.1mg), the negative water quality was eliminated. The results were almost the same whether firing clay for outdoor use or for pottery.

[0254] [Table 106]

[0255] <Example 123> Measurement under the following conditions: 9.9999g of ceramic material, 0.0001g (0.1mg) of meteorite, average particle size 20μm to 40μm, 10 seconds Next, the same meteorite was crushed to an average particle size of 20μm to 40μm, and the same method was used to have the subjects drink 5mL of tap water with a contact time of 10 seconds, and then a trunk gravity axis test was conducted. The results are shown in Table 107. There was almost no difference compared to Example 122. The results were almost the same whether firing clay for open-air firing or clay for pottery.

[0256] [Table 107]

[0257] <Example 124> Measurement under the conditions of 9.9999g of ceramic material, 0.0001g (0.1mg) of meteorite, average particle size 300μm, and 100 seconds Meteorite-containing ceramic was created in the same manner as above. Meteorites were crushed to an average particle size of 300 μm, and alumina was used as the ceramic material to create 10 g of meteorite-containing ceramic, using 9.9999 g of ceramic material and 0.0001 g (0.1 mg) of meteorite. The ceramic was then immersed in stirred tap water for 100 seconds, after which 5 mL of the water was drunk and a trunk gravity axis test was performed. The results are shown in Table 108. At 0.0001g (0.1mg), the negative water quality was eliminated. The results were almost the same whether firing clay for outdoor use or for pottery.

[0258] [Table 108]

[0259] <Example 125> Measurement under the conditions of 9.9999g of ceramic material, 0.0001% (0.1mg) of meteorite, average particle size 300μm, and 10 seconds Next, the same meteorite was crushed to an average particle size of 300 μm, and the trunk gravity axis test was conducted by drinking 5 mL of water using the same method as above, with a contact time of 10 seconds with tap water. The results are shown in Table 109. Furthermore, the results were almost the same whether firing clay for open-air firing or clay for pottery.

[0260] [Table 109]

[0261] <Example 126> Measurement under the following conditions: 9.99999g of ceramic material, 0.00001g (0.01mg) of meteorite, average particle size 20μm to 40μm, 100 seconds Meteorite-containing ceramic was created in the same manner as above. Meteorites were crushed to an average particle size of 20μm to 40μm, and alumina was used as the ceramic material to create 9.99999g of ceramic material and 0.00001g (0.01mg) of meteorite to create 10g of meteorite-containing ceramic. This was then immersed in stirred tap water for 100 seconds, after which 5mL of the water was drunk and a trunk gravity axis test was performed. The results are shown in Table 110. Even 0.00001g (0.01mg) can eliminate the negative effects of water supply, but the data is not very reliable because the memory is not accurate. The results were almost the same whether firing clay for outdoor use or for pottery.

[0262] [Table 110]

[0263] <Example 127> Measurement under the following conditions: 9.99999g of ceramic material, 0.00001g (0.01mg) of meteorite, average particle size 20μm to 40μm, 10 seconds Next, the same meteorite was crushed to an average particle size of 20μm to 40μm, and the same method was used to have the subjects drink 5mL of tap water with a contact time of 10 seconds, and then a trunk gravity axis test was conducted. The results are shown in Table 111. Even 0.00001g (0.01mg) can eliminate the negative effects of water supply, but the memory is not accurate, so the reliability of the data seems to be somewhat low. The results were almost the same whether firing clay for outdoor firing or for pottery.

[0264] [Table 111]

[0265] <Example 128> Measurement under the conditions of 9.99999g of ceramic material, 0.00001g (0.01mg) of meteorite, average particle size 300μm, and 100 seconds Meteorite-containing ceramic was created in the same manner as above. Meteorites were crushed to an average particle size of 300 μm, and alumina was used as the ceramic material to create 9.99999 g of ceramic material and 0.00001 g (0.01 mg) of meteorite, to create 10 g of meteorite-containing ceramic. This was then immersed in stirred tap water for 100 seconds, after which 5 mL of the water was drunk and a trunk gravity axis test was performed. The results are shown in Table 112. Even 0.0001g (0.1mg) was enough to eliminate the negative effects of tap water. The results were almost the same whether firing clay for outdoor use or for pottery.

[0266] [Table 112]

[0267] <Example 129> Measurement under the conditions of 9.99999g of ceramic material, 0.00001g (0.01mg) of meteorite, average particle size 300μm, and 10 seconds Next, the same meteorite was crushed to an average particle size of 300 μm, and the trunk gravity axis test was conducted by drinking 5 mL of water using the same method as above, with a contact time of 10 seconds with tap water. The results are shown in Table 113. When dry, the meteorite weighs 0.00001g, and the ceramic material (alumina) weighs 9.99999g, so even 0.00001g (0.01mg) can eliminate the negative water supply, but since the memory is not accurate, the reliability of the data in this area seems to be somewhat low. Furthermore, the results were almost the same whether firing clay for outdoor firing or for pottery.

[0268] [Table 113]

[0269] <Example 130> Measurement under the following conditions: 9.999999g of ceramic material, 0.000001g (0.001mg) of meteorite, average particle size 20μm to 40μm, 100 seconds Meteorite-containing ceramic was created in the same manner as above. Meteorites were crushed to an average particle size of 20μm to 40μm, and alumina was used as the ceramic material to create 10g of meteorite-containing ceramic using 9.999999g of ceramic material and 0.000001g (0.001mg) of meteorite. This was then immersed in stirred tap water for 100 seconds, after which 5mL of the water was drunk and a trunk gravity axis test was performed. The results are shown in Table 114. Even 0.000001g (0.001mg) can eliminate the negative effects of water supply, but the memory is not accurate, so the reliability of the data seems to be somewhat low. The results were almost the same whether firing clay for outdoor firing or for ceramics.

[0270] [Table 114]

[0271] <Example 131> Measurement under the following conditions: 9.999999g of ceramic material, 0.000001g (0.001mg) of meteorite, average particle size 20μm to 40μm, 10 seconds Next, the same meteorite was crushed to an average particle size of 20μm to 40μm, and the same method was used to have the subjects drink 5mL of tap water with a contact time of 10 seconds, and then a trunk gravity axis test was conducted. The results are shown in Table 115. Even 0.000001g (0.001mg) can eliminate the negative effects of water supply, but the memory is not accurate, so the reliability of the data seems to be somewhat low. The results were almost the same whether firing clay for outdoor firing or for ceramics.

[0272] [Table 115]

[0273] <Example 132> Measurement under the conditions of 9.999999g of ceramic material, 0.000001g (0.001mg) of meteorite, average particle size 300μm, and 100 seconds Meteorite-containing ceramic was created in the same manner as above. Meteorites were crushed to an average particle size of 300 μm, and alumina was used as the ceramic material to create 10 g of meteorite-containing ceramic, using 9.999999 g of ceramic material and 0.000001 g (0.001 mg) of meteorite. This was then immersed in stirred tap water for 100 seconds, after which 5 mL of the water was drunk and a trunk gravity axis test was performed. The results are shown in Table 116. Even 0.0001g (0.1mg) was enough to eliminate the negative effects of water supply.

[0274] [Table 116]

[0275] <Example 133> Measurement under the conditions of 9.999999g of ceramic material, 0.000001g (0.001mg) of meteorite, average particle size 300μm, and 10 seconds Next, the same meteorite was crushed to an average particle size of 300 μm, and the trunk gravity axis test was conducted by drinking 5 mL of water using the same method as above, with a contact time of 10 seconds with tap water. The results are shown in Table 117. Even 0.000001g (0.001mg) can eliminate the negative effects of water supply, but since the memory is not accurate, the reliability of the data in this area seems to be somewhat unreliable.

[0276] [Table 117]

[0277] Meteorite mixing ratio in dental resin (meteorite grain size) Fibers include unspecified Tencel, regenerated rayon, cupra, polynosic, semi-synthetic acetate, triacetate, promix, synthetic acrylic, nylon, polyurethane, polyester, vinylon, Exlan, cashmere, Tevilon, Environ, Pylen, polyethylene, polystyrene, Natural resins include rosin, lacquer, amber, natural rubber, shellac, gelatin, and casein. Examples of thermosetting resins include phenolic resins, epoxy resins, melamine resins, urea resins, unsaturated polyester resins, alkyd resins, silicone resins, polyurethanes, and thermosetting polyamides, while examples of thermoplastic resins include polyethylene, polypropylene, polystyrene, polyethylene terephthalate, polyvinyl chloride, AS resins, ABS resins, polyamides, polycarbonates, polyacetals, polybutylene terephthalates, polyphenylene sulfide, polyether ether ketones, polyamide imides, polyether imides, and polysulfones. In Japanese, resin is used as a general term for both natural and synthetic resins. There are two types of resin: natural resin, which is a substance secreted from plants, and synthetic resin, which is an artificially synthesized synthetic resin. As a representative fiber of the present invention, seven types of resin containing meteorite were created using dental resin with a meteorite content of 10%, 1%, 0.1%, 0.01%, 0.001%, and 0.0001%, and a trunk gravity axis test was conducted. Dental resin was used because it is used in the mouth, but is approved as a medical product, and safety is guaranteed with no reports of harmful effects. Each type of meteorite was crushed into powder with an average particle size of 20 μm to 40 μm using a Chuo Kakoki Co., Ltd. FV-250 crusher, and then mixed with powdered resin material. The resulting material was left at 50°C for 1.5 hours in a Nippon Heater CW36T-R2 electric can warmer to be used as the "resin." The water supply from Yokkaichi City, Mie Prefecture was used as the control, which was set at 0.0 kg.

[0278] <Example 134> As a control, the results of using only the resin material are shown in Table 118. There was no change in the tap water in Yokkaichi. When dry, a 10g block of dental resin containing 100% dental resin was prepared. Tap water from Yokkaichi was used as the control. There was no significant change in the trunk gravity axis test with just the resin. Since it is a dental resin approved by the Ministry of Health, Labor and Welfare, it is not bad for the body and the result was 0.0↑, which should have been negative. Determination of effective value, meteorite particle size, and amount based on the mixing ratio of meteorite in dental resin Seven types of dental resin were created, each containing 10g of meteorite: 10% (1g = 1,000mg), 1% (0.1g = 100mg), 0.01% (0.01g = 10mg), 0.01% (0.001g = 1mg), 0.0001% (0.0001g = 0.1mg), 0.00001% (0.00001g = 0.01mg), and 0.000001% (0.000001g = 0.001mg). The same experiment was conducted using 100g of ceramic containing 10% (10g) (10,000mg) meteorites with meteorite grain sizes of 20-40μm and 300μm.

[0279] [Table 118]

[0280] <Example 135> Next, a resin plate was made using 10g of dental resin and the same experiment was performed. I made them a little larger than I needed, and before they dried I used Evans to remove any excess so that the weight would be 10g when dry. If there was less, I added more resin to make the weight even. Each type of meteorite was crushed into powder with an average particle size of 20μm to 40μm using a Chuo Kakoki Co., Ltd. FV-250 crusher, and 1g (1,000mg) of meteorite was mixed with 9g (10%) of dental resin material to create 10g of meteorite-containing dental resin, and the above experiment was conducted. The control group consisted of subjects drinking 5 mL of tap water from Yokkaichi City, Mie Prefecture, and then undergoing the trunk gravity axis test, with the weight set at 0.0 kg. First, only the dental resin material was prepared and soaked in water for 100 seconds. After that, water was obtained and the subject drank 5 mL of it, immediately after which the trunk gravity axis test was performed. The results are shown in Table 119.

[0281] [Table 119] A 10g ball of dental resin was created when dry and subjected to a trunk gravity axis test, the results of which are shown in Table 120. Dental resin alone only produced changes within the margin of error in the trunk gravity axis test.

[0282] [Table 120]

[0283] <Example 136> In other words, although there seems to be some effect of infrared radiation, the above experiment was conducted using 0.5g of each type of meteorite to create 10g of meteorite-containing ceramic with a meteorite content of 3g. The results are shown in Table 121. Compared to the meteorite above, the 0.5↑ for dental resin alone was within the margin of error.

[0284] [Table 121]

[0285] <Example 137> Measurement under the conditions of 9g (90%) of dental resin material, 1g (10%) of meteorite, 20μm to 40μm, 100 seconds The above experiment was performed using 10 g of dental resin. As there was no difference from the tap water of Yokkaichi City, Mie Prefecture, the tap water of Yokkaichi City was used as the control at 0.0 kg. Each type of meteorite was crushed into powder with an average particle size of 20 μm to 40 μm using a Chuo Kakoki Co., Ltd. FV-250 crusher. Meteorites and dental resin were used to create 10 g of meteorite-containing dental resin, which was then immersed in stirred water for 100 seconds. In other words, 10g of meteorite-containing dental resin was created using 9g (9,000mg) of dental resin material and 1g (1,000mg) of meteorite, and this was then immersed in stirred tap water for 100 seconds, after which 5mL of the water was drunk and the trunk gravity axis test was performed. The results are shown in Table 122.

[0286] [Table 122]

[0287] <Example 138> Measurement under the conditions of 9g (90%) of dental resin material, 1g (10%) of meteorite, 20μm to 40μm, 10 seconds Next, the same meteorite was crushed to an average particle size of 20μm to 40μm, and the same method was used to have the subjects drink 5mL of tap water with a contact time of 10 seconds, and then a trunk gravity axis test was conducted. The results are shown in Table 123. Compared to Example 137, nothing changed.

[0288] [Table 123]

[0289] <Example 139> Measurements were performed under the conditions of 9g (90%) of dental resin material, 1g (10%) of meteorite, 300 μm, and 100 seconds. A meteorite-containing dental resin was prepared in the same manner as above. Meteorites crushed to an average particle size of 300 μm and dental resin were used to prepare 10 g of meteorite-containing dental resin, which was then immersed in stirred water for 100 seconds. In other words, 10g of meteorite-containing dental resin was created using 9g (90%) dental resin material and 1g (10%) meteorite, and then the resin was immersed in stirred tap water for 100 seconds, after which 5mL of the water was drunk and the trunk gravity axis test was performed. The results are shown in Table 124.

[0290] [Table 124]

[0291] <Example 140> Measurement under the conditions of 9g (90%) dental resin material, 1g (10%) meteorite, 300 μm, 10 seconds Next, the same meteorite was crushed to an average particle size of 300 μm, and the trunk gravity axis test was conducted by drinking 5 mL of water using the same method as above, with a contact time of 10 seconds with tap water. The results are shown in Table 125. Compared to Example 139, nothing changed.

[0292] [Table 125]

[0293] <Example 141> Measurement under the conditions of 9.9 g of dental resin material, 0.1 g (100 mg) of meteorite, 20 μm to 40 μm, and 100 seconds Meteorite-containing dental resin was prepared in the same manner as above. Meteorite crushed to an average particle size of 20 μm to 40 μm and dental resin were used to prepare 10 g of meteorite-containing dental resin, which was then immersed in stirred water for 100 seconds. In other words, 10 g of dental resin containing 0.1 g of meteorite was created using 9.9 g of dental resin material, and this was then immersed in stirred tap water for 100 seconds, after which 5 mL of the water was drunk to conduct the trunk gravity axis test. The results are shown in Table 126.

[0294] [Table 126]

[0295] <Example 142> Measurement under the conditions of 9.9 g of dental resin material, 0.1 g (10 mg) of meteorite, 20 μm to 40 μm, and 10 seconds Next, the same meteorite was crushed to an average particle size of 20μm to 40μm, and the same method was used to have the subjects drink 5mL of tap water with a contact time of 10 seconds, and then a trunk gravity axis test was conducted. The results are shown in Table 127.

[0296] [Table 127]

[0297] <Example 143> Measurement under the conditions of 9.9 g of dental resin material, 0.1 g (100 mg) of meteorite, 300 μm, and 100 seconds A meteorite-containing dental resin was prepared in the same manner as above. Meteorites crushed to an average particle size of 300 μm and dental resin were used to prepare 10 g of meteorite-containing dental resin, which was then immersed in stirred water for 100 seconds. In other words, 10 g of meteorite-containing dental resin was created using 9.9 g of dental resin material and 0.1 g (100 mg) of meteorite, and this was then immersed in stirred tap water for 100 seconds, after which the subject was asked to drink 5 mL of the water and perform the trunk gravity axis test. The results are shown in Table 128.

[0298] [Table 128]

[0299] <Example 144> Measurement under the conditions of 9.9 g of dental resin material, 0.1 g (100 mg) of meteorite, 300 μm, and 10 seconds Next, the same meteorite was crushed to an average particle size of 300 μm, and the trunk gravity axis test was conducted by drinking 5 mL of water using the same method as above, with a contact time of 10 seconds with tap water. The results are shown in Table 129.

[0300] [Table 129]

[0301] <Example 145> Measurement under the conditions of 9.99 g of dental resin material, 0.01 g (10 mg) of meteorite, 20 μm to 40 μm, and 100 seconds Meteorite-containing dental resin was prepared in the same manner as above. Meteorite crushed to an average particle size of 20 μm to 40 μm and dental resin were used to prepare 10 g of meteorite-containing dental resin, which was then immersed in stirred water for 100 seconds. In other words, 10 g of meteorite-containing dental resin was created using 9.99 g of dental resin material and 0.01 g (10 mg) of meteorite, and this was then immersed in stirred tap water for 100 seconds, after which 5 mL of the water was drunk and the trunk gravity axis test was performed. The results are shown in Table 130.

[0302] [Table 130]

[0303] <Example 146> Measurement under the conditions of 9.99 g of dental resin material, 0.01 g (10 mg) of meteorite, 20 μm to 40 μm, and 10 seconds Next, the same meteorite was crushed to an average particle size of 20μm to 40μm, and the same method was used to have the subjects drink 5mL of tap water with a contact time of 10 seconds, and then a trunk gravity axis test was conducted. The results are shown in Table 131.

[0304] [Table 131]

[0305] <Example 147> Measurement under the conditions of 9.99 g of dental resin material, 0.01 g (10 mg) of meteorite, 300 μm, and 100 seconds A meteorite-containing dental resin was prepared in the same manner as above. Meteorites crushed to an average particle size of 300 μm and dental resin were used to prepare 10 g of meteorite-containing dental resin, which was then immersed in stirred water for 100 seconds. In other words, 10 g of meteorite-containing dental resin was created using 9.99 g of dental resin material and 0.01 g (10 mg) of meteorite, and this was then immersed in stirred tap water for 100 seconds, after which 5 mL of the water was drunk and the trunk gravity axis test was performed. The results are shown in Table 132.

[0306] [Table 132]

[0307] <Example 148> Measurement under the conditions of 9.99 g of dental resin material, 0.01 g (10 mg) of meteorite, 300 μm, and 10 seconds Next, the same meteorite was crushed to an average particle size of 300 μm, and the trunk gravity axis test was conducted by drinking 5 mL of water using the same method as above, with a contact time of 10 seconds with tap water. The results are shown in Table 133.

[0308] [Table 133]

[0309] <Example 149> Measurement under the conditions of 9.999g of dental resin material, 0.001g (1mg) of meteorite, 20μm to 40μm, and 100 seconds Meteorite-containing dental resin was prepared in the same manner as above. Meteorite crushed to an average particle size of 20 μm to 40 μm and dental resin were used to prepare 10 g of meteorite-containing dental resin, which was then immersed in stirred water for 100 seconds. In other words, 10 g of meteorite-containing dental resin was created using 9.999 g of dental resin material and 0.001 g (1 mg) of meteorite, and this was then immersed in stirred tap water for 100 seconds, after which 5 mL of the water was drunk and the trunk gravity axis test was performed. The results are shown in Table 134.

[0310] [Table 134]

[0311] <Example 150> Measurement under the conditions of 9.999g of dental resin material, 0.001g (1mg) of meteorite, 20μm to 40μm, and 10 seconds Next, the same meteorite was crushed to an average particle size of 20μm to 40μm, and the same method was used to have the subjects drink 5mL of tap water with a contact time of 10 seconds, and then a trunk gravity axis test was conducted. The results are shown in Table 135.

[0312] [Table 135]

[0313] <Example 151> Measurement under the conditions of 9.999g of dental resin material, 0.001g (1mg) of meteorite, 300μm, and 100 seconds A meteorite-containing dental resin was prepared in the same manner as above. Meteorites crushed to an average particle size of 300 μm and dental resin were used to prepare 10 g of meteorite-containing dental resin, which was then immersed in stirred water for 100 seconds. In other words, 10 g of meteorite-containing dental resin was created using 9.999 g of dental resin material and 0.001 g (1 mg) of meteorite, and this was then immersed in stirred tap water for 100 seconds, after which 5 mL of the water was drunk and the trunk gravity axis test was performed. The results are shown in Table 136.

[0314] [Table 136]

[0315] <Example 152> Measurement under the conditions of 9.999g of dental resin material, 0.001g (1mg) of meteorite, 300μm, and 10 seconds Next, the same meteorite was crushed to an average particle size of 300 μm, and the trunk gravity axis test was conducted by drinking 5 mL of water using the same method as above, with a contact time of 10 seconds with tap water. The results are shown in Table 137. It was thought that by mixing 1 mg or more of 20 μm to 300 μm into full dentures, partial dentures, resin restorations, or cement, it could be converted into positive vibrations in the oral cavity.

[0316] [Table 137]

[0317] <Example 153> Measurement under the conditions of 9.9999g of dental resin material, 0.0001g (0.1mg) of meteorite, average particle size 20μm to 40μm, and 100 seconds Meteorite-containing dental resin was prepared in the same manner as above. Meteorite crushed to an average particle size of 20 μm to 40 μm and dental resin were used to prepare 10 g of meteorite-containing dental resin, which was then immersed in stirred water for 100 seconds. In other words, 10 g of meteorite-containing dental resin was created using 9.9999 g of dental resin material and 0.0001 g (0.1 mg) of meteorite, and this was then immersed in stirred tap water for 100 seconds, after which 5 mL of the water was drunk to conduct the trunk gravity axis test. The results are shown in Table 138. 0.0001g (0.1mg) was able to eliminate the negative effects of water supply.

[0318] [Table 138]

[0319] <Example 154> Measurement under the conditions of 9.9999g of dental resin material, 0.0001g (0.1mg) of meteorite, average particle size 20μm to 40μm, and 10 seconds Next, the same meteorite was crushed to an average particle size of 20μm to 40μm, and the same method was used to have the subjects drink 5mL of tap water with a contact time of 10 seconds, and then a trunk gravity axis test was conducted. The results are shown in Table 139.

[0320] [Table 139]

[0321] <Example 155> Measurement was performed under the conditions of 9.999g of dental resin material, 0.001g (1mg) of meteorite, average particle size 300μm, and 100 seconds A meteorite-containing dental resin was prepared in the same manner as above. Meteorites crushed to an average particle size of 300 μm and dental resin were used to create 10 g of meteorite-containing dental resin, which was then immersed in stirred water for 100 seconds, after which the subjects drank 5 mL of the water and performed the trunk gravity axis test. The results are shown in Table 140. 0.0001g (0.1mg) was able to eliminate the negative effects of water supply.

[0322] [Table 140]

[0323] <Example 156> Dental resin material 0.0001g (0.1mg), average particle size 300μm, measurement for 10 seconds Next, the same meteorite was crushed to an average particle size of 300 μm, and the trunk gravity axis test was conducted by drinking 5 mL of water using the same method as above, with a contact time of 10 seconds with tap water. The results are shown in Table 141.

[0324] [Table 141]

[0325] <Example 157> Measurement under the conditions of 9.99999g of dental resin material, 0.00001g (0.01mg) of meteorite, average particle size 20μm to 40μm, and 100 seconds Meteorite-containing dental resin was prepared in the same manner as above. Meteorite crushed to an average particle size of 20 μm to 40 μm and dental resin were used to prepare 10 g of meteorite-containing dental resin, which was then immersed in stirred water for 100 seconds. In other words, 10 g of meteorite-containing dental resin was created using 9.99999 g of dental resin material and 0.00001 g (0.01 mg) of meteorite, and this was then immersed in stirred tap water for 100 seconds, after which 5 mL of the water was drunk and a trunk gravity axis test was performed. The results are shown in Table 142. Even 0.00001g (0.01mg) can eliminate the negative effects of water supply, but since the memory is not accurate, the reliability of the data in this area seems to be somewhat unreliable.

[0326] [Table 142]

[0327] <Example 158> Measurement under the conditions of 9.99999g of dental resin material, 0.00001g (0.01mg) of meteorite, average particle size 20μm to 40μm, and 10 seconds Next, the same meteorite was crushed to an average particle size of 20μm to 40μm, and the same method was used to have the subjects drink 5mL of tap water with a contact time of 10 seconds, and then a trunk gravity axis test was conducted. The results are shown in Table 143. Even 0.00001g (0.01mg) can eliminate the negative effects of water supply, but since the memory is not accurate, the reliability of the data in this area seems to be somewhat unreliable.

[0328] [Table 143]

[0329] <Example 159> Measurement under the conditions of 9.99999g of dental resin material, 0.00001g (0.01mg) of meteorite, average particle size of 300μm, and 100 seconds A meteorite-containing dental resin was prepared in the same manner as above. Meteorites crushed to an average particle size of 300 μm and dental resin were used to create 10 g of meteorite-containing dental resin, which was then immersed in stirred water for 100 seconds, after which the subjects drank 5 mL of the water and performed the trunk gravity axis test. The results are shown in Table 144. There was a positive change in the trunk gravitational axis test at meteorite content of 0.00001g (0.01mg). Even 0.0001g (0.1mg) was enough to eliminate the negative effects of water. It was found that the minimum amount of chlorine that can be mixed into resin is 0.00001g (0.01mg).

[0330] [Table 144]

[0331] <Example 160> Measurement under the conditions of 9.99999g of dental resin material, 0.00001g (0.01mg) of meteorite, average particle size 300μm, and 10 seconds Next, the same meteorite was crushed to an average particle size of 300 μm, and the trunk gravity axis test was conducted by drinking 5 mL of water using the same method as above, with a contact time of 10 seconds with tap water. The results are shown in Table 145. Even 0.00001g (0.01mg) can eliminate the negative effects of water supply, but since the memory is not accurate, the reliability of the data in this area seems to be somewhat unreliable.

[0332] [Table 145]

[0333] <Example 161> Measurement under the conditions of 9.999999g of dental resin material, 0.000001g (0.001mg) of meteorite, average particle size 20μm to 40μm, and 100 seconds Meteorite-containing dental resin was prepared in the same manner as above. Meteorite crushed to an average particle size of 20 μm to 40 μm and dental resin were used to prepare 10 g of meteorite-containing dental resin, which was then immersed in stirred water for 100 seconds. In other words, 10 g of meteorite-containing dental resin was created using 9.999999 g of dental resin material and 0.000001 g (0.001 mg) of meteorite, and this was then immersed in stirred tap water for 100 seconds, after which 5 mL of the water was drunk and a trunk gravity axis test was performed. The results are shown in Table 146. Even 0.000001g (0.001mg) can eliminate the negative effects of water supply, but since the memory is not accurate, the reliability of the data in this area seems to be somewhat unreliable.

[0334] [Table 146]

[0335] <Example 162> Measurement under the conditions of 99.999999g of dental resin material, 0.000001g (0.001mg) of meteorite, average particle size 20μm to 40μm, and 10 seconds Next, the same meteorite was crushed to an average particle size of 20μm to 40μm, and the same method was used to have the subjects drink 5mL of tap water with a contact time of 10 seconds, and then a trunk gravity axis test was conducted. The results are shown in Table 147. Even 0.000001g (0.001mg) was able to eliminate the negative effects of water supply on stony meteorites, iron meteorites, and stony-iron meteorites, but no effect was observed on tektite, moldavite, or Libyan glass.

[0336] [Table 147]

[0337] <Example 163> Measurement under the conditions of 99.999999g of dental resin material, 0.000001g (0.001mg) of meteorite, average particle size 300μm, and 100 seconds A meteorite-containing dental resin was prepared in the same manner as above. Meteorites crushed to an average particle size of 300 μm and dental resin were used to create 10 g of meteorite-containing dental resin, which was then immersed in stirred water for 100 seconds, after which the subjects drank 5 mL of the water and performed the trunk gravity axis test. The results are shown in Table 148. Even 0.000001g (0.001mg) was enough to eliminate the negative effects of water supply.

[0338] [Table 148]

[0339] <Example 164> Measurement under the conditions of 99.999999g of dental resin material, 0.000001g (0.001mg) of meteorite, average particle size 300μm, and 10 seconds Next, the same meteorite was crushed to an average particle size of 300 μm, and the trunk gravity axis test was conducted by drinking 5 mL of water using the same method as above, with a contact time of 10 seconds with tap water. The results are shown in Table 149. It turns out that there is almost no force. Therefore, data on the weight of various meteorites less than 0.000001g (0.001mg) is omitted for both 100 seconds and 10 seconds.

[0340] [Table 149]

[0341] <Example 165> Cement can be broadly divided into four types: (1) Portland cement, (2) blended cement (blast furnace cement, silica cement, fly ash cement), (3) ecocement, and (4) special cement (alumina cement, white Portland cement, ultra-fast hardening cement, expansive cement, colloidal cement, oil well cement, geothermal cement). Dental cements include, for example, glass ionomer cement, resin cement, zinc phosphate cement, zinc oxide eugenol cement, non-eugenol cement, polycarboxylate cement, zinc oxide eugenol cement, EBA cement, CR-based resin cement, PMMA-based resin cement, zinc polycarbonate cement, carbocement, ceramia cement, polycarboxylate cement, and superbond. The experimental results were almost the same for ceramic and resin, so we will omit the details here. The adhesive strength was fine for meteorites with a particle size of 20μm to 40μm, but the adhesive strength decreased for 300μm, so there was no problem in making the filter. Taking zinc phosphate cement as an example, the following is described for representative meteorites with weights of 10 mg, 1 mg, 0.1 mg, and 0.01 mg, meteorite particle sizes of 20 μm to 40 μm and approximately 300 μm, and water contact times of 100 seconds and 10 seconds.

[0342] <Example 166> Measurement under the conditions of 9.99 g of zinc phosphate cement material, 0.01 g (10 mg) of meteorite, 20 μm to 40 μm, and 100 seconds A meteorite-containing zinc phosphate cement board was prepared in the same manner as above. Meteorite crushed to an average particle size of 20 μm to 40 μm and zinc phosphate cement were used to prepare 10 g of meteorite-containing zinc phosphate cement board, which was then immersed in stirred water for 100 seconds. In other words, a meteorite-containing zinc phosphate cement board (10 g) was created using 9.99 g of zinc phosphate cement material and 0.01 g (10 mg) of meteorite, and this was then immersed in stirred tap water for 100 seconds, after which 5 mL of the water was drunk and a trunk gravitational axis test was performed. The results are shown in Table 150.

[0343] [Table 150]

[0344] <Example 167> Measurement under the conditions of 9.99 g of zinc phosphate cement material, 0.01 g (10 mg) of meteorite, 20 μm to 40 μm, and 10 seconds Next, the same meteorite was crushed to an average particle size of 20μm to 40μm, and the same method was used to have the subjects drink 5mL of tap water with a contact time of 10 seconds, and then a trunk gravity axis test was conducted. The results are shown in Table 151.

[0345] [Table 151]

[0346] <Example 162> Measurement under the conditions of 9.99g zinc phosphate cement material, 0.01g (10mg) meteorite, 300μm, 100 seconds A meteorite-containing zinc phosphate cement board was prepared in the same manner as above. Meteorite crushed to an average particle size of 300 μm and zinc phosphate cement were used to prepare 10 g of meteorite-containing zinc phosphate cement board, which was then immersed in stirred water for 100 seconds. In other words, a meteorite-containing zinc phosphate cement board (10 g) was created using 9.99 g of zinc phosphate cement material and 0.01 g (10 mg) of meteorite, and this was then immersed in stirred tap water for 100 seconds, after which 5 mL of the water was drunk and a trunk gravitational axis test was performed. The results are shown in Table 152.

[0347] [Table 152]

[0348] <Example 163> Measurement under the conditions of 9.99 g of zinc phosphate cement material, 0.01 g (10 mg) of meteorite, 300 μm, and 10 seconds Next, the same meteorite was crushed to an average particle size of 300 μm, and the trunk gravity axis test was conducted by drinking 5 mL of water using the same method as above, with a contact time of 10 seconds with tap water. The results are shown in Table 153.

[0349] [Table 153]

[0350] <Example 164> Measurement under the conditions of 9.999 g of zinc phosphate cement, 0.001 g (1 mg) of meteorite, 20 μm to 40 μm, and 100 seconds A meteorite-containing zinc phosphate cement board was prepared in the same manner as above. Meteorite crushed to an average particle size of 20 μm to 40 μm and zinc phosphate cement were used to prepare 10 g of meteorite-containing zinc phosphate cement board, which was then immersed in stirred water for 100 seconds. In other words, a 10g meteorite-containing zinc phosphate cement slab was created using 9.999g of zinc phosphate cement and 0.001g (1mg) of meteorite, and then it was immersed in stirred tap water for 100 seconds, after which 5mL of the water was drunk and the trunk gravitational axis test was performed. The results are shown in Table 154.

[0351] [Table 154]

[0352] <Example 165> Measurement under the conditions of 9.999g zinc phosphate cement, 0.001g (1mg) meteorite, 20μm to 40μm, 10 seconds Next, the same meteorite was crushed to an average particle size of 20μm to 40μm, and the same method was used to have the subjects drink 5mL of tap water with a contact time of 10 seconds, and then a trunk gravity axis test was conducted. The results are shown in Table 155.

[0353] [Table 155]

[0354] <Example 166> Measurement under the conditions of 9.999g zinc phosphate cement, 0.001g (1mg) meteorite, 300μm, 100 seconds A meteorite-containing zinc phosphate cement board was prepared in the same manner as above. Meteorite crushed to an average particle size of 300 μm and zinc phosphate cement were used to prepare 10 g of meteorite-containing zinc phosphate cement board, which was then immersed in stirred water for 100 seconds. In other words, a 10g meteorite-containing zinc phosphate cement slab was created using 9.999g of zinc phosphate cement and 0.001g (1mg) of meteorite, and then it was immersed in stirred tap water for 100 seconds, after which 5mL of the water was drunk and the trunk gravitational axis test was performed. The results are shown in Table 156.

[0355] [Table 156]

[0356] <Example 167> Measurement under the conditions of 9.999g zinc phosphate cement, 0.001g (1mg) meteorite, 300μm, 10 seconds Next, the same meteorite was crushed to an average particle size of 300 μm, and the trunk gravity axis test was conducted by drinking 5 mL of water using the same method as above, with a contact time of 10 seconds with tap water. The results are shown in Table 157. It is thought that by mixing 1 mg or more of 20 μm to 300 μm into full dentures, partial dentures, resin restorations, or cement, it can be converted into positive vibrations in the oral cavity.

[0357] [Table 157]

[0358] <Example 168> Measurement under the conditions of 9.9999g of zinc phosphate cement, 0.0001g (0.1mg) of meteorite, average particle size 20μm to 40μm, and 100 seconds A meteorite-containing zinc phosphate cement board was prepared in the same manner as above. Meteorite crushed to an average particle size of 20 μm to 40 μm and zinc phosphate cement were used to prepare 10 g of meteorite-containing zinc phosphate cement board, which was then immersed in stirred water for 100 seconds. In other words, 10 g of meteorite-containing zinc phosphate cement slab was created using 9.9999 g of zinc phosphate cement and 0.0001 g (0.1 mg) of meteorite, and this was then immersed in stirred tap water for 100 seconds, after which 5 mL of the water was drunk to perform the trunk gravitational axis test. The results are shown in Table 158. 0.0001g (0.1mg) was able to eliminate the negative effects of water supply.

[0359] [Table 158]

[0360] <Example 169> Measurement under the conditions of 9.9999g of zinc phosphate cement, 0.0001g (0.1mg) of meteorite, average particle size 20μm to 40μm, and 10 seconds Next, the same meteorite was crushed to an average particle size of 20μm to 40μm, and the same method was used to have the subjects drink 5mL of tap water with a contact time of 10 seconds, and then a trunk gravity axis test was conducted. The results are shown in Table 159.

[0361] [Table 159]

[0362] <Example 170> Measurement under the conditions of 9.9999g of zinc phosphate cement, 0.0001g (0.1mg) of meteorite, average particle size of 300μm, and 100 seconds A meteorite-containing zinc phosphate cement plate was prepared in the same manner as above. Meteorites crushed to an average particle size of 300 μm and zinc phosphate cement were used to prepare 10 g of meteorite-containing zinc phosphate cement plate, which was then immersed in stirred water for 100 seconds and then 5 mL of the water was drunk to perform the trunk gravitational axis test. The results are shown in Table 160.

[0363] [Table 160]

[0364] <Example 171> Measurement under the conditions of 9.9999g of zinc phosphate cement, 0.0001g (0.1mg) of meteorite, average particle size of 300μm, and 10 seconds Next, the same meteorite was crushed to an average particle size of 300 μm, and the trunk gravity axis test was conducted by drinking 5 mL of water using the same method as above, with a contact time of 10 seconds with tap water. The results are shown in Table 161.

[0365] [Table 161]

[0366] <Example 172> Measurement under the conditions of 9.99999g of zinc phosphate cement, 0.00001g (0.01mg) of meteorite, average particle size 20μm to 40μm, and 100 seconds A meteorite-containing zinc phosphate cement board was prepared in the same manner as above. Meteorite crushed to an average particle size of 20 μm to 40 μm and zinc phosphate cement were used to prepare 10 g of meteorite-containing zinc phosphate cement board, which was then immersed in stirred water for 100 seconds. In other words, 10 g of meteorite-containing zinc phosphate cement slab was created using 9.99999 g of zinc phosphate cement and 0.00001 g (0.01 mg) of meteorite, and the slab was then immersed in stirred tap water for 100 seconds, after which 5 mL of the water was drunk and the trunk gravitational axis test was performed. The results are shown in Table 162. Even 0.00001g (0.01mg) can eliminate the negative effects of water supply, but since the memory is not accurate, the reliability of the data in this area seems to be somewhat unreliable.

[0367] [Table 162]

[0368] <Example 173> Measurement under the conditions of 9.99999g of zinc phosphate cement, 0.00001g (0.01mg) of meteorite, average particle size 20μm to 40μm, and 10 seconds Next, the same meteorite was crushed to an average particle size of 20μm to 40μm, and the same method was used to have the subjects drink 5mL of tap water with a contact time of 10 seconds, and then a trunk gravity axis test was conducted. The results are shown in Table 163. Even 0.000001g (0.01mg) can eliminate the negative effects of water supply, but since the memory is not accurate, I feel that the reliability of this measure is somewhat lacking.

[0369] [Table 163]

[0370] <Example 174> Measurement under the conditions of 9.99999g of zinc phosphate cement, 0.00001g (0.01mg) of meteorite, average particle size of 300μm, and 100 seconds A meteorite-containing zinc phosphate cement plate was prepared in the same manner as above. Meteorites crushed to an average particle size of 300 μm and zinc phosphate cement were used to prepare a meteorite-containing zinc phosphate cement plate (10 g), which was then immersed in stirred water for 100 seconds and then 5 mL of the water was drunk to perform the trunk gravitational axis test. The results are shown in Table 164. A meteorite content of 0.00001g (0.01mg) caused a positive change in the trunk gravity axis test. Even 0.00001g (0.01mg) was enough to eliminate the negative effects of the water supply. It was found that the minimum amount of meteorite that can be mixed into resin is 0.00001g (0.01mg).

[0371] [Table 164]

[0372] <Example 175> Measurement under the conditions of 9.99999g of zinc phosphate cement, 0.00001g (0.01mg) of meteorite, average particle size of 300μm, and 10 seconds Next, the same meteorite was crushed to an average particle size of 300 μm, and the trunk gravity axis test was conducted by drinking 5 mL of water using the same method as above, with a contact time of 10 seconds with tap water. The results are shown in Table 165. Even 0.000001g (0.01mg) was enough to eliminate the negative effects of tap water. This is because 0.01mg of ceramics (including fired clay for pottery), resin, and cement are almost the same as tap water and have no effect. Therefore, the weights of various meteorites less than 0.000001g (0.001mg) are omitted.

[0373] [Table 165]

[0374] Experiments on the effectiveness of various minerals in terms of quantity and time Therefore, we investigated whether there was a mineral other than meteorite that could produce an effect of 0.5kg to 2kg or more in the trunk gravity axis test using tap water from Yokkaichi City, Mie Prefecture, similar to the well water from Tanba. Kinkaseki is a metamorphic rock found in the Hime River basin, and does not have an official mineral name. We used a rock that is thought to be a sulfide agate, and is formed by metamorphosing pyrite and agate into mudstone, and is called "kinkaseki" in the Itoigawa region. Iwo stone is a natural mineral mined from Mt. Iwo on the border between Toyama and Ishikawa prefectures; in the case of red, the scientific name is orthopyroxene hornblende andesite, blue is quartz-biotite-hornblende-biopyroxene andesite, antelope horn is a chamois antler, stag antler is a deer antler that includes deer antler, meng stone is blue meng stone and includes blue meng stone, Mumyoui ware is a traditional craft of Sado Island in Niigata prefecture, clam shells are bivalve shells, and ishi ketsumeiichi abalone refers to abalone, common joint, and conch shells.

[0375] In order to determine the type and amount of minerals, we obtained each mineral over a period of three years and performed the same trunk gravity axis test. First, we determined the different types of minerals in 1g. The method is as follows. <Example 176> In the experiment, (a) the minerals were weighed using Shimadzu Corporation's high-precision analytical electronic balance BM 0.01 mg weighing, (b) the minerals were cut out with a dental diamond desk using a dental diamond burr using a dental magnifying glass, and each mineral was adjusted to 10.00 g. (c) Minerals less than 100 mg were crushed in a grinder and weighed. Meteorites were crushed into powder with an average particle size of 20 μm to 30 μm using a Chuo Kakoki Co., Ltd. FV-250 grinder. Minerals with small amounts were crushed into powder with an average particle size of 50 μm to 100 μm using a Labnect Co., Ltd. high-speed mill. (d) 100 mL of tap water from Yokkaichi City, Mie Prefecture was used for the experiment. (e) The water was stirred for 100 seconds at 500 rpm using a magnetic stirrer REXIM, and (f) the minerals were immersed in the stirred water for 1 second. (Ki) To extract the minerals from the stirred water, three coffee filters were used to filter them and then the water was collected in a beaker. (Ki) The filtration time, during which the minerals were in contact with the water even if some water remained, was set at 100 seconds in total. (Ki) The subjects drank 5mL of the water that had been filtered by soaking the minerals, and (Ki) immediately after drinking the water, the subjects performed one type of trunk gravitational axis test per day without being informed of anything. (Ki) One person performed the trunk gravitational axis test three times for each mineral, and the average was calculated after excluding those who were extremely weak or extremely strong. For the various minerals that were scarce, the crushers (hammer type) NH-33S manufactured by Sansho Industry Co., Ltd. were used to crush the minerals to an average meteorite particle size of 20 μm to 40 μm. Tables 166 to 170 show the results of the trunk gravity axis test using 100 g (100,000 mg) of various minerals obtained by the above method and 100 mL of Yokkaichi tap water after 100 seconds of contact.

[0376] [Table 166]

[0377] [Table 167]

[0378] [Table 168]

[0379] [Table 169]

[0380] [Table 170]

[0381] The 115 types of minerals in group (b) were used as minerals that, when used alone, had an effect of 1.0kg to 2kg↑ in the trunk gravity axis test, similar to the well water in Tamba, with each mineral weighing 100g and having a contact time of 100 seconds with 1,000mL of water. Furthermore, since it was not possible to prepare 100g of diamonds, the experiment was carried out with 10g. Next, for each of the above minerals, 100g was used, so the weights were adjusted to 10g, 1g, 0.1g (100mg), 0.01g (10mg), 0.001g (1mg), 0.1mg, 0.01mg, and 0.001mg by cutting out with a dental diamond desk or grinding with a dental diamond bur using a dental magnifying glass. The weight of diamonds was adjusted using melee diamonds, etc. As a test, I also got some diamonds weighing 0.000000000000011mg (the lowest value is the theoretical value for a diamond with a diameter of 0.0025mm, made by Grunberger, as it is impossible to measure), so I tested those too. All of them were 0.0kg.

[0382] <Example 177> The weight changes of 80 kinds of minerals that were found to be effective in the above trunk gravitational axis test were examined to see how they affected the trunk gravitational axis test. The weights used in the experiment were 10g, 1g, 100mg, 10mg, 1mg, 0.1mg, 0.01mg, and 0.001mg. Diamond was also added to the above minerals and the following experiment was carried out. The results of the trunk gravity axis test using various minerals weighing 10 g (10,000 mg) and 100 mL of Yokkaichi tap water after a contact time of 100 seconds are shown in Tables 171 to 174. All minerals in the tables showed trunk gravity axis tests of 1.0 g or more.

[0383] [Table 171]

[0384] [Table 172]

[0385] [Table 173]

[0386] [Table 174]

[0387] <Example 178> The results of the trunk gravity axis test using 1 g (1,000 mg) of various minerals and 100 mL of Yokkaichi tap water after 100 seconds of contact are shown in Tables 175 and 176.

[0388] [Table 175]

[0389] [Table 176]

[0390] <Example 179> The results of the trunk gravity axis test using various minerals weighing 0.1g (100mg) and 100mL of tap water from Yokkaichi after 100 seconds of contact are shown in Tables 177 and 178. All minerals in the table showed trunk gravity axis tests of 1.0g or more.

[0391] [Table 177]

[0392] [Table 178]

[0393] <Example 180> The results of the trunk gravity axis test using various minerals weighing 0.01g (10mg) and 100mL of tap water from Yokkaichi after 100 seconds of contact are shown in Tables 179 and 180. All minerals in the table showed trunk gravity axis tests of 1.0g or more. It has been shown to be effective at a weight of 0.001g (1mg).

[0394] [Table 179]

[0395] [Table 180]

[0396] <Example 181> The results of the trunk gravity axis test using various minerals weighing 0.001g (1mg) and 100mL of tap water from Yokkaichi after 100 seconds of contact are shown in Tables 181 and 182. All minerals in the table had trunk gravity axis tests of 1.0g or more. The result turned positive at a weight of 0.0001g (0.1mg).

[0397] [Table 181]

[0398] [Table 182]

[0399] <Example 182> The results of the trunk gravity axis test using 0.0001g (0.1mg) of various minerals and 100mL of tap water from Yokkaichi after 100 seconds of contact are shown in Tables 183 and 184. The results showed about half the effect of 1mg.

[0400] [Table 183]

[0401] [Table 184]

[0402] <Example 183> The results of the trunk gravity axis test using 0.00001g (0.01mg) of various minerals and 100mL of Yokkaichi tap water after 100 seconds of contact are shown in Tables 185 and 186. As a result, although it was better than tap water, there was not much difference, so it was thought to have no effect.

[0403] [Table 185]

[0404] [Table 186]

[0405] <Example 184> Tables 187 and 188 show the results of trunk gravity axis tests using various minerals weighing 0.000001g (0.001mg) and 100mL of Yokkaichi tap water after 100 seconds of contact. The results showed that they had no ability to eliminate the negative effects of tap water. However, for diamonds, the results of the trunk gravity axis test showed that they had no ability to eliminate the negative effects of tap water when weighed at 0.000000000000011mg.

[0406] [Table 187]

[0407] [Table 188]

[0408] <Example 185> Next, we investigated the effect of contact time on the trunk gravitational axis. The results of the trunk gravity axis test using various minerals weighing 10 g (10,000 mg) and 100 mL of Yokkaichi tap water after 10 seconds of contact are shown in Tables 189 and 190.

[0409] [Table 189]

[0410] [Table 190]

[0411] <Example 186> The results of the trunk gravity axis test using 1 g (1,000 mg) of various minerals and 100 mL of Yokkaichi tap water after 10 seconds of contact are shown in Tables 191 and 192.

[0412] [Table 191]

[0413] [Table 192]

[0414] <Example 187> The results of the trunk gravity axis test using 0.1 g (100 mg) of various minerals and 100 mL of Yokkaichi tap water after 10 seconds of contact are shown in Tables 193 and 194.

[0415] [Table 193]

[0416] [Table 194]

[0417] <Example 188> The results of the trunk gravity axis test using 0.01 g (10 mg) of various minerals and 100 mL of Yokkaichi tap water after 10 seconds of contact are shown in Tables 195 and 196. As a result, it was found to be effective at a weight of 0.001g (1mg).

[0418] [Table 195]

[0419] [Table 196]

[0420] <Example 189> The results of the trunk gravity axis test, in which 0.001g (1mg) of various minerals were in contact with 100mL of tap water from Yokkaichi for 10 seconds, are shown in Tables 197 and 198. For a weight of 0.001g (1mg), contact for 10 seconds was almost the same as contact for 100 seconds, and the effect was turned positive.

[0421] [Table 197]

[0422] [Table 198]

[0423] <Example 190> The results of the trunk gravity axis test of various minerals weighing 0.0001g (0.1mg) with 100mL of Yokkaichi tap water, with the contact time changed from 100 to 10 seconds, are shown in Tables 199 and 200.

[0424] [Table 199]

[0425] [Table 200]

[0426] <Example 191> The results of the trunk gravity axis test using 0.00001g (0.01mg) of various minerals and 100mL of Yokkaichi tap water after 10 seconds of contact are shown in Tables 201 and 202. The results of the trunk gravity axis test using 0.00001g (0.01mg) of various minerals and 100mL of Yokkaichi tap water after 100 seconds of contact and the results after 10 seconds were almost the same, and no effect as a power stone was observed.

[0427] [Table 201]

[0428] [Table 202]

[0429] <Example 192> All the minerals except meteorite were mixed in 100mL of water, and the contact time with the minerals was 10 seconds. The minerals used were the 115 types listed above, each weighing 0.001g (1mg). The results are shown in Table 203. The gravity axis test increased, but it was even stronger when meteorites were added, meaning that meteorites definitely play a major role.

[0430] [Table 203]

[0431] <Example 193> Results of trunk gravity axis test by frequency In addition, since it is known that low frequencies also have great power, we conducted tests on the trunk gravitational axis at different frequencies as follows. Since it is not possible to conduct all experiments, we conducted only representative ones. The results are shown in Table 204. We found that low frequencies are effective, but high frequencies are ineffective.

[0432] [Table 204]

[0433] <Example 194> Experiments using different types of meteorites and the following combinations of minerals Since the number of combinations would be too large to test all combinations, and it would be too much for the inventor, experiments were conducted using the same procedure as in Example 54, with the types of meteorites and the following combinations of minerals. 115 types of minerals were used, and all were adjusted to 0.001g (1mg). 1mg of melee diamonds were inexpensive and easy to obtain. The results are shown in Table 205. Regardless of the type of meteorite, the trunk gravity axis test generally showed an astonishing result of +13kg. With 100 different types of meteorites, the results were astonishing, ranging from +20kg to +23.5kg.

[0434] [Table 205]

[0435] <Example 195> Next, we conducted an experiment with corbicula. The conditions were 65% humidity, 25℃ room temperature, and a 100W FED light bulb 250cm away. Thirty corbicula were lined up on a black plate, and changes were observed every 5 minutes. The number of corbicula that extended their toes and moved around was counted. The same experiment was carried out three times with different specimens, and the average value was calculated. For each meteorite, 1g of meteorite was cut out and poured into a 3000mL beaker. 1000mL of tap water collected on January 17, 2010 at 7-6 Tomari-cho, Yokkaichi City, Mie Prefecture, was poured into the beaker and stirred slowly (using a magnetic stirrer REXIM, 100 rpm) to avoid creating bubbles. 1g of meteorite was soaked in the water for 100 seconds, after which the meteorite was removed and the water was used. The total meteorites were determined by powdering 100 different meteorites, mixing them, and then extracting 1g of each. The results are shown in Table 206. All 30 Jijimis soaked in low-frequency vibrational water containing meteorites, minerals, and minerals began to become active after 25 minutes. All 30 Jijimis soaked in stony meteorite + mineral vibrational water, iron meteorite + mineral vibrational water, and stony-iron meteorite + mineral vibrational water began to become active after 45, 50, and 55 minutes. After 60 minutes, all 30 clams soaked in tektite + mineral vibrational water, moldavite + mineral vibrational water, and Libyan glass + mineral vibrational water began to become active. However, not a single one of the clams soaked in Yokkaichi tap water became active after 60 minutes. The difference was clear. It has been previously proven that the composition of the water has not changed. In other words, meteorite + gemstone vibration water, and meteorite + gemstone vibration + low frequency vibration water, seem to be useful for mollusca organisms such as shellfish.

[0436] [Table 206]

[0437] Example 196: Experiment on mouse life span Next, we conducted an experiment on the lifespan of mice. Three mice were used for each water. Among the mice used, BB6D2F1 showed an average lifespan of 870 days for males and 783 days for females. Males lived longer than females. There was little difference between males and females in terms of maximum lifespan, both around 1100 days. The animals were provided with food (CE-2, CR-3M) manufactured by CLEA Japan, without any drugs. Water (1) to (14) was provided ad libitum through an automatic water dispenser. The life span was measured for three males and three females for each water type, and the average was calculated. None of the mice died suddenly or prematurely. The results are shown in Table 207. As shown in the table, the vibrational water made from all meteorites and gemstones overwhelmingly extended lifespan. Lifespan is normally determined by the fact that sequences on chromosomes called telomeres, which shorten when cells divide, cannot be extended, and if telomeres become shorter than a certain point, they will no longer be able to divide. In animals, this is called the Keizurik limit, and is thought to be the cause of physiological lifespan, and it is thought that animals set their physiological lifespan by losing telomerase. Therefore, lifespan would be extended if the environment were one that produced telomerase, but it is difficult to imagine that telomeres would be extended. In humans, the SpO2 value (blood oxygen concentration) of a healthy person at rest is said to be in the range of 96% to 98%, and a value below 90% is defined as respiratory failure. When respiratory failure occurs, the breathing rate increases, which in turn increases the heart rate, shortening lifespan. According to "Elephant Time, Mouse Time, and the Biology of Size" by Tatsuo Motokawa (Chuko Shinsho), the lifespan of any living creature is said to end when the heart beats 1.5 billion times. It is thought that the increase in blood oxygen concentration reduces the breathing rate, which in turn reduces the heart rate, thereby extending the lifespan.

[0438] [Table 207]

[0439] <Example 197> Relationship between respiratory rate, heart rate and oxygen concentration Next, we investigated the respiratory rate, heart rate, and percutaneous arterial oxygen saturation in humans. (a) Respiration rate (RR), (b) heart rate (HR), and (c) percutaneous arterial oxygen saturation (SpO2) were measured in humans because they cannot be measured in mice. (a) The number of breaths taken per minute was counted. Breathing was done naturally without any conscious effort, with each breath counted as one "exhale and inhale." If the breath stopped midway, the number of breaths was counted as 0.0. (b) Heart rate was measured using an OMRON HCR-7800T (upper arm blood pressure monitor with electrocardiogram), and (c) blood oxygen concentration was measured using an OMRON pulse oximeter HPO-300T. The subjects were divided into 10 age groups: Group A: 10-15 years old, Group B: 16-20 years old, Group C: 21-25 years old, Group D: 26-30 years old, Group E: 31-35 years old, Group F: 36-40 years old, Group G: 41-45 years old, Group H: 46-50 years old, Group I: 51-60 years old, and Group J: 61-65 years old. Those with extremely low or high blood pressure were excluded, and the average of 5 people was calculated. These were taken once per day per sample. As for the drinking conditions, on the first day, 2.5 liters of tap water were drunk in small portions from 21:00, and the breathing rate, heart rate, and oxygen concentration were measured from 20:00 the next day. On the second day, 2.5 liters of tap water + water that had been given the vibrations of the whole meteorite + minerals were drunk in small portions from 21:00, and the breathing rate, heart rate, and oxygen concentration were measured for each sample from 20:00 the next day. Because oxygen partial pressure changes depending on air pressure, breathing-related heating (37°C), and humidity (100%), the experiment was conducted in a room kept at a room temperature of 25°C and humidity of 65%. Cloudy and rainy days were avoided, and sunny days were chosen for the experiment. After resting for 15 minutes, the respiratory rate, heart rate, and SpO2 values ​​were measured and the results are shown in Table 208.

[0440] [Table 208]

[0441] There was no significant difference between well water and tap water. However, there was a clear significant difference in the vibrational water containing all meteorites and the 80 types of minerals mentioned above, using tap water from Yokkaichi. This phenomenon was thought to be explained as follows. The difference in SpO2 was only 1% to 2% at most. In general, the total blood volume is said to be 1 / 13 of the body weight in men. For example, for a person weighing 60 kg, 60÷13≒3.6 kg. Since the specific gravity of blood is about 1.00, the volume is about 3.6 liters. Furthermore, gases can be dissolved in blood in two ways: physically dissolved (in a molecular state) and chemically dissolved (chemically bound to substances in the blood). The physical dissolution of oxygen is 0.29 mL / dL. In chemical dissolution, O2 exists bound to hemoglobin. When reduced hemoglobin binds with O2, it becomes oxyhemoglobin (HBO2). The ratio of oxyhemoglobin to total hemoglobin is called oxygen saturation (HBO2 / (HB+HBO2)). An increase in oxygen partial pressure increases oxygen saturation, and normally, at an oxygen partial pressure of 100 mmHg, the saturation is approximately 98%. 1g of HB binds with 1.33mL of oxygen, so if HB in 100mL is 15g, 1.33mL x 15g = about 20mL can be transported. If the cardiac output per minute is about 5L, then 1L of oxygen can be transported per minute. In other words, the difference between the amount of oxygen transported per minute between 99% and 98% is 10mL per minute, and 10mL x 60 minutes x 24 hours = 14,400mL per day, so even a 1% difference can have a significant impact on lifespan. The number of breaths and the heart rate are linked, and it is said that a person's lifespan ends when their heart beats 1.5 billion times. If the number of breaths decreases and the heart rate decreases accordingly, lifespan will be extended. If a heart rate drops from 80 beats per minute to 65 beats per minute, it would not be surprising if life expectancy increased by 18%. In humans, this would increase life expectancy by more than 18%. In other words, it is highly likely that the increase in life expectancy in mice is due to an effect on heart rate. It was thought that the vibrational water, which was made from tap water in Yokkaichi and had been passed through the meteorite and the above minerals, would increase the amount of oxygen supplied. However, since there was no machine to accurately measure the partial pressure of oxygen in the blood, no data could be obtained from blood tests.

[0442] Other reported effects of using the water of the present invention include: (1) a dying goldfish regained its strength, (2) a pet dog's cataracts improved, (3) a cat that could not walk was able to walk again, (4) a dying cat regained its strength, (5) a dog gave birth to 11 kittens, (6) the coat of dogs and cats improved, (7) plants sprouted two days earlier, (8) cut flowers lasted longer, and (9) ornamental plants began to look greener. Further reported effects in humans include: (1) relief from constipation, (2) less likely to catch a cold, (3) more frequent urination than before drinking the tea, (4) less susceptibility to hangovers, (5) improved liver values, (6) reduced asthma, (7) less susceptibility to alcohol intoxication, (8) reduced diabetes, (9) improved general health, (10) improved cystitis, (11) improved kidney function (creatinine count), and (12) improved skin condition.

[0443] <Water treatment filters and water purifiers> FIG. 38 shows the configuration of a water purifier 12 equipped with a water treatment filter 11. The water treatment filter 11 is provided with a container 15 having a water inlet 13 and a drain outlet 14, and a water flow passage 16 for supplying water from the water inlet 13 to the drain outlet 14. A meteorite 17 is provided in the water flow passage 16 inside the container 15, so that water passing through the water flow passage 16 comes into contact with the meteorite 17. The water purifier 12 is provided with a sound wave irradiation device 18 that applies sound waves to the water passing through the water flow passage 16, and a fluctuation device 19 that applies 1 / f fluctuation. By using the water purifier 12 configured in this manner, water can be made to flow from the water inlet 13, where it comes into contact with the meteorite 17 and is subjected to sound waves and / or 1 / f fluctuations by the sound wave irradiation device 18 and / or fluctuation device 19. In the above embodiment, any of the following structures are within the technical scope of the present invention: (A) a structure without the ultrasonic irradiation device 18 and the fluctuation device 19 (only the water treatment filter 11); (B) a structure with only the ultrasonic irradiation device 18 (the water treatment filter 11 and the ultrasonic irradiation device 18); (C) a structure with only the fluctuation device 19 (the water treatment filter 11 and the fluctuation device 19); or (D) a structure with the ultrasonic irradiation device 18 and the fluctuation device 19 (the water treatment filter 11, the ultrasonic irradiation device 18, and the fluctuation device 19).

[0444] Thus, according to this embodiment, by bringing water into contact with a meteorite, it is possible to provide water treatment filters, cartridges, water purifiers, and water that has been subjected to the meteorite's natural vibrations. In addition, the water purifier is a wave water purifier in which a wave generating material (meteorite + minerals) is placed in the flowing water passage. The presence of a wave generating material including meteorite in the flowing water passage in the container allows the flowing water passing through to come into contact with the wave generating material and experience waves. In addition, according to the filter, tap water or the like enters the filter through the water inlet and exits through the drain at another outlet in the water purifier, during which time the wave action of meteorites and minerals can be exerted on the tap water. As a result, unlike simple tap water filtration, we have succeeded in providing water that has a mild effect on the body by bringing tap water into contact with or passing near a wave-generating substance containing meteorites, for example water with a high oxygen content like blood, and have been able to provide such a filter.

Claims

1. A water treatment filter comprising a container having a water inlet and a drain outlet, a water passageway leading from the water inlet to the drain outlet, and a meteorite disposed within the water passageway, the meteorite weighing 0.0001 g or more.

2. The water treatment filter according to claim 1, wherein the meteorite is pulverized to a size of 20 μm to 300 μm, kneaded into a ceramic material having an infrared emissivity of 90% or more, or mixed into a glaze, and then fired to form a ceramic.

3. 2. The water treatment filter according to claim 1, wherein the meteorite is pulverized to a size of 20 μm to 300 μm and then kneaded into or adsorbed onto the fibers.

4. The water treatment filter according to claim 1, wherein the meteorite is pulverized to a size of 20 μm to 300 μm and then kneaded into an adhesive such as cement.

5. In addition to the meteorites mentioned above, we also offer: arcade, aquamarine, apatite, amazonite, alexandrite, andesine, amber, Iwo stone, ichikaku, Inca rose, wollastonite, emerald, ochre, onyx, opal, garnet, carnelian, kaolinite, amphibole, granite, volcanic glass, volcanic rock (Qinghai medicinal stone) Itoigawa, volcanic rock (lava), talc, limonite, calcite, guiyang stone, fish brain stone, fish, squid and octopus otoliths, gold, silver, and cinnabar stone. (No mineral name), chrysocolla, crystal quartz, chrysoprase, kunzite, quercere stone, basalt, cow's gall, obsidian, amber, sapphire, samarskite, yttrium oxide, copper oxide, coral, sunstone, native copper (pyrite), red pyrite, autumn stone, stalactite, silica, silicic cyst, zirconia (artificial), zircon (natural), super seven, sugilite, soft-shelled turtle shell, spinel, hematite, lime (quicklime), stone Charcoal, abalone shell, xenotime, selenite, diorite, zoisite, ivory, sodalite, turquoise, tiger's eye, diamond, marble, tanzanite, chert, terahertz ore, celestial eye, topaz, tourmaline, Herkimer diamond, pearl, Maifan stone, platinum, palladium, bandit carnelian, jade, bismuth, Himekawa medicinal stone, fluorite, black star, black stone, clam shell (ni 2. The water treatment filter according to claim 1, containing 0.001 g (1 mg) of at least one raw material selected from the group consisting of quartz, quartz, hematite, peridot, sodalite, horn herb, malachite, sea pine, moonstone, mumyoi ware, agate, meng stone, yangki stone, raspirazuri, labradorite, limonite, ruby, ruby ​​in zoisite, antelope horn, lepidolite, roselite, rhodonite, hearth eye, deer antler, and wild horse.

6. A water purifier incorporating an infrared radiator having a wavelength range of 2 μm to 14 μm and an emissivity of 90% or more when treated with the water treatment filter according to any one of claims 1 to 5.

7. A water purifier comprising the water treatment filter according to claim 1.

8. A water treatment method characterized by contacting water with a meteorite having a mass of 0.1 mg or more at a flow rate of 10 mL / sec or less per unit mass (100 L / sec or less per 1 g of meteorite unit mass).

9. (a) meteorites with a mass of 0.1 mg or more, and (b) arcade, aquamarine, apatite, amazonite, alexandrite, andesine, amber, iwo stone, ichikaku, Inca rose, wollastonite, emerald, ochre, onyx, opal, garnet, carnelian, kaolinite, amphibole, granite, volcanic glass, volcanic rock (Qinghai Yakuseki) Itoigawa, volcanic rock (lava), talc, limonite, calcite, guiyang stone, fish brain stone, fish, squid, and octopus otoliths, gold, silver, and kinka stone (minerals). No name), chrysocolla (malachite), crystal quartz, chrysoprase, kunzite, quesera stone, basalt, cow's gall, obsidian, amber, sapphire, samarskite, yttrium oxide, copper oxide, coral, sunstone, native copper (pyrite), red pyrite, autumn stone, stalactite, silica, silicic cyst, zirconia (artificial), zircon (natural), super seven, sugilite, soft-shelled turtle shell, spinel, hematite, lime (quicklime), coal, abalone shell, xeno Thyme, Selenite, Diorite, Zoisite, Ivory, Sodalite, Turquoise, Tiger's Eye, Diamond, Marble, Tanzanite, Chert, Terahertz Ore, Eye Stone, Topaz, Tourmaline, Herkimer Diamond, Pearl, Maifan Stone, Platinum, Palladium, Banded Carnelian, Jade, Bismuth, Himekawa Yakuseki, Fluorite, Black Star, Black Stone, Clam Shell (Bifid Shell), Hematite, Peridot, Sodalite, Horn Health A water treatment method comprising contacting 1 mg or more of at least one mineral selected from the group consisting of malachite, sea pine, moonstone, Mumyoui ware, agate, meng stone, yangki stone, raspirazuri, labradorite, limonite, ruby, ruby ​​in zoisite, antelope horn, lepidolite, roselite, rhodonite, hearth eye, deer antler, and wild horse with water at a flow rate of 10 mL / sec or less per unit mass (1 L / sec or less per 1 g of mineral unit mass).

10. (a) Meteorites with a mass of 0.1 mg or more and (b) (b) Arcade, aquamarine, apatite, amazonite, alexandrite, andesine, amber, Iwo stone, ichikaku, Inca rose, wollastonite, emerald, ochre, onyx, opal, garnet, carnelian, kaolinite, amphibole, granite, volcanic glass, volcanic rock (Qinghai Yakuseki) Itoigawa, volcanic rock (lava), talc, limonite, calcite, guiyang stone, fish brain stone, fish, squid, and octopus otoliths, gold, silver, and cinnabar stone (minerals). No name), chrysocolla, crystal quartz, chrysoprase, kunzite, quesera stone, basalt, cow's gall, obsidian, amber, sapphire, samarskite, yttrium oxide, copper oxide, coral, sunstone, native copper (pyrite), red pyrite, autumn stone, stalactite, silica, silicic cyst, zirconia (artificial), zircon (natural), super seven, sugilite, soft-shelled turtle shell, spinel, hematite, lime (quicklime), coal, abalone shell, xenotime , selenite, diorite, zoisite, ivory, sodalite, turquoise, tiger's eye, diamond, marble, tanzanite, chert, terahertz ore, eye stone, topaz, tourmaline, Herkimer diamond, pearl, Maifan stone, platinum, palladium, banded carnelian, jade, bismuth, Himekawa medicinal stone, fluorite, black star, black stone, clam shell (bifid shell), hematite, peridot, sodalite, horn health, malachite A water treatment method comprising: passing water near at least 1 mg of at least one mineral raw material selected from the group consisting of pine, moonstone, Mumyoui ware, agate, meng stone, yangki stone, raspirazuri, labradorite, limonite, ruby, ruby ​​in zoisite, antelope horn, lepidolite, roselite, rhodonite, hearth eye, deer antler, and wild horse at a flow rate of 10 mL / sec or less per unit mass (1 L / sec or less per gram of mineral unit mass) without contacting the mineral.

11. A water purifier comprising the water treatment filter according to any one of claims 1 to 5 and a sound wave irradiation device capable of applying sound waves of 20 Hz to 10,000 Hz to water passing through the filter.

12. A water purifier comprising the water treatment filter according to any one of claims 1 to 5 and a fluctuation device capable of applying 1 / f fluctuation to water passing through the filter.

13. 6. Water treated with the water treatment filter according to any one of claims 1 to 5, which has the effect of increasing the trunk gravitational axis (the load weight at which the waist collapses) by 5 kg or more.

14. A trunk gravity axis testing device capable of measuring the pressing force between both hands in the vertical direction on the back of a subject, comprising a first pressing operation unit that can be pressed with either palm, a second pressing operation unit that can be pressed with the other palm and in a direction opposite to the pressing force of the first pressing operation unit, and a pressing force measuring unit that can measure the force applied to both pressing operation units.

Citation Information

Patent Citations

  • Strong magnetic energy water activation device and application thereof

    CN102701344A

  • Water purification device

    CN105668878A

  • Ceramic for preparing aerolite activated water, preparation method and application thereof

    CN109761632A

  • Method for preparing meteorite energy water

    CN109956611A

  • Treatment of water by far infrared emitting ceramic

    JP1995039865A